Sterile insect technique for key agricultural pests in Africa: successes, challenges, and future opportunities - Michael M. Githae; Reyard Mutamiswa; Pascal O. Aigbedion-Atalor; Megan Mulcahy; Candice A. Coombes; Sean D. Moore; Martin P. Hill (Crop Protection, 2026)

Parasites of Arctic char (Salvelinus alpinus) in North America: a systematic literature review and an analysis of contemporary data from anadromous populations from Nunavut - Les N. Harris; Phillip R. Morrison; Michael W. Johnson; Sara Bolduc; Ariane Côté; Amélie Papillon; Justine Lapointe; Xuehan Qu; David J. Yurkowski; Connor W. Faulkner; Colin P. Gallagher; Lauren N. Wiens; et al. (Reviews in Fish Biology and Fisheries, 2026)
Parasites play a critical yet understudied role in Arctic ecosystems, particularly within key subsistence species such as Arctic char ( Salvelinus alpinus ). As the Arctic undergoes rapid climate-driven change, establishing baseline parasite biodiversity is essential for monitoring ecological shifts and anticipating emerging health and conservation concerns. This study provides the most comprehensive assessment to date of Arctic char parasites in the North American Arctic by integrating a systematic literature review with new empirical data from 378 Arctic char collected across five Nunavut areas (2020–2024). The literature review (30 studies, 1956–2024) documented 67 parasite taxa—48 identified to species—with helminths (nematodes, cestodes, trematodes, acanthocephalans) dominant. Overall, 82% of taxa occurred in anadromous Arctic char and 54% in freshwater forms, including 22 species unique to anadromous fish. Our empirical assessment identified 35 parasite taxa—23 to species level—including several previously unreported from Arctic char in this region. Common and widespread parasites documented in the empirical assessment included Brachyphallus crenatus , Derogenes varicus , Bothrimonus sturionis , and Alloopistholecithum gibbosum , although notable spatial variation occurred in community composition and infection intensity. The occurrence of rare and previously unreported parasites may suggest emerging shifts in host–parasite dynamics potentially linked to changing prey availability and northward species range expansions. Together, these findings establish an essential baseline for Arctic char parasite biodiversity and highlight the need for continued monitoring to track future changes driven by climate warming, shifting food webs, and their implications for fish health and food security in northern Indigenous communities.

Human neuronal cells SH-SY5Y as an in vitro model to study Neospora caninum infection and innate immune modulation - Natalia Plá; Mercedes M. Burucúa; Dadin P. Moore; Eduardo R. Cobo; Anselmo C. Odeón; Silvina Quintana; Maia S. Marin (The Veterinary Journal, 2026)

Differences in Siderophore Production During the Growth of Phytoplankton in Southern Ocean Incubation Experiments Under High‐ and Low‐Iron Conditions - Randelle M. Bundy; Kristen N. Buck; Bethany D. Jenkins; P. Dreux Chappell; Daniel J. Repeta; Alexa Sterling; Shannon M. Yang; Laura Holland; Léo Mahieu; Laura E. Moore (Environmental Microbiology, 2026)
Iron is an important micronutrient required by marine microorganisms. The Southern Ocean is an ecosystem where primary production is limited by the availability of iron, but how microorganisms in this region adapt to low‐iron conditions or respond to episodic iron inputs is understudied. We tested how external iron additions would impact bacterial production of siderophores during phytoplankton growth using shipboard incubation experiments under a range of iron conditions. Similar heterotrophic bacteria communities and phytoplankton biomass were observed whether iron was added from the continental margin or as inorganic iron. Under both high‐ and low‐iron conditions, the heterotrophic bacteria community remained the same but produced distinct iron‐binding siderophores. Siderophores were detected in the highest concentrations when phytoplankton and heterotrophic bacteria were iron‐limited, and unique compounds were produced in low‐iron conditions compared to when iron was added. Hydrophobic siderophores dominated when iron concentrations were low, and hydrophilic compounds when iron concentrations were higher, and this was likely due to environmental factors rather than changes in the microbial siderophore producers. Our results also highlight that phytoplankton growth likely played an important role in stimulating siderophore production across both low‐ and high‐iron conditions, with important implications for phytoplankton and bacteria interactions.

GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

Dynamic remodeling in lipophilic metabolites during Coffea canephora maturation: A lipidomic study - Marcos V.V. Lyrio; João V.M. de Almeida; Eric C. Gier; Samuel G. Moore; Henzo P. Salvador; Fábio L. Partelli; Facundo M. Fernández; Wanderson Romão; Eustáquio V.R. de Castro (Food Chemistry, 2026)

Reproductive meltdowns underlie arthropod extinctions in the face of climate change - Michael P Moore; Sarah E Nalley; Noah T Leith (Current Opinion in Insect Science, 2026)

Flux Science Without Borders: Strengthening Ecosystem Flux Capacity in Latin America - Tonantzin Tarin; M. Susana Alvarado‐Barrientos; Eugenia González del Castillo; Mónica Cervantes‐Jiménez; Zulia Sánchez‐Mejía; Alejandro Cueva; Alejandro Delgado‐Guerrero; Dulce Flores‐Renteria; Jaime Garatuza‐Payan; César Hinojo‐Hinojo; Karem Meza; David J. P. Moore; et al. (Global Change Biology, 2026)
The future of how we understand and manage ecosystems largely depends on direct and continuous observations that connect local territories to planetary processes. Latin America (LATAM: Mexico, Central and South America, and the Caribbean) hosts ecosystems critical for regulating global carbon, water, and energy cycles. However, persistent underinvestment in science and technology hampers the long‐term monitoring capacity needed to advance regional priorities. Addressing the climate crisis requires investing in local researchers, technicians, and students, providing Earth System Science training that integrates biophysical and sociocultural knowledge. Although English is the lingua franca of science, training in native languages accelerates technical capacity, strengthens regional collaboration, and grounds solutions in local experience. Here, we present TAFE ( Taller de Aprendizaje de Flujos Ecosistémicos ) as an example of how regionally grounded, native‐languages training can strengthen ecosystem flux science in LATAM and beyond. Such initiatives help decentralize knowledge, reduce the underrepresentation of Global South ecosystems in flux databases, and empower the next generation to lead research for both regional and global benefit.

Potato Disease Prevalence and Quality Performance Under Four Soil Health-Related Practices - Kate Binzen Fuller; Kusum Adhikari; Alexander Maas; Christopher McIntosh; Carl Rosen; James E. Crants; Robert P. Larkin; Kim Zitnick Anderson; Anna Stasko; Julie Pasche; Kenneth Frost; Jeff Miller; et al. (American Journal of Potato Research, 2026)

Fentanyl decreases arterial blood oxygen saturation more than furanylfentanyl in mice due to increased apnea - Catherine Demery; Sierra C. Moore; Kelsey E. Kochan; Mengchu Li; Thomas D. Prince; Benjamin M. Clements; Zhongqi Chen; Jessica R. Whitaker-Fornek; Erica S. Levitt; Jessica P. Anand; John R. Traynor (Psychopharmacology, 2026)
Rationale Fatal opioid overdoses involving synthetic opioids have increased >10-fold over the past 8 years. Fentanyl, a potent synthetic opioid acting at the mu-opioid receptor (MOR), has largely replaced heroin as the predominant illicit opioid available. Various analogs have been synthesized from the fentanyl scaffold, including 2-furanylfentanyl, one of the most trafficked analogs from 2019 to 2024. Despite its prevalence, the in vivo effects of furanylfentanyl are not well characterized, especially regarding respiratory depression. Objectives To characterize furanylfentanyl relative to fentanyl in vitro and compare the effects of both drugs in mouse models of antinociception and respiratory depression. Methods The affinity and potency of fentanyl and furanylfentanyl were determined in CHO cells overexpressing MOR. Male and female CD-1 mice were administered ( i.p. ) fentanyl or furanylfentanyl prior to measuring antinociception (warm-water tail withdrawal), respiration (whole-body plethysmography), or oxygen saturation (pulse oximetry). Results Furanylfentanyl behaves as a partial agonist in vitro relative to fentanyl and morphine but with similar affinity and potency at MOR. In mice, fentanyl and furanylfentanyl produced similar effects on breathing parameters (including rate and inspiration time) that were greater than those induced by morphine, yet only fentanyl caused a drastic, long-lasting depletion of blood oxygen saturation. The discrepancy between effects on breathing and oxygen saturation may be explained by a greater number of apneas induced by fentanyl. Conclusions These results highlight the complexity of fentanyl-induced respiratory depression and indicate that recreational use of 2-furanylfentanyl in humans may pose a greater risk of overdose than morphine but lesser than fentanyl.

Adaptation and Response in Drylands: A Dryland Research Agenda and Campaign Strategy - Andrew F. Feldman; Sasha C. Reed; Konrad Wessels; Dennis Ojima; David J. P. Moore; William K. Smith; Niall P. Hanan; Cibele Amaral; Flurin Babst; Joel A. Biederman; Marcy Litvak; Natasha MacBean; et al. (Global Change Biology, 2026)
Dryland ecosystems cover 41% of Earth's land surfaces, account for 44% of cultivated lands and 60% of food sources, and make large contributions to the global water and carbon cycles. However, these ecosystems are experiencing unprecedented extremes including heatwaves, floods, and droughts as well as hotter temperatures and often declining water resource availability. These ecosystems are some of the most challenging to monitor given their high temporal variability with rapid response to their environment as well as vast spatial variability with intermixing of different plant species and life forms amongst bare soil coverage. The Adaptation and Response in Drylands (ARID) campaign was selected by National Aeronautics and Space Administration (NASA) as a scoping study to develop a research agenda for a dryland field campaign. Here, we detail our ARID science research agenda and implementation plan that were developed based on an extensive community engagement effort in over 160 events with over a thousand scientists, land managers, and Tribal communities between 2023 and 2024. The selected science themes cover drought and climate variability, ecosystem structure, function, and biodiversity, carbon cycle interannual variability and trends, and social ecological systems (land management and adaptation). We then detail our remote sensing, modeling, and field‐based strategies to capture high temporal and high spatial resolution processes. Finally, our implementation strategy is presented which includes focus area selections in a core intensive western U.S. domain and distributed international domains. This strategy includes our overarching guiding principles of using multi‐temporal airborne acquisitions and super sites as well as enhancing land management in co‐development with end‐user partners. While originally developed for NASA, our ARID report creates a blueprint for any future dryland field campaign, at any scale, that can be implemented widely for foundational and applied science objectives.

The Integration of Fire Ecology and Freshwater Ecosystems in North America: Knowledge Gaps and Research Needs - Morgan L. Piczak; Ava J. A. Sergio; Caliyena R. Brown; Waverley S. Birch; Rebecca L. Flitcroft; Meg A. Krawchuk; Colin P. R. McCarter; Jonathan W. Moore; Brendan P. Murphy; Brooke E. Penaluna; Prabha A. Rupasinghe; Victoria Steblaj; et al. (Global Change Biology, 2026)
Wildfires, unplanned fires that start and spread under the influence of weather and fuel composition, are increasing in frequency, duration, and severity across North America. While wildfires are one component of wildland fire, a broader natural process in many ecosystems, their changing behavior poses growing ecological and management challenges. Although wildfire is widely recognized as an important disturbance, empirical research quantifying its impacts on freshwater ecosystems remains limited and fragmented. As a result, our understanding of how wildfire affects imperiled freshwater systems remains underdeveloped. The objective of this review was to synthesize the existing empirical literature and identify key knowledge gaps to guide future research on wildfire–freshwater interactions across both biotic and abiotic components. At the biological scale, uncertainties remain around species‐ and community‐level responses (e.g., direct and indirect effects on biota). Freshwater habitat dimensions should also be the focus of further research, including alterations to physical structure (e.g., vegetation) and physicochemical conditions (e.g., temperature). From a management perspective, critical questions relate to fire‐informed restoration (e.g., specialized techniques, role of managed burns) and strategies for enhancing ecosystem resilience (e.g., identifying relevant indicators, links to watershed health). Understanding how land‐use change (e.g., forestry) and climate change interact to influence wildfire regimes and generate cumulative effects across landscapes is also essential in this new wildfire reality. To advance research and practice, we recommend comprehensive monitoring, standardization of methods and indicators, recognition of the role of cultural and prescribed burns, meaningful knowledge co‐production, and bridging the gap between scientific knowledge and management action.

Population Genomics of a Cosmopolitan Weed Provides Insights Into Its Local Adaptation and Recent Demographic History - Marilia Souza Lucas; Christoph Rosche; Isabell Hensen; Stefan G. Michalski; Dávid U. Nagy; Diana Gamba; Renske E. Onstein; Karime Abidkulova; Mohammad Al‐Gharaibeh; Ali A. Al‐Namazi; Sirwan Babaei; Fernando Bastida; et al. (Molecular Ecology, 2026)
Invasive plant species present a growing ecological and economic challenge, and often adapt rapidly to their novel environments through complex demographic and evolutionary processes. Invasion genomics offers powerful tools to disentangle these processes, but most studies rely on geographically narrow sampling across native and non‐native ranges. Erigeron canadensis is a cosmopolitan weed native to North America that has successfully invaded diverse climates worldwide. We used double‐digest restriction site‐associated DNA sequencing (ddRADseq) to investigate the genetic diversity and structure of 280 E. canadensis populations across the Northern Hemisphere. We found that native and non‐native populations maintained comparable genetic diversity. Population structure analyses revealed four genetic clusters that were mainly differentiated along latitudinal and aridity gradients. However, one cluster was strongly overrepresented in the non‐native compared to the native range. In the native range, genetic differentiation was shaped by spatial and environmental gradients, while in non‐native regions human‐mediated dispersal and repeated introductions disrupted environmentally driven genetic structure. Migration network analyses revealed limited intercontinental connectivity and a possible role of long‐distance dispersal in within‐range expansions. Genomic offset analyses showed that genotype‐environment mismatches in non‐native populations associated with reduced growth and reproduction. Together, our results indicate that the invasion dynamics of E. canadensis were driven by multiple introductions, population admixture, and lineage sorting, while some genotypes contributed disproportionately to the spread of this invader. The presence of apparent maladaptation suggests that even long‐established invaders may still be evolving in response to their novel environment, raising concerns about potential future expansions.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Current knowledge about neosporosis in Colombia - Piedad C. Rivas López; Samuel E. Idarraga-Bedoya; Luisa F. Mendoza-Morales; Jenny J. Chapparro-Gutiérrez; Agustín Góngora; Milton M. McAllister; Dadín P. Moore (Veterinary Research Communications, 2026)

Chronic exposure to waterborne nickel significantly reduced growth of juvenile crayfish (Faxonius virilis) - Adrian P. Moore; Mark L. Wildhaber; Zachary D. Beaman; Kendell R. Bennett; Karlie K. Ditter; Danielle Cleveland; Jenna A. Blanton; Tyler J. Grant (Ecotoxicology, 2026)

Ti solubility in biotite at low pressure in metapelitic systems: the Torres del Paine case - Maria M. Ariza-Acero; Lukas P. Baumgartner; C. Tom Foster; Marisa D. Acosta; Jo Moore; Jack Gillespie; Robert Bodner; Guillaume Siron (Contributions to Mineralogy and Petrology, 2026)
The Torres del Paine Intrusive Complex (TPIC) is a shallowly emplaced pluton surrounded by a well-defined contact aureole, providing an ideal setting to test Ti-in-biotite thermometry. We compare existing Ti-in-biotite thermometers with phase petrology constraints and found that they systematically overestimate peak metamorphic temperatures. This discrepancy arises from a significant increase in Ti solubility at low pressures $$(<1$$ kbar). In fact, we demonstrate that a pressure difference of $$\sim 0.25$$ kbar within the aureole leads to an increase of 0.1 a.p.f.u. in Ti content, suggesting that pressure plays a key role in Ti incorporation at these low pressures. At lower pressures, the Ti-oxy substitution becomes saturated, and Ti incorporation is dominated by a Ti-spinel exchange mechanism. Additionally, textural and chemical analyses reveal that composition vary between small domains of a few hundred micrometers, indicating that local compositional heterogeneities significantly influences Ti content in biotite, even when a Ti-oxide and an Al-rich silicate are nearby. Finally, biotite starts growing near to the biotite-in isograd, and keeps on growing, so that its composition does not fully adjust to the peak composition due to the short metamorphic event. These findings highlight that both pressure and temperature influence the Ti content in biotite. The application of Ti-in-biotite thermometry requires careful consideration of equilibrium domains and growth kinetics.

Informing spatial conservation prioritization with species’ traits - Liam A. Trethowan; Laura Jennings; Haerul Arifin; Renata Borosova; Gemma L. C. Bramley; Marie Briggs; Osanna Chu; Ruth P. Clark; Sally Dawson; Kiran L. Dhanjal‐Adams; Yance de Freitas; James Hartup; et al. (Conservation Biology, 2026)
New Guinea, the most botanically diverse island on the planet, is the location for one of the boldest conservation initiatives. The Manokwari Declaration aims to achieve 70% conservation designation for the Bird's Head Peninsula. This is 40% higher than the 2022 Global Biodiversity Framework target. However, there is a lack of species occurrence data to support evidence of where biodiversity can be best protected. To address this, we integrated plant trait data from taxonomic descriptions in species occurrence models that can inform conservation planning. Inclusion of traits improved the performance of co‐occurrence models of ∼800 plant species across the 100,000‐km 2 landscape. Traits generally improved model performance, but not all traits contributed equally (e.g., leaf size and red flower color most improved accuracy of occurrence prediction). Likewise, trait‐parameterized models tended to be most useful with rare species occurrence prediction, but this was inconsistent among traits. Under 70% protection, three‐quarters of the areas selected conserved trait diversity. Critically, trait diversity also increased the chances that areas at high risk of deforestation were selected as conservation priorities. Overall, we found that plant species’ traits, often key parameters of ecosystem function and resilience, improved spatial conservation planning.

Racial and ethnic disparities in environmental chemical exposures and hypertensive disorders of pregnancy: The ECHO-wide cohort study - Hongxiu Liu; Amii M. Kress; Emma X. Yu; Xuejuan Ning; Akhgar Ghassabian; Linda G. Kahn; Shilpi Mehta-Lee; Sara Brubaker; Akram Alshawabkeh; John Meeker; Carlos A. Camargo; Shakira F. Suglia; et al. (Environmental Pollution, 2026)

Identification of Dolly Varden (Salvelinus malma) in the Canadian Arctic east of the Mackenzie River - Spencer Y. Weinstein; Amanda Dumond; Tracey N. Loewen; James D. Reist; Matthew C. Hale; Colin P. Gallagher; Jean-Sébastien Moore; Les N. Harris; Ross F. Tallman; Robert Bajno; Zoya A. Martin; Paul M. Craig; et al. (Environmental Biology of Fishes, 2026)

Long‐Term Habitat Use Patterns of Ray Assemblages in Coastal and Inshore Waters of the Eastern Gulf of Mexico - Julian R. Gatch; Matthew E. Kimball; Robert P. Dunn; Alan Moore; Lina Vanesa Garzón‐Peña; Angelica Barrera‐García (Marine Ecology, 2026)
Rays are common marine mesopredators that use coastal and estuarine habitats during multiple life history stages for critical functions. They are long‐lived, late to mature, and have low reproductive output, making them vulnerable to and slow to recover from population threats such as overfishing and habitat loss. Considering this, examining ray abundance, assemblage structure and distribution, as well as identifying ray habitat use patterns, especially over long time periods, is important. Fishery‐independent sampling (tangle nets, bottom longlines, and rod and reel) was used to examine ray species composition, distribution, and abundance in St. Joseph Sound over a 10‐year period. Six different ray species were caught, with three species making up 93.5% of the catch: southern stingray ( Hypanus americanus ), cownose ray ( Rhinoptera sp.), and bluntnose stingray ( Hypanus say ). Ray abundance and assemblage composition varied across the study area, potentially due to differences in abiotic or biotic conditions. Analyses revealed that this area is used by multiple ray species for multiple life history functions, including use by cownose rays as a pupping area. This study represents the first in‐depth analysis of the batoid community in St. Joseph Sound, and collectively, the results suggest that the study area serves as important habitat supporting ray communities in the coastal and inshore waters of the eastern Gulf of Mexico.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Signal characteristics of potential airbursts in Titan’s atmosphere - Elisa Dong; Catherine D. Neish; John E. Moores; Shigeru Wakita; Gareth S. Collins; Peter G. Brown; Ralph D. Lorenz; Benjamin Fernando; Mark P. Panning (Icarus, 2026)

Micro‐Refuges or Ecological Traps: Context‐Dependent Effects of Rock Pools on Intertidal Biodiversity Across Latitudes - Louise B. Firth; Andrea Desiderato; Antony M. Knights; J. David Aguirre; Juan C. Astudillo; Juan C. Azofeifa‐Solano; David T. Bilton; Su Yin Chee; Hartvig C. Christie; Ronaldo A. Christofoletti; Amelia Curd; Katherine A. Dafforn; et al. (Global Ecology and Biogeography, 2026)
Aim We investigated how local‐scale environmental heterogeneity influences biodiversity patterns across broad biogeographic gradients, using intertidal microhabitats as a model system within one of the most environmentally stressful ecosystems on Earth. Location Intertidal habitats at 26 locations (two rocky shore sites per location) across six continents, spanning 98° of latitude (38°S to 60°N). Time Period 2019–2022. Major Taxa Studied Algae, sessile and mobile invertebrates. Methods We compared biodiversity and thermal environments across contrasting microhabitats (rock pools and adjacent emergent rock) along a latitudinal gradient, sampling during environmentally ‘milder’ and ‘harsher’ periods. Biodiversity was quantified using multiple richness metrics (mean, total, unique taxa) and functional diversity. Results Microhabitat differences strongly influenced biodiversity patterns across latitude. Rock pools consistently supported higher taxonomic and functional diversity than emergent rock, irrespective of sampling period, reflecting their ability to buffer thermal extremes, particularly under harsher conditions. Mean species richness exhibited a non‐linear, s‐shaped latitudinal pattern, with lowest values near the equator and higher richness at mid‐latitudes, diverging from classical Latitudinal Diversity Gradient expectations. Biodiversity differences between microhabitats were greatest in temperate regions and diminished at low latitudes, where extreme conditions constrained diversity across habitats. Main Conclusions Local environmental heterogeneity can substantially modify, and in some cases obscure large‐scale biodiversity patterns. By mediating exposure to environmental stress, intertidal microhabitats provide insight into how fine‐scale variability interacts with latitudinal stress gradients to shape biodiversity distributions. Incorporating microhabitat variability into biogeographic frameworks is important for understanding global biodiversity patterns and predicting ecological responses to climate change.

Satellite observations reveal ecosystem resistance and resilience to short-term water stress driven by dominant vegetation along a rainfall gradient in Australia - Huanhuan Wang; Qiaoyun Xie; Sally E. Thompson; Caitlin E. Moore; David L. Miller; Erik J. Veneklaas; Richard P. Silberstein; Xing Li; Jingfeng Xiao; Belinda E. Medlyn; William K. Smith (Remote Sensing of Environment, 2026)

Road Salt Impacts on Soil Properties and Permanent Nitrogen Removal Capacity of Freshwater Urban Wetlands - Md. Moklesur Rahman; Marc Peipoch; Jinjun Kan; Eric Moore; Matthew Sena; Mukta Kantak; Suparn Sharma; Chander Lekha; Shreeram P. lnamdar (Wetlands, 2026)
Freshwater urban wetlands are important ecosystems that can naturally filter and remove excess nitrogen (N) through the process of denitrification (DNF). However, anthropogenic inputs such as road salt application may affect the N removal capacity of urban wetlands by affecting the relative rates of DNF and another competing reductive process that retains N – dissimilatory nitrate reduction to ammonium (DNRA). Here, we assessed 13 roadside wetlands in urban/suburban areas of Delaware, USA to determine the effects of road salt sodium (Na + ) on soil physical, chemical, and biological properties and the rates of DNF and DNRA. Based on soil Na + concentrations, wetlands were grouped into three categories: low (Na + < 70 mg kg −1 ), medium (70 mg kg −1 < Na + < 150 mg kg −1 ) and high (Na + > 150 mg kg −1 ). Rates of DNF and DNRA ranged from 0.8 – 83 and 0.2 – 24 μg N L −1 slurry h −1 , respectively. DNF was significantly lower in high Na + category wetlands whereas DNRA did not show any significant differences. Similarly, macroaggregates and bioavailable Fe were lowest in the high Na + category, whereas concentrations of soil NH 4 + , NO 3 − , TOC, TN, and microbial metrics (biomass and nosZ and nrfA functional genes) did not reveal any consistent patterns. These findings imply that road salt Na + input exhibited mixed effects on soil properties in these wetlands. Overall, elevated Na + from road salt could undermine the N removal capacity of the roadside urban wetlands. Therefore, strategies should be implemented to reduce the application of road salt or identify effective alternatives.

Biomechanical Analysis of the Effects of Knee Savers on Knee Joint Loading During High Knee-Flexion Tasks - Liying Zheng; John Z. Wu; Kevin D. Moore; Ashley L. Hawke; Robert E. Carey; Christopher M. Warren; Scott P. Breloff (Annals of Biomedical Engineering, 2026)

Mesenchymal cell-derived extracellular vesicles ameliorate age-related deficits in working memory and in vivo MRI measures of white matter structure and function in rhesus monkeys - Evan C. Mackie; Chia-Hsin Cheng; Maya N. Alibrio; Christine Rutledge; Hongqi Xin; Michael Chopp; Ryan P. McCann; Douglas L. Rosene; Qiong Yang; Ella Zeldich; Maria Medalla; Bang-Bon Koo; et al. (GeroScience, 2025)
Aging humans and non-human primates both exhibit a similar pattern of cognitive decline beginning in middle age that is characterized by progressive impairments in rule learning, executive function, and working and recognition memory—functions often associated with dysfunction of prefrontal and medial temporal lobe regions. The heterogeneity and inter-subject variability in aging and age-related cognitive impairments present challenges for developing effective therapeutics and can be attributed to differing degrees of cortical white matter (WM) damage and alterations to local and long-range prefrontal and temporal networks. A promising therapeutic that has been shown to be efficacious in mitigating WM damage and improving cognitive function in rodent models is mesenchymal cell-derived extracellular vesicles (MSC-EVs). In the present study, late middle-aged rhesus monkeys were systemically administered monkey-derived MSC-EVs every 2 weeks for 18 months. We demonstrate that MSC-EV treatment improves spatial working memory and decreases the frequency of perseverative responses with largely no effects on recognition memory. These cognitive improvements were associated with increases in MRI diffusion measures of WM structural integrity over time as well as preservation of inter-network functional connectivity as measured by resting-state functional MRI. These findings suggest that MSC-EV treatment can slow or reverse age-related cognitive decline while strengthening WM integrity and improving functional connectivity in late middle-aged rhesus monkeys.

Associations between concurrent neonicotinoid, pyrethroid, and organophosphate insecticide metabolites and neurocognitive performance in Ecuadorian adolescents - Jessica Yen; Kun Yang; Tuo Lin; Xin M. Tu; Georgia Kayser; Rajendra P. Parajuli; Ana Skomal; Sheila Gahagan; Jose Suarez-Torres; Suzi Hong; Raeanne C. Moore; Jose R. Suarez-Lopez (Science of The Total Environment, 2025)

Environmental drivers of foraging by deep-diving cetaceans: Roles of mesoscale oceanography and light-driven cycles - Thomas A. Clay; Gemma Carroll; Megan A. Cimino; Jennifer L. Miksis-Olds; Katie A. Kowarski; Anthony P. Lyons; Peter I. Miller; Timothy S. Moore; Joseph D. Warren; Elliott L. Hazen (Progress in Oceanography, 2025)

Biomarkers and organic carbon isotopes in Pennsylvanian–Early Permian coals of the Ordos Basin: Implications for palaeoenvironmental evolution in North China - Yang Liang; Wei Yuan; Jingjing Liu; Victor P. Nechaev; Tim A. Moore; Shaowei Zhang; Qian Wang; Jintian Zheng; Xiaoyun Yan; Mengda Yao; Shuai Kang; Shifeng Dai (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

The effects of cadmium and high fructose diet on metabolic and reproductive health in female CD-1 mice - Victoria R. Adams; Janice A. Dye; Micheal G. Narotsky; Makala L. Moore; Helen H. Nguyen; Aubrey L. Sasser; Kaberi P. Das; Lillian F. Strader; Joseph P. Pancras; Donna Hill; Chloe Davis; Wanda C. Williams; et al. (Food and Chemical Toxicology, 2025)

Invasive freshwater jellyfish (Craspedacusta cf. sowerbii) in the Hudson River basin, NYS: comparisons of detection methods - Jacob P. Moore; Hyatt C. Green; Donald J. Stewart; Florian Lüskow; Maxwell L. Wilder (Hydrobiologia, 2025)

Correction: The Natural History Study and Biomarker Collection of the Clinical Research Consortium for the Study of Cerebellar Ataxia (CRC-SCA) - Yicheng Lin; Nadia Amokrane; Sandie Worley; Lauren R. Moore; Andrew Rosen; Laura P. Crespo; Kelsey Trace; Tetsuo Ashizawa; Andrew Billnitzer; Susan Perlman; Aaron Fisher; Khalaf Bushara; et al. (The Cerebellum, 2025)

Investigating Sulfotransferase Mediated Drug Interactions of Ethinylestradiol using a Physiologically Based Pharmacokinetic Model - Harry P. Moore; Kuan-Fu Chen; Aki T. Heikkinen; Sibylle Neuhoff; Udoamaka Ezuruike; Jean Dinh; Iain Gardner; Hannah M. Jones; Felix Stader (The AAPS Journal, 2025)

Profiling the plant cell wall: A comparison of glycan array and immunological methods for studying plant polysaccharides and glycoproteins - Eugene Badenhorst; Paul Hills; John P. Moore (South African Journal of Botany, 2025)

Decision-making Dynamics of Pregnant and Lactating Women (PLW) Participating in a Community Health and Nutrition Intervention in Jordan - R. Brown; L. Miller; Y. Ren; I. Moore; A. Alghanmi; r. Safadi; P. Webb; R. Shrestha; S. Ghosh (Journal of the Academy of Nutrition and Dietetics, 2025)

Arctic lake trout ( Salvelinus namaycush ) show evidence of seasonal acclimation of cardiac adrenergic sensitivity but not heat tolerance - Emily P. Williams; Les N. Harris; Jean‐Sébastien Moore; Ella K. Middleton; Shira A. Berkelhammer; Ben Speers‐Roesch; Matthew J. H. Gilbert (Journal of Fish Biology, 2025)
Many Arctic fishes experience prolonged periods of extreme cold and large thermal variation over both rapid and seasonal time scales which challenge critical physiological functions. In the central Canadian Arctic, we caught wild adult lake trout ( Salvelinus namaycush ) acclimatized to winter and summer temperatures to determine the extent to which they seasonally adjust cardiac thermal performance and adrenergic control. We assessed the intrinsic and maximum heart rate ( f Hint and f Hmax ) of anaesthetised fish through cholinergic blockade and either adrenergic blockade ( f Hint ) or stimulation ( f Hmax ) during acute warming. Contrary to expectations, S. namaycush showed largely consistent heart rate responses to acute warming between seasons and adrenergic treatments. The f Hmax increased with acute warming and reached a peak (peak f H ) of 83 and 93 beats min −1 at temperatures ( T peak ) of 19.6 and 20°C and arrhythmia occurred at temperatures ( T arr ) of 22.7 and 22.3°C in winter and summer, respectively. However, in the winter, adrenergic stimulation was important to achieve peak f H at high temperatures; adrenergic blockade in winter did not affect T peak (18.3°C) or T arr (21°C) but lowered peak f H to only 68 beats min −1 ( p f H , when compared at common, cool to moderate temperatures, winter acclimated fish did exhibit slower atrioventricular conduction (longer PR interval), slower ventricular depolarization (longer QRS duration) and a shorter overall systolic duration (lower QT interval). Overall, S. namaycush exhibited no seasonal plasticity in cardiac thermal tolerance and modest seasonal changes in adrenergic control at high temperatures and in cardiac electrical activity. This limited thermal plasticity may constrain their ability to cope with seasonally distinct thermal challenges including extreme heat events and increase their reliance on other coping or avoidance mechanisms when thermal refugia are available (e.g. behavioural thermoregulation). An increased need for avoidance behaviour could limit the accessibility of key habit for foraging and spawning which occurs in late summer in this region (Dubos et al., 2024).

New records of fishes from the Coral Sea Marine Park, Australia - Yi-Kai Tea; Tiffany L. Sih; Fenton Walsh; Timothy Bennett; Luiz A. Rocha; Ghislain Bardout; Amanda Hay; Kerryn Parkinson; Sally Reader; Indiana J. Riley; John J. Pogonoski; Jeffrey W. Johnson; et al. (Coral Reefs, 2025)
With an area covering just under 1 million km 2 , Australia’s Coral Sea Marine Park (CSMP) is among the largest marine protected areas globally. Yet, the demersal deep-reef fish fauna of the CSMP remains poorly described, due in part to its remote location, as well as its sheer size, much of which is inaccessible below conventional SCUBA diving depths. Recent remotely operated vehicle (ROV) explorations conducted by the Schmidt Ocean Institute provided an opportunity to explore the benthic ichthyofauna of deep mesophotic and rariphotic coral ecosystems. Contributions to the deep, demersal ichthyofauna of Australia’s CSMP are herein supplemented with an integrative dataset consisting of ROV imagery and specimen vouchers. Sixty-two new records of fishes from 26 families are reported from the CSMP. Of these, 45 are new Australian records, one of which is also a new family record for Australia. Four species are new records for the Southern Hemisphere, and 21 species are potentially new to science. We report new voucher material for 29 species, including several species previously identified as new for the CSMP with no voucher specimens.

The Natural History Study and Biomarker Collection of the Clinical Research Consortium for the Study of Cerebellar Ataxia (CRC-SCA) - Yicheng Lin; Nadia Amokrane; Sandie Worley; Lauren R. Moore; Andrew Rosen; Laura P. Crespo; Kelsey Trace; Tetsuo Ashizawa; Andrew Billnitzer; Susan Perlman; Aaron Fisher; Khalaf Bushara; et al. (The Cerebellum, 2025)

Limited Regulation of Canopy Water Use Efficiency by Stomatal Behavior Under Drought Propagation - Feng Li; Qinchuan Xin; Chuixiang Yi; Steven A. Kannenberg; Julia K. Green; Mirco Migliavacca; David J. P. Moore; Armen R. Kemanian; Pierre Gentine; Paul C. Stoy; Fangyue Zhang; Yujiu Xiong; et al. (Global Change Biology, 2025)
Water use efficiency (WUE) is a critical ecosystem function and a key indicator of vegetation responses to drought, yet its temporal trajectories and underlying drivers during drought propagation remain insufficiently understood. Here, we examined the trajectories, interdependencies and drivers of multidimensional WUE metrics and their components (gross primary production (GPP), evapotranspiration, transpiration (T), and canopy conductance (Gc)) using a conceptual drought propagation framework. We found that even though the carbon assimilation efficiency per stomata increases during drought, the canopy‐level WUE (represented by transpiration WUE (TWUE)) declines, indicating that stomatal regulation operates primarily at the leaf level and cannot offset the drought‐induced reduction in WUE at the canopy scale. A stronger dependence on T and TWUE indicates that the water–carbon trade‐off relationship of vegetation more inclines toward water transport than carbon assimilation. Gc fails to prevent the sharp decline in GPP during drought and has limited capacity to suppress T, as reflected by the reduction magnitude and the threshold (the turning point at which a component shifts from a normal to drought‐responsive state). The primary drivers of the water–carbon relationship under drought propagation include vapor pressure deficit and hydraulic traits. Among plant functional types, grasslands show the strongest water–carbon fluxes in response to drought, whereas evergreen broadleaf forests exhibit the weakest response. These findings refine our comprehensive understanding of multidimensional ecosystem functional dynamics under drought propagation and enlighten how the physiological response of vegetation to drought affects the carbon and water cycles.

The Response and Recovery of Carbon and Water Fluxes in Australian Ecosystems Exposed to Severe Drought - C. Stephens; B. Medlyn; L. Williams; J. Knauer; A. Inbar; E. Pendall; S. K. Arndt; J. Beringer; C. M. Ewenz; N. Hinko‐Najera; L. B. Hutley; P. Isaac; et al. (Global Change Biology, 2025)
Climate change‐driven increases in drought risk pose a critical threat to global carbon and water cycles. However, ecosystem‐scale responses remain poorly quantified, particularly for severe, multiyear drought events. We addressed this gap by examining ecosystem‐scale carbon and water flux sensitivity to the extreme 2018–19 drought in Australia using data from 14 eddy covariance flux sites. The ecosystems span grasslands and semi‐arid woodlands to tropical and temperate forests. The driest sites (classed as “grass” and “very dry”) experienced drastic productivity impacts, with a 65% decrease in Gross Primary Productivity (GPP) over 2 years relative to the pre‐drought average. However, fluxes in “dry,” “seasonally wet” and “wet” ecosystems showed remarkable resistance, with no overall change in GPP. All sites recovered rapidly; carbon fluxes in the first post‐drought year matched (and generally exceeded) those of a climatically similar pre‐drought year. Drought responses were strongly mediated by ecosystem‐specific strategies. The driest ecosystems showed direct coupling of productivity to water availability, while intermediate ecosystems (dry and seasonally wet) leveraged stored soil water to maintain evapotranspiration and productivity under drought. At these sites, water was conserved over wet periods (evapotranspiration rainfall). This mechanism mitigating periodic water stress under high rainfall variability likely contributed to the notable drought resistance of the dry and seasonally wet sites. The monthly water deficit index (MWDI) emerged as a robust predictor of productivity across space, highlighting that short‐term water availability deficits strongly influence overall ecosystem composition. Analysis of drought response mechanisms suggested rapid leaf loss under water stress, particularly at the driest sites. Our findings underscore the importance of accounting for sub‐surface water storage and diverse drought response strategies in vegetation models. We provide critical benchmarks for improving parameterization of plant‐water relations, aiding efforts to inform climate‐robust management strategies.

Preoperative Micronutrient Repletion Strategies in Metabolic and Bariatric Surgery: A Systematic Review - Xueying Tang; Dianne P. Reidlinger; Megan Crichton; Lillian Craggs-Dino; Flavia Fayet-Moore; Skye Marshall (Journal of the Academy of Nutrition and Dietetics, 2025)

Dental and mandibular morphology of Peligrotherium tropicalis (Mammalia, Meridiolestida) from the Paleocene of Patagonia, Argentina - G. W. Rougier; N. Paez-Arango; J. P. Moore; Z. Biven-Leslie (Journal of Mammalian Evolution, 2025)

Influence of virtual reality stallion collection simulation on student salivary cortisol levels - A. Schwab; P. Linne; J.L. Zoller; C.J. Huseman; J.L. Leatherwood; K. Dunlap; J. Harlin; A. Baxter; M. Jensen; B.L. Paris; G.E. Moore (Journal of Equine Veterinary Science, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Corrigendum to “Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes” [Biol. Conserv. 300 (2024), 110843] - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2025)

Declines in greater bilby (Macrotis lagotis) geographic range and realised niche are best explained by the invasive red fox (Vulpes vulpes) - Hayley M. Geyle; Alys R. Young; Brett P. Murphy; Chris R. Dickman; Christine Schlesinger; Kelly M. Dixon; Harry Moore; Sarah Legge; Jennifer Silcock; Naomi Indigo; Martin Dziminski; Bruce Greatwich; et al. (Biological Conservation, 2025)

Synthesis of encapsulated nanofertilizer from biogas plant digestate - Edward D. Nasser; Joel Kenneth M. Ngojo; Ramiro Emerson C. Amon; Jayvee Moore S. Dy; Julius J. Rosalia; Chosel P. Lawagon (Bioresource Technology Reports, 2025)

Labile Soil Carbon Heterogeneity Driven by Consumer Engineering of Aboveground Structure in a Kenyan Savanna - Elizabeth S. Forbes; Dana D. Moore; John Naisikie Mantas; Joshua Schimel; Truman P. Young; Hillary S. Young (Ecosystems, 2025)
Aboveground ecosystem structure moderates and even confers essential ecosystem functions. This includes an ecosystem’s carbon dynamics, which are strongly influenced by its structure: for example, tropical savannas like those in central Kenya store substantial amounts of carbon in soil. Savannas’ belowground allocation of carbon makes them important for global carbon sequestration, but difficult to monitor. However, the labile soil carbon pool is responsive to changes in ecosystem structure and is thus a good indicator of overall soil organic carbon dynamics. Kenya’s savanna structure is controlled by belowground ecosystem engineers (termites), ambient weather conditions, and the aboveground engineering influences of large-bodied, mammalian consumers. As a result, climate change and biodiversity loss are likely to change savannas’ aboveground structure. To predict likely outcomes of these threats on savanna soil carbon, it is critical to explore the relationships between labile soil carbon and ecosystem structure, local climate, and mammalian consumer community composition. In a large-scale, long-term herbivore exclosure experiment in central Kenya, we sampled labile carbon from surface soils at three distinct savanna structural elements: termite mounds, beneath tree canopies, and the grassland matrix. In one sampling year, we measured total extractable organic carbon (TEOC), total extractable nitrogen (TEN), and extractable microbial biomass for each sample. Across three sampling years with varying weather conditions, we measured rate of labile soil carbon mineralization. We quantified areal coverage of each structural element across herbivore community treatments to estimate pool sizes and mineralization dynamics at the plot scale. Concentrations and stocks of soil TEOC, TEN, and microbial biomass were driven by the structural element from which they were sampled (soils collected under tree canopies generally had the highest of each). Large-bodied herbivore community composition interacted variably with concentrations, stocks, and carbon mineralization, resulting in apparently compensatory effects of herbivore treatment and structural element with no net effects of large herbivore community composition on plot-scale labile carbon dynamics. We confirmed engineering of structural heterogeneity by consumers and identified distinct labile carbon dynamics in each structural element. However, carbon and nitrogen were also influenced by consumer community composition, indicating potentially compensatory interacting effects of herbivore treatment and structural element. These results suggest that one pathway by which consumers influence savanna carbon is by altering its structural heterogeneity and thus the heterogeneity of its plot-scale labile carbon.

The Influence of Material Properties and Wall Thickness on Predicted Wall Stress in Ascending Aortic Aneurysms: A Finite Element Study - Yu Zhu; Selene Pirola; M. Yousuf Salmasi; Sumesh Sasidharan; Serena M. Fisichella; Declan P. O’Regan; James E. Moore Jr; Thanos Athanasiou; Xiao Yun Xu (Cardiovascular Engineering and Technology, 2025)
Purpose Finite element analysis (FEA) has been used to predict wall stress in ascending thoracic aortic aneurysm (ATAA) in order to evaluate risk of dissection or rupture. Patient-specific FEA requires detailed information on ATAA geometry, loading conditions, material properties, and wall thickness. Unfortunately, measuring aortic wall thickness and mechanical properties non-invasively poses a significant challenge, necessitating the use of non-patient-specific data in most FE simulations. This study aimed to assess the impact of employing non-patient-specific material properties and wall thickness on ATAA wall stress predictions. Methods FE simulations were performed on 13 ATAA geometries reconstructed from computed tomography angiography (CTA) images. Patient-specific material properties and wall thicknesses were made available from a previous study where uniaxial tensile testing was performed on tissue samples obtained from the same patients. The ATAA wall models were discretised with hexahedral elements and prestressed. For each ATAA model, FE simulations were conducted using patient-specific material properties and wall thicknesses, and group-mean values derived from all tissue samples included in the same experimental study. Literature-based material property and wall thickness were also obtained from the literature and applied to 4 representative cases. Additional FE simulations were performed on these 4 cases by employing group-mean and literature-based wall thicknesses. Results FE simulations using the group-mean material property produced peak wall stresses comparable to those obtained using patient-specific material properties, with a mean deviation of 7.8%. Peak wall stresses differed by 20.8% and 18.7% in patients with exceptionally stiff or compliant walls, respectively. Comparison to results using literature-based material properties revealed larger discrepancies, ranging from 5.4% to 28.0% (mean 20.1%). Bland-Altman analysis showed significant discrepancies in areas of high wall stress, where wall stress obtained using patient-specific and literature-based properties differed by up to 674 kPa, compared to 227 kPa between patient-specific and group-mean properties. Regarding wall thickness, using the literature-based value resulted in even larger discrepancies in predicted peak stress, ranging from 24.2% to 30.0% (mean 27.3%). Again, using the group-mean wall thickness offered better predictions with a difference less than 5% in three out of four cases. While peak wall stresses were most affected by the choice of mechanical properties or wall thickness, the overall distribution of wall stress hardly changed. Conclusions Our study demonstrated the importance of incorporating patient-specific material properties and wall thickness in FEA for risk prediction of aortic dissection or rupture. Our future efforts will focus on developing inverse methods for non-invasive determination of patient-specific wall material parameters and wall thickness.

Stronger together: a cross-SIG perspective on improving drug development - Luke Fostvedt; Jiawei Zhou; Anna G. Kondic; Ioannis P. Androulakis; Tongli Zhang; Meghan Pryor; Luning Zhuang; Jeroen Elassaiss-Schaap; Phyllis Chan; Helen Moore; Sean N. Avedissian; Jeremy Tigh; et al. (Journal of Pharmacokinetics and Pharmacodynamics, 2025)

Comparing freshwater mussel responses to stress using life-history and Dynamic Energy Budget theory - Ines Haberle; Adrian P. Moore; Valery E. Forbes; Richard A. Brain; Daniel J. Hornbach; Nika Galic; Maxime Vaugeois (Science of The Total Environment, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

Determination of PCB and PAH tissue levels in bottlenose dolphins that stranded in the Mississippi sound before and after the unusual mortality event in 2019 - Nelmarie Landrau-Giovannetti; Jordan Rogers; Ryanne Murray; Stephen R. Reichley; Debra P. Moore; Theresa Madrigal; Ashli Brown; Ashley Meredith; Christina Childers; Darrell Sparks; Moby Solangi; Beth Peterman; et al. (Science of The Total Environment, 2024)

Override forces through clumps of small vegetation - Marc N. Moore; Christopher Goodin; Ethan Salmon; Michael P. Cole; Paramsothy Jayakumar; Brittney English (Journal of Terramechanics, 2024)

The root extracellular trap; a complex and dynamic biomatrix network essential for plant protection - Azeddine Driouich; Marie-Laure Follet Gueye; Maïté Vicré; John P. Moore (Current Opinion in Plant Biology, 2024)

Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2024)

Mn-porphyrins in a four-helix bundle participate in photo-induced electron transfer with a bacterial reaction center - J. C. Williams; M. S. Faillace; E. J. Gonzalez; R. E. Dominguez; K. Knappenberger; D. A. Heredia; T. A. Moore; A. L. Moore; J. P. Allen (Photosynthesis Research, 2024)

Incidence of contrast-induced neurotoxicity following endovascular treatment of unruptured intracranial aneurysms: a single-centre cohort study - Frederick P. Mariajoseph; Leon T. Lai; Justin Moore; Ronil V. Chandra; Tony Goldschlager; Adrian Praeger; Daniel Yu; Lee-Anne Slater (Acta Neurologica Belgica, 2024)
Background Contrast-induced neurotoxicity (CIN) is a recognised complication of endovascular procedures and has been increasingly observed in recent years. Amongst other clinical gaps, the precise incidence of CIN is unclear, particularly following intracranial interventional procedures. Methods A retrospective study of consecutive patients undergoing elective endovascular treatment of unruptured intracranial aneurysms (UIAs) was performed. Patients with previously ruptured aneurysms were excluded. The primary aim of this study was to determine the incidence of CIN following endovascular UIA treatment. Our secondary aim was to isolate potential predictive factors for developing CIN. Results From 2017 to 2023, a total of 158 patients underwent endovascular UIA treatment, with a median age of 64 years (IQR: 54–72), and 70.3% of female sex. Over the study period, the crude incidence of CIN was 2.5% (95% CI: 0.7 – 6.4%). The most common clinical manifestation of CIN was confusion (75%) and seizures (50%). Statistical analysis was conducted, and prolonged procedural duration was found be significantly associated with developing CIN (OR 12.55; p = 0.030). Conclusion Clinicians should be aware of the risk of CIN following endovascular neurointervention, particularly following technically challenging cases resulting in prolonged procedural time.

Promoting best practices in ocean forecasting through an Operational Readiness Level - E. Alvarez Fanjul; S. Ciliberti; J. Pearlman; K. Wilmer-Becker; P. Bahurel; F. Ardhuin; A. Arnaud; K. Azizzadenesheli; R. Aznar; M. Bell; L. Bertino; S. Behera; et al. (Frontiers in Marine Science, 2024)
Predicting the ocean state in a reliable and interoperable way, while ensuring high-quality products, requires forecasting systems that synergistically combine science-based methodologies with advanced technologies for timely, user-oriented solutions. Achieving this objective necessitates the adoption of best practices when implementing ocean forecasting services, resulting in the proper design of system components and the capacity to evolve through different levels of complexity. The vision of OceanPrediction Decade Collaborative Center, endorsed by the UN Decade of Ocean Science for Sustainable Development 2021-2030, is to support this challenge by developing a “predicted ocean based on a shared and coordinated global effort” and by working within a collaborative framework that encompasses worldwide expertise in ocean science and technology. To measure the capacity of ocean forecasting systems, the OceanPrediction Decade Collaborative Center proposes a novel approach based on the definition of an Operational Readiness Level (ORL). This approach is designed to guide and promote the adoption of best practices by qualifying and quantifying the overall operational status. Considering three identified operational categories - production, validation, and data dissemination - the proposed ORL is computed through a cumulative scoring system. This method is determined by fulfilling specific criteria, starting from a given base level and progressively advancing to higher levels. The goal of ORL and the computed scores per operational category is to support ocean forecasters in using and producing ocean data, information, and knowledge. This is achieved through systems that attain progressively higher levels of readiness, accessibility, and interoperability by adopting best practices that will be linked to the future design of standards and tools. This paper discusses examples of the application of this methodology, concluding on the advantages of its adoption as a reference tool to encourage and endorse services in joining common frameworks.

Straight from the horse's mouth: The effect of different feedstuffs on oral pH in horses and ponies - S.P. Daniels; E.J. Whiteside; S. Martin; M.J.S. Moore-Colyer; P. Harris (Journal of Equine Veterinary Science, 2024)

Episodic ozone exposure in Long-Evans rats has limited effects on cauda sperm motility and non-coding RNA populations - Brian N. Chorley; Gary R. Klinefelter; Gail M. Nelson; Lillian F. Strader; Helen H. Nguyen; Mette C. Schladweiler; Grant Palmer; Makala L. Moore; Rachel D. Grindstaff; William T. Padgett; Gleta K. Carswell; Anna A. Fisher; et al. (Reproductive Toxicology, 2024)

Suitability of false codling moth eggs from different sterile to fertile moth ratios in the sterile insect technique programme, to parasitism by Trichogrammatoidea cryptophlebiae - Michael M. Githae; Candice A. Coombes; Reyard Mutamiswa; Sean D. Moore; Martin P. Hill (Crop Protection, 2024)

Beneficial ‘inefficiencies’ of western ranching: Flood-irrigated hay production sustains wetland systems by mimicking historic hydrologic processes - J. Patrick Donnelly; Kelsey Jensco; John S. Kimball; Johnnie N. Moore; David Ketchum; Daniel P. Collins; David E. Naugle (Agriculture, Ecosystems & Environment, 2024)

Clinical management of contrast-induced neurotoxicity: a systematic review - Frederick P. Mariajoseph; Jia Xi Chung; Leon T. Lai; Justin Moore; Tony Goldschlager; Ronil V. Chandra; Adrian Praeger; Lee-Anne Slater (Acta Neurologica Belgica, 2024)
Background Contrast-induced neurotoxicity (CIN) is an increasingly recognised complication following endovascular procedures utilising contrast. It remains poorly understood with heterogenous clinical management strategies. The aim of this review was to identify commonly employed treatments for CIN to enhance clinical decision making. Methods A systematic search of Embase (1947–2022) and Medline (1946–2022) was conducted. Articles describing (i) patients with a clinical diagnosis of CIN, (ii) with radiological exclusion of other pathologies, (iii) detailed report of treatments, and (iv) discharge outcomes, were included. Data relating to demographics, procedure, symptoms, treatment and outcomes were extracted. Results A total of 73 patients were included, with a median age of 64 years. The most common procedures were cerebral angiography (42.5%) and coronary angiography (42.5%), and the median volume of contrast administered was 150 ml. The most common symptoms were cortical blindness (38.4%) and reduced consciousness (28.8%), and 84.9% of patients experienced complete resolution at the time of discharge. Management included intravenous fluids to dilute contrast in the cerebrovasculature (54.8%), corticosteroids to reduce blood–brain barrier damage (47.9%), antiseizure (16.4%) and sedative (16.4%) medications. Mannitol (13.7%) was also utilised to reduce cerebral oedema. Intensive care admission was required for 19.2% of patients. No statistically significant differences were observed between treatment and discharge outcomes. Conclusions The clinical management of CIN should be considered on a patient-by-patient basis, but may consist of aggressive fluid therapy alongside corticosteroids, as well as other supportive therapy as required. Further examination of CIN management is required to define best practice.

Evidence of heat sensitivity in people with Parkinson’s disease - Andrew P. Hunt; Aline Souza Pagnussat; Alexander Lehn; Daniel Moore; Daniel Schweitzer; E-Liisa Laakso; Ewald Hennig; Meg E. Morris; Graham Kerr; Ian Stewart (International Journal of Biometeorology, 2024)
Examining how heat affects people with Parkinson’s disease is essential for informing clinical decision-making, safety, well-being, and healthcare planning. While there is evidence that the neuropathology associated with Parkinson’s disease affects thermoregulatory mechanisms, little attention has been given to the association of heat sensitivity to worsening symptoms and restricted daily activities in people with this progressive disease. Using a cross-sectional study design, we examined the experiences of people diagnosed with Parkinson’s disease in the heat. Two-hundred and forty-seven people completed an online survey (age: 66.0 ± 9.2 years; sex: male = 102 (41.3%), female = 145 (58.7%)), of which 195 (78.9%) reported becoming more sensitive to heat with Parkinson’s disease. Motor and nonmotor symptoms worsened with heat in 182 (73.7%) and 203 (82.2%) respondents, respectively. The most commonly reported symptoms to worsen included walking difficulties, balance impairment, stiffness, tremor, fatigue, sleep disturbances, excess sweating, difficulty concentrating, and light-headedness when standing. Concerningly, over half indicated an inability to work effectively in the heat, and nearly half reported that heat impacted their ability to perform household tasks and social activities. Overall, heat sensitivity was common in people with Parkinson’s disease and had a significant impact on symptomology, day-to-day activities and quality of life.

The murine metastatic microenvironment of experimental brain metastases of breast cancer differs by host age in vivo: a proteomic study - Allison L. Hunt; Imran Khan; Alex M. L. Wu; Sasha C. Makohon-Moore; Brian L. Hood; Kelly A. Conrads; Tamara Abulez; Jonathan Ogata; Dave Mitchell; Glenn Gist; Julie Oliver; Debbie Wei; et al. (Clinical & Experimental Metastasis, 2024)

Human‐modified habitats imperil ornamented dragonflies less than their non‐ornamented counterparts at local, regional, and continental scales - Michael P. Moore; Noah T. Leith; Kasey D. Fowler‐Finn; Kim A. Medley (Ecology Letters, 2024)
Biologists have long wondered how sexual ornamentation influences a species' risk of extinction. Because the evolution of condition‐dependent ornamentation can reduce intersexual conflict and accelerate the fixation of advantageous alleles, some theory predicts that ornamented taxa can be buffered against extinction in novel and/or stressful environments. Nevertheless, evidence from the wild remains limited. Here, we show that ornamented dragonflies are less vulnerable to extinction across multiple spatial scales. Population‐occupancy models across the Western United States reveal that ornamented species have become more common relative to non‐ornamented species over >100 years. Phylogenetic analyses indicate that ornamented species exhibit lower continent‐wide extinction risk than non‐ornamented species. Finally, spatial analyses of local dragonfly assemblages suggest that ornamented species possess advantages over non‐ornamented taxa at living in habitats that have been converted to farms and cities. Together, these findings suggest that ornamented taxa are buffered against contemporary extinction at local, regional, and continental scales.

CamTrapAsia : A dataset of tropical forest vertebrate communities from 239 camera trapping studies - Calebe P. Mendes; Wido R. Albert; Zachary Amir; Marc Ancrenaz; Eric Ash; Badrul Azhar; Henry Bernard; Jedediah Brodie; Tom Bruce; Elliot Carr; Gopalasamy Reuben Clements; Glyn Davies; et al. (Ecology, 2024)
Information on tropical Asian vertebrates has traditionally been sparse, particularly when it comes to cryptic species inhabiting the dense forests of the region. Vertebrate populations are declining globally due to land‐use change and hunting, the latter frequently referred as “defaunation.” This is especially true in tropical Asia where there is extensive land‐use change and high human densities. Robust monitoring requires that large volumes of vertebrate population data be made available for use by the scientific and applied communities. Camera traps have emerged as an effective, non‐invasive, widespread, and common approach to surveying vertebrates in their natural habitats. However, camera‐derived datasets remain scattered across a wide array of sources, including published scientific literature, gray literature, and unpublished works, making it challenging for researchers to harness the full potential of cameras for ecology, conservation, and management. In response, we collated and standardized observations from 239 camera trap studies conducted in tropical Asia. There were 278,260 independent records of 371 distinct species, comprising 232 mammals, 132 birds, and seven reptiles. The total trapping effort accumulated in this data paper consisted of 876,606 trap nights, distributed among Indonesia, Singapore, Malaysia, Bhutan, Thailand, Myanmar, Cambodia, Laos, Vietnam, Nepal, and far eastern India. The relatively standardized deployment methods in the region provide a consistent, reliable, and rich count data set relative to other large‐scale pressence‐only data sets, such as the Global Biodiversity Information Facility (GBIF) or citizen science repositories (e.g., iNaturalist), and is thus most similar to eBird. To facilitate the use of these data, we also provide mammalian species trait information and 13 environmental covariates calculated at three spatial scales around the camera survey centroids (within 10‐, 20‐, and 30‐km buffers). We will update the dataset to include broader coverage of temperate Asia and add newer surveys and covariates as they become available. This dataset unlocks immense opportunities for single‐species ecological or conservation studies as well as applied ecology, community ecology, and macroecology investigations. The data are fully available to the public for utilization and research. Please cite this data paper when utilizing the data.

Field-scale efficacy of entomopathogenic nematodes to control false codling moth, Thaumatotibia leucotreta (Lepidoptera: Tortricidae), in citrus orchards in South Africa - Sean D. Moore; Ralf-Udo Ehlers; Aruna Manrakhan; Martin Gilbert; Wayne Kirkman; John-Henry Daneel; Jeanne Y. De Waal; Rynhardt Nel; Guy Sutton; Antoinette P. Malan (Crop Protection, 2024)

The COSPAR planetary protection policy for missions to Icy Worlds: A review of history, current scientific knowledge, and future directions - P.T. Doran; A. Hayes; O. Grasset; A. Coustenis; O. Prieto-Ballesteros; N. Hedman; O. Al Shehhi; E. Ammannito; M. Fujimoto; F. Groen; J.E. Moores; C. Mustin; et al. (Life Sciences in Space Research, 2024)

The JPL-GIM algorithm and products: multi-GNSS high-rate global mapping of total electron content - Léo Martire; Thomas F. Runge; Xing Meng; Siddharth Krishnamoorthy; Panagiotis Vergados; Anthony J. Mannucci; Olga P. Verkhoglyadova; Attila Komjáthy; Angelyn W. Moore; Robert F. Meyer; Byron A. Ijima; Donald W. Green (Journal of Geodesy, 2024)

Infection with different Neospora caninum strains causes differences in the glycosylation pattern in the uteri and placentae of Neospora caninum-infected heifers - Sergio G. Caspe; Jose L. Konrad; Dadin P. Moore; Juan M. Sala; Paola Della-Rosa; Luis M. Ortega-Mora; Diana R. Bacigalupe; Maria C. Venturini; Carlos M. Campero; Claudio G. Barbeito (Journal of Comparative Pathology, 2024)

Towards harmonized standards for freshwater biodiversity monitoring and biological assessment using benthic macroinvertebrates - John P. Simaika; James Stribling; Jennifer Lento; Andreas Bruder; Sandra Poikane; Marcelo S. Moretti; Nick Rivers-Moore; Kristian Meissner; Craig R. Macadam (Science of The Total Environment, 2024)

Wet and dry events influenced colonization of a mid-elevation Andean forest - R.A. Sales; C.N.H. McMichael; L.C. Peterson; A. Stanley; I. Bennett; T.E. Jones; A.S. Walker; M. Mulhearn; A. Nelson; C. Moore; M. O'Connor; W. Sinkler; et al. (Quaternary Science Reviews, 2024)

Arabinogalactan proteins and polysaccharides compete directly with condensed tannins for saliva proteins influencing astringency perception of Cabernet Sauvignon wines - Brock Kuhlman; Jose Luis Aleixandre-Tudo; John P. Moore; Wessel du Toit (Food Chemistry, 2024)

Short-Term Recovery of Pilot Living Shoreline Projects for Salt Marsh Habitat in New Hampshire - James Grant McKown; Gregg E. Moore; David M. Burdick; Thomas P. Ballestero; Natalie A. White (Estuaries and Coasts, 2024)

Global Patterns of Metal and Other Element Enrichment in Bog and Fen Peatlands - Chetwynd Osborne; Spencer Gilbert-Parkes; Graeme Spiers; Louis James Lamit; Erik A. Lilleskov; Nathan Basiliko; Shaun Watmough; Roxanne Andersen; Rebekka E. Artz; Brian W. Benscoter; Luca Bragazza; Suzanna L. Bräuer; et al. (Archives of Environmental Contamination and Toxicology, 2024)

Transitioning through the vapour-liquid equilibrium for low energy thermal stripping of ammonia from wastewater: Enabling transformation of NH3 into a zero-carbon fuel - B. Luqmani; A. Brookes; A. Moore; P. Vale; M. Pidou; E.J. McAdam (Water Research, 2024)

Habitat structure shapes temperate reef assemblages across regional environmental gradients - Tim Jackson-Bué; Ally J. Evans; Peter J. Lawrence; Paul R. Brooks; Sophie L. Ward; Stuart R. Jenkins; Pippa J. Moore; Tasman P. Crowe; Simon P. Neill; Andrew J. Davies (Science of The Total Environment, 2024)

The influence of environmental context on community composition in artificial rockpools associated with seawalls - Veronica Farrugia Drakard; Ally J. Evans; Tasman P. Crowe; Pippa J. Moore; Jennifer Coughlan; Paul R. Brooks (Marine Environmental Research, 2024)

Transplacental infection by bovine alphaherpesvirus type 1 induces protein expression of COX-2, iNOS and inflammatory cytokines in fetal lungs and placentas - Mercedes M. Burucúa; María A. Risalde; Felipe A. Cheuquepán; Silvina Quintana; Sandra E. Pérez; Germán J. Cantón; Dadin P. Moore; Anselmo C. Odeón; Irene Agulló-Ros; María Valeria Scioli; Claudio Barbeito; Eleonora L. Morrell; et al. (Veterinary Microbiology, 2023)

Species identity and tree size drive residual tree mortality in island remnants in burned and harvested boreal forests - Rosanise A. Odell; Richard Osei; Marcel Schneider; Lance P. Moore; Tanvir Ahmed Shovon; Charles A. Nock (Forest Ecology and Management, 2023)

Pectolytic enzyme treatment partially degrades an arabinogalactan protein–rhamnogalacturonan I–xyloglucan co-polymer in red wine as characterised using epitope mass profiling - Brock Kuhlman; Jose Luis Aleixandre-Tudo; Wessel du Toit; John P. Moore (Food Hydrocolloids, 2023)

A Review of Grass Carp and Related Species Literature on Diet, Behavior, Toxicology, and Physiology Focused on Informing Development of Controls for Invasive Grass Carp Populations in North America - Mark L. Wildhaber; Benjamin M. West; Karlie K. Ditter; Adrian P. Moore; Alex S. Peterson (Fishes, 2023)
Grass carp (Ctenopharyngodon idella) are globally important in aquaculture and aquatic vegetation control. However, escaped grass carp have established invasive populations. A targeted keyword search was performed on a carp (order: Cypriniformes) literature database maintained by the U.S. Geological Survey to identify literature relevant to grass carp. Additional sources cited in reviewed documents and provided by numerous reviewers were also included. There were three focus areas designed to provide support for invasive grass carp management: (1) diet and behavior; (2) physiological constraints, toxicity, and biology; and (3) gut physiology. Each focus area provides information to guide development of potential pathways for invasive grass carp control. Information from other carp species was used to fill in gaps where grass carp information was lacking and provide additional, potential research directions. Diet-related information included food selection and aquacultural diet formulations. Behavioral information included stimuli and non-physical barriers to attract, repel, or stop movement. Physiological constraints, toxicology, reproductive control, and biological control provide a research review for control options. Gut physiology and related control pathways provide knowledge to improve toxin or pathogen delivery. This review provides a basis for developing approaches and research for controlling invasive grass carp populations, aquaculture, and native population management.

Drought conditioning of rhizosphere microbiome influences maize water use traits - Kelsey R. Carter; Abigael C. Nachtsheim; L. Turin Dickman; Eric R. Moore; Sangeeta Negi; John P. Heneghan; Anthony J. Sabella; Christina R. Steadman; Michaeline B. N. Albright; Christine M. Anderson-Cook; Louise H. Comas; Rose J. Harris; et al. (Plant and Soil, 2023)
Background and Aims Beneficial plant–microbe interactions can improve plant performance under drought; however, we know less about how drought-induced shifts in microbial communities affect plant traits. Methods We cultivated Zea mays in fritted clay with soil microbiomes originating from contrasting environments (agriculture or forest) under two irrigation treatments (well-watered or water limited). Using this design, we investigated whether water conditioning was carried forward through the microbiome to affect a subsequent plant cohort that was subjected to either a well-watered or water limited treatment. Results Regardless of the microbiome-origin, plants inoculated with a microbiome from a water limited legacy had traits that allowed them to avoid stress but conserve water. They produced longer roots to explore soil, generated greater soil dissolved organic carbon, potentially stimulating the microbiome, and slower soil water content loss during drought. A well-watered legacy resulted in plants that delayed permanent stomatal closure and higher photosynthetic nitrogen use efficiency. In plants with a forest-originated microbiome, a well-watered legacy and water treatment also resulted in higher rates of photosynthesis and stomatal conductance. Conclusion These results demonstrate that soil microbiomes can be developed to influence plant drought performance, impacting crop resilience, using short-term microbial conditioning.

Characterization of lesions of nutritional congenital goitre in cattle - Luis A. Colque-Caro; Francisco Acuña; Laura S. Aguirre; Agustín Avellaneda-Cáceres; Claudio G. Barbeito; Marcelo Signorini; Dadin P. Moore; Juan F. Micheloud (Journal of Comparative Pathology, 2023)

Using in-situ strain measurements to evaluate the accuracy of stress estimation procedures from fracture injection/shut-in tests - Yves Guglielmi; Mark McClure; Jeffrey Burghardt; Joseph P. Morris; Thomas Doe; Pengcheng Fu; Hunter Knox; Vince Vermeul; Tim Kneafsey; J. Ajo-Franklin; T. Baumgartner; K. Beckers; et al. (International Journal of Rock Mechanics and Mining Sciences, 2023)

A review of the role of metabolites in vegetative desiccation tolerance of angiosperms - Halford JW. Dace; Ademola E. Adetunji; John P. Moore; Jill M. Farrant; Henk WM. Hilhorst (Current Opinion in Plant Biology, 2023)

Mercury in Neotropical birds: a synthesis and prospectus on 13 years of exposure data - Christopher J. Sayers; David C. Evers; Viviana Ruiz-Gutierrez; Evan Adams; Claudia M. Vega; Jessica N. Pisconte; Vania Tejeda; Kevin Regan; Oksana P. Lane; Abidas A. Ash; Reynold Cal; Stevan Reneau; et al. (Ecotoxicology, 2023)
Environmental mercury (Hg) contamination of the global tropics outpaces our understanding of its consequences for biodiversity. Knowledge gaps of pollution exposure could obscure conservation threats in the Neotropics: a region that supports over half of the world’s species, but faces ongoing land-use change and Hg emission via artisanal and small-scale gold mining (ASGM). Due to their global distribution and sensitivity to pollution, birds provide a valuable opportunity as bioindicators to assess how accelerating Hg emissions impact an ecosystem’s ability to support biodiversity, and ultimately, global health. We present the largest database on Neotropical bird Hg concentrations ( n = 2316) and establish exposure baselines for 322 bird species spanning nine countries across Central America, South America, and the West Indies. Patterns of avian Hg exposure in the Neotropics broadly align with those in temperate regions: consistent bioaccumulation across functional groups and high spatiotemporal variation. Bird species occupying higher trophic positions and aquatic habitats exhibited elevated Hg concentrations that have been previously associated with reductions in reproductive success. Notably, bird Hg concentrations were over four times higher at sites impacted by ASGM activities and differed by season for certain trophic niches. We developed this synthesis via a collaborative research network, the Tropical Research for Avian Conservation and Ecotoxicology (TRACE) Initiative, which exemplifies inclusive, equitable, and international data-sharing. While our findings signal an urgent need to assess sampling biases, mechanisms, and consequences of Hg exposure to tropical avian communities, the TRACE Initiative provides a meaningful framework to achieve such goals. Ultimately, our collective efforts support and inform local, scientific, and government entities, including Parties of the United Nations Minamata Convention on Mercury, as we continue working together to understand how Hg pollution impacts biodiversity conservation, ecosystem function, and public health in the tropics.

Improving data collection in pregnancy safety studies: Towards standardization of data elements in pregnancy reports from public and private partners (ConcePTION) - Guillaume Favre; Jonathan L. Richardson; Alan Moore; Yvonne Geissbühler; Valentine Jehl; Alison Oliver; Svetlana Shechtman; Orna Diav-Citrin; Maya Berlin; Tal De-Haan; Anil Mor; Meritxell Sabidó; et al. (Neurotoxicology and Teratology, 2023)

Population structure and reproductive states of the dogwhelk Nucella lapillus differ between artificial structures and natural rocky shores - Bryan Thompson; Paul R. Brooks; Veronica Farrugia Drakard; Fiona Kubin; Hannah S. Earp; Ignacio Alvarez-Cienfuegos; Pippa J. Moore; Tasman P. Crowe (Marine Environmental Research, 2023)

Rapid prototyping for quantifying belief weights of competing hypotheses about emergent diseases - Ellen P. Robertson; Daniel P. Walsh; Julien Martin; Thierry M. Work; Christina A. Kellogg; James S. Evans; Victoria Barker; Aine Hawthorn; Greta Aeby; Valerie J. Paul; Brian K. Walker; Yasunari Kiryu; et al. (Journal of Environmental Management, 2023)

Mid-sized felids threatened by habitat degradation in Southeast Asia - Henri Decœur; Zachary Amir; Calebe P. Mendes; Jonathan H. Moore; Matthew Scott Luskin (Biological Conservation, 2023)

The visual fields of the Harpy Eagle (Harpia harpyja) - Anna E. Brewer; Wanderlei de Moraes; Thiago Alegre Coelho Ferreira; Andre Tovares Somma; Zalmir Silvino Cubas; Rogerio R. Lange; Luke P. Tyrrell; Tara M. Czepiel; Esteban Fernández-Juricic; Fabiano Montiani-Ferreira; Bret A. Moore (Journal of Ornithology, 2023)

Artificial rockpools: Seaweed colonisation and productivity vary between sites but are consistent across environmental contexts - Veronica Farrugia Drakard; Ally J. Evans; Tasman P. Crowe; Pippa J. Moore; Jennifer Coughlan; Paul R. Brooks (Marine Environmental Research, 2023)

Drivers of the microbial metabolic quotient across global grasslands - A. C. Risch; S. Zimmermann; M. Schütz; E. T. Borer; A. A. D. Broadbent; M. C. Caldeira; K. F. Davies; N. Eisenhauer; A. Eskelinen; P. A. Fay; F. Hagedorn; J. M. H. Knops; et al. (Global Ecology and Biogeography, 2023)
Aim The microbial metabolic quotient (MMQ; mg CO 2 ‐C/mg MBC/h), defined as the amount of microbial CO 2 respired (MR; mg CO 2 ‐C/kg soil/h) per unit of microbial biomass C (MBC; mg C/kg soil), is a key parameter for understanding the microbial regulation of the carbon (C) cycle, including soil C sequestration. Here, we experimentally tested hypotheses about the individual and interactive effects of multiple nutrient addition (nitrogen + phosphorus + potassium + micronutrients) and herbivore exclusion on MR, MBC and MMQ across 23 sites (five continents). Our sites encompassed a wide range of edaphoclimatic conditions; thus, we assessed which edaphoclimatic variables affected MMQ the most and how they interacted with our treatments. Location Australia, Asia, Europe, North/South America. Time period 2015–2016. Major taxa Soil microbes. Methods Soils were collected from plots with established experimental treatments. MR was assessed in a 5‐week laboratory incubation without glucose addition, MBC via substrate‐induced respiration. MMQ was calculated as MR/MBC and corrected for soil temperatures (MMQsoil). Using linear mixed effects models (LMMs) and structural equation models (SEMs), we analysed how edaphoclimatic characteristics and treatments interactively affected MMQsoil. Results MMQsoil was higher in locations with higher mean annual temperature, lower water holding capacity and lower soil organic C concentration, but did not respond to our treatments across sites as neither MR nor MBC changed. We attributed this relative homeostasis to our treatments to the modulating influence of edaphoclimatic variables. For example, herbivore exclusion, regardless of fertilization, led to greater MMQsoil only at sites with lower soil organic C ( Main conclusions Our results pinpoint the main variables related to MMQsoil across grasslands and emphasize the importance of the local edaphoclimatic conditions in controlling the response of the C cycle to anthropogenic stressors. By testing hypotheses about MMQsoil across global edaphoclimatic gradients, this work also helps to align the conflicting results of prior studies.

Stationary and drone-assisted methane plume localization with dispersion spectroscopy - Michael G. Soskind; Nathan P. Li; Daniel P. Moore; Yifeng Chen; Lars P. Wendt; James McSpiritt; Mark A. Zondlo; Gerard Wysocki (Remote Sensing of Environment, 2023)

Photosensitiser-incorporated microparticles for photodynamic inactivation of bacteria - Jessica V. Moore; Matthew P. Wylie; Gavin P. Andrews; Colin P. McCoy (Journal of Photochemistry and Photobiology B: Biology, 2023)

The impact of polyphenolic compounds on the in vitro growth of oak-associated foliar endophytic and saprotrophic fungi - Megan N. Nickerson; Lillian P. Moore; Jana M. U'Ren (Fungal Ecology, 2023)

Seawater from Bergen harbor is a reservoir of conjugative multidrug-resistance plasmids carrying genes for virulence - Nachiket P. Marathe; Didrik H. Grevskott; Francisco Salvà-Serra; Priyank S. Nimje; Cecilie S. Svanevik; Bjørn Tore Lunestad; Edward R.B. Moore (International Journal of Hygiene and Environmental Health, 2023)

The population structure, sex ratio and reproductive potential of limpets (Patella spp.) on natural shores and artificial structures in the Irish Sea - Hannah S. Earp; Ruby George; Paul R. Brooks; Veronica Farrugia Drakard; Bryan J. Thompson; Benjamin Fisher; Róisín Hayden; Tasman P. Crowe; Pippa J. Moore (Marine Environmental Research, 2023)

A multicentre evaluation and expert recommendations of use of the newly developed BioFire Joint Infection polymerase chain reaction panel - Kordo Saeed; Nusreen Ahmad-Saeed; Rachel Annett; Gavin Barlow; Lucinda Barrett; Sara E. Boyd; Nicola Boran; Peter Davies; Harriet Hughes; Gwennan Jones; Laura Leach; Maureen Lynch; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)
Septic arthritis is a serious condition with significant morbidity and mortality, routinely diagnosed using culture. The FDA has recently approved the rapid molecular BioFire® Joint Infection Panel (BJIP) for synovial fluid. We aimed to evaluate the BJIP compared to culture and its potential use in patient management. A multicentre retrospective evaluation of BJIP was conducted in the UK and Ireland. Positive percent agreement (PPA) and negative percent agreement (NPA) were calculated between the BJIP and routine culture. A multidisciplinary team (MDT) discussion addressing the optimal or potential case use of the assay practice was facilitated. Three hundred ninety-nine surplus synovial fluid samples (~ 70% from native joints) from eight centres were processed using BJIP in addition to routine culture. An increased yield of positive results was detected using BJIP compared to routine culture (98 vs 83), giving an overall PPA of 91.6% and overall NPA of 93% for the BJIP compared to culture results. The BJIP detected resistant markers and additional organisms that could influence antibiotic choices including Neisseria gonorrhoeae and Kingella kingae . The MDT agreed that the assay could be used, in addition to standard methods, in adult and children patients with specialist advice use based on local needs. Rapid results from BJIP were assessed as having potential clinical impact on patient management. Organisms not included in the panel may be clinically significant and may limit the value of this test for PJI.

Mismatch between conservation status and climate change sensitivity leaves some anurans in the United States unprotected - Traci P. DuBose; Chloe E. Moore; Sam Silknetter; Abigail L. Benson; Tess Alexander; Grace O'Malley; Meryl C. Mims (Biological Conservation, 2023)

Passive Treatment of Circumneutral Mine Drainage from the St. Louis Mine Tunnel, Rico, CO: Part 1—Case Study: Characteristics of the Mine Drainage - Terry J. Moore; Arthur C. Riese; Anne Lewis-Russ; James P. Jonas; Brian S. Johnson (Mine Water and the Environment, 2022)
This publication is a case study of the seasonal variability of mine water drainage from the Saint Louis Tunnel (SLT) at the inactive Rico-Argentine mine site located in southwestern Colorado. It is an introductory paper for the two passive water treatment system technology evaluations contained in this issue. Mine water chemistry changes from baseflow to a snowmelt runoff event (SMRE) where snowmelt runoff follows preferential migration pathways to flush acidic weathering products from the upper mine workings to the SLT. Baseflow mine drainage is characterized as circumneutral, with Zn, Cd, Mn, and Ni concentrations primarily in the dissolved form. Dissolved Zn, Mn, Fe, and potentially Cd illustrate equilibrium with carbonate minerals. Total concentrations of Fe, Cu, Pb, and As are primarily in the suspended form and suggest sorption to Fe oxides. Mine water chemistry during the SMRE reflects mixing of circumneutral baseflow waters with more acidic waters flushing the upper mine workings. Geothermal activity provides for a consistently warm mine water discharge from the SLT. The two seasons that provide the most challenge to passive water treatment of SLT mine drainage are the SMRE period and the low flow stage of the Dolores River. Mine water flow and chemistry during SMRE are highly correlated with Dolores River flow and this site conceptual model was and will be used to assist in pilot project evaluation, water treatment system design, monitoring system design, a seasonal compliance approach, and water management.

Linking changes in species composition and biomass in a globally distributed grassland experiment - Emma Ladouceur; Shane A. Blowes; Jonathan M. Chase; Adam T. Clark; Magda Garbowski; Juan Alberti; Carlos Alberto Arnillas; Jonathan D. Bakker; Isabel C. Barrio; Siddharth Bharath; Elizabeth T. Borer; Lars A. Brudvig; et al. (Ecology Letters, 2022)
Global change drivers, such as anthropogenic nutrient inputs, are increasing globally. Nutrient deposition simultaneously alters plant biodiversity, species composition and ecosystem processes like aboveground biomass production. These changes are underpinned by species extinction, colonisation and shifting relative abundance. Here, we use the Price equation to quantify and link the contributions of species that are lost, gained or that persist to change in aboveground biomass in 59 experimental grassland sites. Under ambient (control) conditions, compositional and biomass turnover was high, and losses (i.e. local extinctions) were balanced by gains (i.e. colonisation). Under fertilisation, the decline in species richness resulted from increased species loss and decreases in species gained. Biomass increase under fertilisation resulted mostly from species that persist and to a lesser extent from species gained. Drivers of ecological change can interact relatively independently with diversity, composition and ecosystem processes and functions such as aboveground biomass due to the individual contributions of species lost, gained or persisting.

Amplifying actions for food system transformation: insights from the Stockholm region - David P. M. Lam; Amanda Jiménez-Aceituno; Leonie Guerrero Lara; My M. Sellberg; Albert V. Norström; Michele-Lee Moore; Garry D. Peterson; Per Olsson (Sustainability Science, 2022)
Food is essential to people and is one of the main ways in which people are connected to the world’s ecosystems. However, food systems often cause ecosystem degradation and produce ill-health, which has generated increasing calls to transform food systems to be more sustainable. The Swedish food system is currently undergoing substantial change. A varied set of local actors have created alternative sustainability initiatives that enact new ways of doing, thinking, and organizing. These actors can increase the transformative impact of their initiatives through multiple actions and a variety of amplification processes. We analyzed the actions adopted by 29 food initiatives active in the Stockholm region using information available online. We conducted 11 interviews to better understand the amplification processes of speeding up (i.e., accelerating impact) , scaling up (i.e., influencing higher institutional levels), and scaling deep (i.e., changing values and mind-sets). Our results indicated that the initiatives mainly seek to stabilize and grow their impact while changing the awareness, values, and mind-sets of people concerning the food they consume ( scaling deep ). However, these approaches raise new questions about whether these actions subvert or reinforce current unsustainable and inequitable system dynamics. We suggest there are distinct steps that local and regional governments could take to support these local actors via collaborations with coordinated forms of initiatives, and fostering changes at the municipality level, but these steps require ongoing, adaptive approaches given the highly complex nature of transformative change and the risks of reinforcing current system dynamics.

The policy and ecology of forest-based climate mitigation: challenges, needs, and opportunities - Courtney L. Giebink; Grant M. Domke; Rosie A. Fisher; Kelly A. Heilman; David J. P. Moore; R. Justin DeRose; Margaret E. K. Evans (Plant and Soil, 2022)

Ensemble of models shows coherent response of a reservoir’s stratification and ice cover to climate warming - Johannes Feldbauer; Robert Ladwig; Jorrit P. Mesman; Tadhg N. Moore; Hilke Zündorf; Thomas U. Berendonk; Thomas Petzoldt (Aquatic Sciences, 2022)
Water temperature, ice cover, and lake stratification are important physical properties of lakes and reservoirs that control mixing as well as bio-geo-chemical processes and thus influence the water quality. We used an ensemble of vertical one-dimensional hydrodynamic lake models driven with regional climate projections to calculate water temperature, stratification, and ice cover under the A1B emission scenario for the German drinking water reservoir Lichtenberg. We used an analysis of variance method to estimate the contributions of the considered sources of uncertainty on the ensemble output. For all simulated variables, epistemic uncertainty, which is related to the model structure, is the dominant source throughout the simulation period. Nonetheless, the calculated trends are coherent among the five models and in line with historical observations. The ensemble predicts an increase in surface water temperature of 0.34 K per decade, a lengthening of the summer stratification of 3.2 days per decade, as well as decreased probabilities of the occurrence of ice cover and winter inverse stratification by 2100. These expected changes are likely to influence the water quality of the reservoir. Similar trends are to be expected in other reservoirs and lakes in comparable regions.

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

eDNA metabarcoding of decapod crustaceans across Indonesian seas has implications for biodiversity conservation and fisheries sustainability - Hawis Madduppa; Lalu M. Iqbal Sani; Kuncoro Catur Nugroho; Dietriech G. Bengen; Zainal Abidin Muchlisin; Nur Fadli; Beginer Subhan; Dondy Arafat; Neviaty P. Zamani; Adriani Sunuddin; Meutia Samira Ismet; Endang S. Srimariana; et al. (Frontiers in Marine Science, 2022)
Environmental DNA (eDNA) methods are increasingly viewed as alternate or complementary approaches to conventional capture-based surveys for marine conservation and fisheries management purposes, especially at large spatial scales in mega-biodiversity regions such as Indonesia. Decapod crustacean distribution and diversity across Indonesia are still poorly known, even for economically important fisheries commodities. This study assessed coral reef associated decapod diversity and distribution by sampling 40 sites in three regions (West, Central, East), representing 17 provinces and 10 Fisheries Management Areas (FMAs) across Indonesia, with a special focus on the blue swimming crab Portunus pelagicus . DNA sequencing (Illumina iSeq100) data were analysed in mBRAVE (Multiplex Barcode Research And Visualization Environment) yielded 406 OTUs belonging to 32 families, with 47 genera and 51 species identified. The number of families identified was highest in the Central region (25), while the most genera (31) and species (36) were identified in the West region. Alpha diversity did not differ significantly between regions or provinces, while Beta diversity differed significantly between provinces but not between regions. Our results also showed 31 species are possibility native based on the distribution meanwhile 12 species do not appear to have been recorded based of SeaLifeBase or WorMS. While providing a reference for further exploration of Indonesian coastal and small island decapod biodiversity, the high proportion of unidentified taxa calls for concerted efforts to develop and maintain reference specimen and sequence repositories and expand species conservation status assessments. The economically important decapod crustaceans identified in this study included three crabs ( Charybdis anisodon, Charybdis japonica, Portunus pelagicus ), a freshwater prawn ( Macrobrachium nipponense ), a lobster ( Panulirus stimpsoni ) and two penaeid shrimps ( Mierspenaeopsis hardwickii and Trachysalambria aspera ). For most decapod taxa, observed patterns indicate management under existing provincial and/or FMA level management structures is appropriate. Furthermore, the data can inform science-based fisheries management strategies, in particular for P. pelagicus .

Acute tryptophan depletion alters affective touch perception - Paula D. Trotter; Sharon A. Smith; David J. Moore; Noreen O’Sullivan; Martyn M. McFarquhar; Francis P. McGlone; Susannah C. Walker (Psychopharmacology, 2022)
Rationale Affiliative tactile interactions help regulate physiological arousal and confer resilience to acute and chronic stress. C-tactile afferents (CTs) are a population of unmyelinated, low threshold mechanosensitive cutaneous nerve fibres which respond optimally to a low force stimulus, moving at between 1 and 10 cm/s. As CT firing frequencies correlate positively with subjective ratings of touch pleasantness, they are hypothesised to form the first stage of encoding affiliative tactile interactions. Serotonin is a key modulator of social responses with known effects on bonding. Objectives The aim of the present study was to determine the effect of acutely lowering central serotonin levels on perceptions of CT-targeted affective touch. Methods In a double blind, placebo-controlled design, the effect of acute tryptophan depletion (ATD) on 25 female participants’ ratings of directly and vicariously experienced touch was investigated. Psychophysical techniques were used to deliver dynamic tactile stimuli; some velocities were targeted to optimally activate CTs (1–10 cm/s), whereas other, faster and slower strokes fell outside the CT optimal range. Discriminative tactile function, cold pain threshold and tolerance were also measured. Results ATD significantly increased pleasantness ratings of both directly and vicariously experienced affective touch, increasing discrimination of the specific hedonic value of CT targeted velocities. While ATD had no effect on either tactile or cold pain thresholds, there was a trend for reduced tolerance to cold pain. Conclusions These findings are consistent with previous reports that depletion of central serotonin levels modulates neural and behavioural responsiveness to appetitive sensory signals.

Length of growing season is modulated by Northern Hemisphere jet stream variability - Amy R. Hudson; William K. Smith; David J. P. Moore; Valerie Trouet (International Journal of Climatology, 2022)
Atmospheric circulations create regions of similar climate at the land surface across the Northern Hemisphere's mid‐latitudes, while climate controls on plant phenology phases (phenophases) can vary. Here, we quantify and classify the seasonal impacts of the Northern Hemisphere jet stream (NHJ) on vegetation phenophases using novel NHJ indices, designed to characterize latitudinal jet stream position, and satellite‐based vegetation phenology products of length, start, and end of season (LOS, SOS, EOS). We composited years of northern and southern NHJ anomalies in April–May and October–November from LOS, SOS, and EOS and classified ecosystem response based on: latitudinal location relative to the climatological mean (CM) latitude of the NHJ; climate; and land cover type. For nearly a third of the NH, LOS was modulated by NHJ position. The magnitude and direction of NHJ influence on LOS was dependent on the season of NHJ position anomaly. In spring, a northern NHJ, which typically corresponded with warmer temperatures, led to earlier SOS and longer LOS, especially in cold systems north of the NHJ's CM. Surprisingly, in fall, a northern NHJ led to shorter LOS and earlier EOS for most systems, which may be due to the interaction of temperature and water availability in this season when water is critical for sustained growth. Southern NHJ corresponded with similar but opposite effects on phenophases. Crop land cover was mixed in LOS response to NHJ, reflecting the added impact of land‐use and management. The NHJ can synchronize phenology across apparently disparate regions of the Northern Hemisphere. Rather than simply lengthening or shortening seasons as the NHJ moves northward or southward, the influence of the NHJ on phenology at a given location depends on whether the NHJ is limiting resources—which vary relative to the climatological mean. We find that complex patterns in phenology emerge from a relatively simple contingency.

Evolutionary interactions between thermal ecology and sexual selection - Noah T. Leith; Kasey D. Fowler‐Finn; Michael P. Moore (Ecology Letters, 2022)
Thermal ecology and mate competition are both pervasive features of ecological adaptation. A surge of recent work has uncovered the diversity of ways in which temperature affects mating interactions and sexual selection. However, the potential for thermal biology and reproductive ecology to evolve together as organisms adapt to their thermal environment has been underappreciated. Here, we develop a series of hypotheses regarding (1) not only how thermal ecology affects mating system dynamics, but also how mating dynamics can generate selection on thermal traits; and (2) how the thermal consequences of mate competition favour the reciprocal co‐adaptation of thermal biology and sexual traits. We discuss our hypotheses in the context of both pre‐copulatory and post‐copulatory processes. We also call for future work integrating experimental and phylogenetic comparative approaches to understand evolutionary feedbacks between thermal ecology and sexual selection. Overall, studying reciprocal feedbacks between thermal ecology and sexual selection may be necessary to understand how organisms have adapted to the environments of the past and could persist in the environments of the future.

Spatial–temporal trends and economic losses associated with bovine abortifacients in central Argentina - Germán J. Cantón; Fabiana Moreno; María A. Fiorentino; Yanina P. Hecker; Maximiliano Spetter; Franco Fiorani; María G. Monterubbianesi; Juan A. García; Erika González Altamiranda; Karina M. Cirone; Enrique L. Louge Uriarte; Andrea E. Verna; et al. (Tropical Animal Health and Production, 2022)

Influence of Rising Water Temperature on the Temperate Seagrass Species Eelgrass (Zostera marina L.) in the Northeast USA - Holly K. Plaisted; Erin C. Shields; Alyssa B. Novak; Christopher P. Peck; Forest Schenck; Jillian Carr; Paul A. Duffy; N. Tay Evans; Sophia E. Fox; Stephen M. Heck; Robbie Hudson; Trevor Mattera; et al. (Frontiers in Marine Science, 2022)
Sea surface temperature (SST) has increased worldwide since the beginning of the 20th century, a trend which is expected to continue. Changes in SST can have significant impacts on marine biota, including population-level shifts and alterations in community structure and diversity, and changes in the timing of ecosystem events. Seagrasses are a group of foundation species that grow in shallow coastal and estuarine systems, where they provide many ecosystem services. Eelgrass, Zostera marina L., is the dominant seagrass species in the Northeast United States of America (USA). Multiple factors have been cited for losses in this region, including light reduction, eutrophication, and physical disturbance. Warming has the potential to exacerbate seagrass loss. Here, we investigate regional changes in eelgrass presence and abundance in relation to local water temperature using monitoring data from eight sites in the Northeastern USA (New Hampshire to Maryland) where a consistent monitoring protocol, SeagrassNet, has been applied. We use a hurdle model consisting of a generalized additive mixed model (GAMM) with binomial and beta response distributions for modeling eelgrass presence and abundance, respectively, in relation to the local summer average water temperature. We show that summer water temperature one year prior to monitoring is a significant predictor of eelgrass presence, but not abundance, on a regional scale. Above average summer temperatures correspond to a decrease in probability of eelgrass presence (and increased probability of eelgrass absence) the following year. Cooler than average temperatures in the preceding year, down to approximately 0.5°C below the site average, are associated with the highest predicted probability of eelgrass presence. Our findings suggest vulnerability in eelgrass meadows of the Northeast USA and emphasize the value of unified approaches to seagrass monitoring, conservation and management at the seascape scale.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Bridge to the future: Important lessons from 20 years of ecosystem observations made by the OzFlux network - Jason Beringer; Caitlin E. Moore; Jamie Cleverly; David I. Campbell; Helen Cleugh; Martin G. De Kauwe; Miko U. F. Kirschbaum; Anne Griebel; Sam Grover; Alfredo Huete; Lindsay B. Hutley; Johannes Laubach; et al. (Global Change Biology, 2022)
In 2020, the Australian and New Zealand flux research and monitoring network, OzFlux, celebrated its 20 th anniversary by reflecting on the lessons learned through two decades of ecosystem studies on global change biology. OzFlux is a network not only for ecosystem researchers, but also for those ‘next users’ of the knowledge, information and data that such networks provide. Here, we focus on eight lessons across topics of climate change and variability, disturbance and resilience, drought and heat stress and synergies with remote sensing and modelling. In distilling the key lessons learned, we also identify where further research is needed to fill knowledge gaps and improve the utility and relevance of the outputs from OzFlux. Extreme climate variability across Australia and New Zealand (droughts and flooding rains) provides a natural laboratory for a global understanding of ecosystems in this time of accelerating climate change. As evidence of worsening global fire risk emerges, the natural ability of these ecosystems to recover from disturbances, such as fire and cyclones, provides lessons on adaptation and resilience to disturbance. Drought and heatwaves are common occurrences across large parts of the region and can tip an ecosystem's carbon budget from a net CO 2 sink to a net CO 2 source. Despite such responses to stress, ecosystems at OzFlux sites show their resilience to climate variability by rapidly pivoting back to a strong carbon sink upon the return of favourable conditions. Located in under‐represented areas, OzFlux data have the potential for reducing uncertainties in global remote sensing products, and these data provide several opportunities to develop new theories and improve our ecosystem models. The accumulated impacts of these lessons over the last 20 years highlights the value of long‐term flux observations for natural and managed systems. A future vision for OzFlux includes ongoing and newly developed synergies with ecophysiologists, ecologists, geologists, remote sensors and modellers.

A field experiment characterizing variable detection rates during plant surveys - Cindy E. Hauser; Katherine M. Giljohann; Michael A. McCarthy; Georgia E. Garrard; Andrew P. Robinson; Nicholas S. G. Williams; Joslin L. Moore (Conservation Biology, 2022)
Surveys aimed at finding threatened and invasive species can be challenging due to individual rarity and low and variable individual detection rates. Detection rate in plant surveys typically varies due to differences among observers, among the individual plants being surveyed (targets), and across background environments. Interactions among these 3 components may occur but are rarely estimated due to limited replication and control during data collection. We conducted an experiment to investigate sources of variation in detection of 2 Pilosella species that are invasive and sparsely distributed in the Alpine National Park, Australia. These species are superficially similar in appearance to other yellow‐flowered plants occurring in this landscape. We controlled the presence and color of flowers on target Pilosella plants and controlled their placement in plots, which were selected for their variation in cover of non‐target yellow flowers and dominant vegetation type. Observers mimicked Pilosella surveys in the plots and reported 1 categorical and 4 quantitative indicators of their survey experience level. We applied survival analysis to detection data to model the influence of both controlled and uncontrolled variables on detection rate. Orange‐ and yellow‐flowering Pilosella in grass‐ and heath‐dominated vegetation were detected at a higher rate than nonflowering Pilosella . However, this detection gain diminished as the cover of other co‐occurring yellow‐flowering species increased. Recent experience with Pilosella surveys improved detection rate. Detection experiments are a direct and accessible means of understanding detection processes and interpreting survey data for threatened and invasive species. Our detection findings have been used for survey planning and can inform progress toward eradication. Interaction of target and background characteristics determined detection rate, which enhanced predictions in the Pilosella eradication program and demonstrated the difficulty of transferring detection findings into untested environments.

A pathogenic deletion in Forkhead Box L1 (FOXL1) identifies the first otosclerosis (OTSC) gene - Nelly Abdelfatah; Ahmed A. Mostafa; Curtis R. French; Lance P. Doucette; Cindy Penney; Matthew B. Lucas; Anne Griffin; Valerie Booth; Christopher Rowley; Jessica E. Besaw; Lisbeth Tranebjærg; Nanna Dahl Rendtorff; et al. (Human Genetics, 2022)
Otosclerosis is a bone disorder of the otic capsule and common form of late-onset hearing impairment. Considered a complex disease, little is known about its pathogenesis. Over the past 20 years, ten autosomal dominant loci ( OTSC1-10 ) have been mapped but no genes identified. Herein, we map a new OTSC locus to a 9.96 Mb region within the FOX gene cluster on 16q24.1 and identify a 15 bp coding deletion in Forkhead Box L1 co-segregating with otosclerosis in a Caucasian family. Pre-operative phenotype ranges from moderate to severe hearing loss to profound sensorineural loss requiring a cochlear implant. Mutant FOXL1 is both transcribed and translated and correctly locates to the cell nucleus. However, the deletion of 5 residues in the C-terminus of mutant FOXL1 causes a complete loss of transcriptional activity due to loss of secondary (alpha helix) structure. FOXL1 (rs764026385) was identified in a second unrelated case on a shared background. We conclude that FOXL1 (rs764026385) is pathogenic and causes autosomal dominant otosclerosis and propose a key inhibitory role for wildtype Foxl1 in bone remodelling in the otic capsule. New insights into the molecular pathology of otosclerosis from this study provide molecular targets for non-invasive therapeutic interventions.

Nutrient identity modifies the destabilising effects of eutrophication in grasslands - Oliver Carroll; Evan Batzer; Siddharth Bharath; Elizabeth T. Borer; Sofía Campana; Ellen Esch; Yann Hautier; Timothy Ohlert; Eric W. Seabloom; Peter B. Adler; Jonathan D. Bakker; Lori Biederman; et al. (Ecology Letters, 2022)
Nutrient enrichment can simultaneously increase and destabilise plant biomass production, with co‐limitation by multiple nutrients potentially intensifying these effects. Here, we test how factorial additions of nitrogen (N), phosphorus (P) and potassium with essential nutrients (K+) affect the stability (mean/standard deviation) of aboveground biomass in 34 grasslands over 7 years. Destabilisation with fertilisation was prevalent but was driven by single nutrients, not synergistic nutrient interactions. On average, N‐based treatments increased mean biomass production by 21–51% but increased its standard deviation by 40–68% and so consistently reduced stability. Adding P increased interannual variability and reduced stability without altering mean biomass, while K+ had no general effects. Declines in stability were largest in the most nutrient‐limited grasslands, or where nutrients reduced species richness or intensified species synchrony. We show that nutrients can differentially impact the stability of biomass production, with N and P in particular disproportionately increasing its interannual variability.

Aortic haemodynamics: the effects of habitual endurance exercise, age and muscle sympathetic vasomotor outflow in healthy men - Denis J. Wakeham; Tony G. Dawkins; Rachel N. Lord; Jack S. Talbot; Freya M. Lodge; Bryony A. Curry; Lydia L. Simpson; Christopher J. A. Pugh; Robert E. Shave; Jonathan P. Moore (European Journal of Applied Physiology, 2022)
Purpose We determined the effect of habitual endurance exercise and age on aortic pulse wave velocity (aPWV), augmentation pressure (AP) and systolic blood pressure (aSBP), with statistical adjustments of aPWV and AP for heart rate and aortic mean arterial pressure, when appropriate. Furthermore, we assessed whether muscle sympathetic nerve activity (MSNA) correlates with AP in young and middle-aged men. Methods Aortic PWV, AP, aortic blood pressure (applanation tonometry; SphygmoCor) and MSNA (peroneal microneurography) were recorded in 46 normotensive men who were either young or middle-aged and endurance-trained runners or recreationally active nonrunners (10 nonrunners and 13 runners within each age-group). Between-group differences and relationships between variables were assessed via ANOVA/ANCOVA and Pearson product-moment correlation coefficients, respectively. Results Adjusted aPWV and adjusted AP were similar between runners and nonrunners in both age groups (all, P > 0.05), but higher with age (all, P < 0.001), with a greater effect size for the age-related difference in AP in runners (Hedges’ g , 3.6 vs 2.6). aSBP was lower in young ( P = 0.009; g = 2.6), but not middle-aged ( P = 0.341; g = 1.1), runners compared to nonrunners. MSNA burst frequency did not correlate with AP in either age group (young: r = 0.00, P = 0.994; middle-aged: r = − 0.11, P = 0.604). Conclusion There is an age-dependent effect of habitual exercise on aortic haemodynamics, with lower aSBP in young runners compared to nonrunners only. Statistical adjustment of aPWV and AP markedly influenced the outcomes of this study, highlighting the importance of performing these analyses. Further, peripheral sympathetic vasomotor outflow and AP were not correlated in young or middle-aged normotensive men.

Photoelectrochemistry of metalloporphyrin-modified GaP semiconductors - Daiki Nishiori; Brian L. Wadsworth; Edgar A. Reyes Cruz; Nghi P. Nguyen; Lillian K. Hensleigh; Timothy Karcher; Gary F. Moore (Photosynthesis Research, 2022)

Structure and diversity of blackfly assemblages in the Luvuvhu River system, South Africa in response to changing environmental gradients - P. A. Ramulifho; S. H. Foord; N. A. Rivers-Moore (Hydrobiologia, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

A framework for incorporating ecology into Earth System Models is urgently needed - David J. P. Moore (Global Change Biology, 2022)

Preface: honoring the career of Russell K. Monson - Amy M. Trowbridge; David J. P. Moore; Paul C. Stoy (Oecologia, 2021)

Quantitative analysis of Cenozoic faults and fractures and their impact on groundwater flow in the bedrock aquifers of Ireland - J. P. Moore; J. J. Walsh (Hydrogeology Journal, 2021)
Faults and fractures are a critical store and pathway for groundwater in Ireland’s limestone bedrock aquifers either directly as conductive structures or indirectly as the locus for the development of karst conduits. From the quantitative analysis of post-Devonian faults and fractures in a range of lithological sequences, this report describes the principal characteristics of Cenozoic strike-slip faults and joints, the youngest and the most intrinsically conductive fractures within Irish bedrock. Analysis of these structures in more than 120 outcrop, quarry, mine and cave locations in a range of bedrock types, provides a basis for: (1) definition of quantitative models for their depth dependency, lithological control, scaling systematics and links to preexisting structure, (2) conceptualisation of their impact on groundwater behaviour, and (3) estimation of groundwater flow parameters. The quantitative models provide constraints on fracture-controlled flow connectivity. Commonly observed decreases in sustainable flows and water strike interceptions with depth are attributed to increasing confinement and decreasing fracture connectivity and dissolution. Faults and joints have quite different end member geometries, with faults having strongly heterogeneous scale-independent properties and joints more often showing scale-dependent stratabound properties. The highest and most sustainable groundwater flows are usually associated with the complexity of structure of Cenozoic faults and of preexisting Carboniferous structures (on which conductive fracturing localises), enhanced by karstification and strongly jointed limestone bedrock particularly in the near-surface. Increased groundwater flow is promoted within bedded, rather than massive (i.e. unbedded), limestone sequences, characterised by bedding-parallel fractures and karst connecting otherwise subvertical fractures and subvertical wells.

Root cap–derived cells and mucilage: a protective network at the root tip - Azeddine Driouich; Alexia Gaudry; Barbara Pawlak; John P. Moore (Protoplasma, 2021)

Temporal rarity is a better predictor of local extinction risk than spatial rarity - Peter A. Wilfahrt; Ashley L. Asmus; Eric W. Seabloom; Jeremiah A. Henning; Peter Adler; Carlos A. Arnillas; Jonathan D. Bakker; Lori Biederman; Lars A. Brudvig; Marc Cadotte; Pedro Daleo; Anu Eskelinen; et al. (Ecology, 2021)
Spatial rarity is often used to predict extinction risk, but rarity can also occur temporally. Perhaps more relevant in the context of global change is whether a species is core to a community (persistent) or transient (intermittently present), with transient species often susceptible to human activities that reduce niche space. Using 5–12 yr of data on 1,447 plant species from 49 grasslands on five continents, we show that local abundance and species persistence under ambient conditions are both effective predictors of local extinction risk following experimental exclusion of grazers or addition of nutrients; persistence was a more powerful predictor than local abundance. While perturbations increased the risk of exclusion for low persistence and abundance species, transient but abundant species were also highly likely to be excluded from a perturbed plot relative to ambient conditions. Moreover, low persistence and low abundance species that were not excluded from perturbed plots tended to have a modest increase in abundance following perturbance. Last, even core species with high abundances had large decreases in persistence and increased losses in perturbed plots, threatening the long‐term stability of these grasslands. Our results demonstrate that expanding the concept of rarity to include temporal dynamics, in addition to local abundance, more effectively predicts extinction risk in response to environmental change than either rarity axis predicts alone.

Population structure associated with bioregion and seasonal prey distribution for Indo‐Pacific bottlenose dolphins ( Tursiops aduncus ) in South Africa - O. Alejandra Vargas‐Fonseca; Paige Yates; Stephan P. Kirkman; Pierre A. Pistorius; Daniel M. Moore; Ada Natoli; Victor Cockcroft; A. Rus Hoelzel (Molecular Ecology, 2021)
Many marine species exhibit fine‐scale population structure despite high mobility and a lack of physical barriers to dispersal, but the evolutionary drivers of differentiation in these systems are generally poorly understood. Here we investigate the potential role of habitat transitions and seasonal prey distributions on the evolution of population structure in the Indo‐Pacific bottlenose dolphin, Tursiops aduncus , off South Africa's coast, using double‐digest restriction‐site associated DNA sequencing. Population structure was identified between the eastern and southern coasts and correlated with the habitat transition between the temperate Agulhas (southern) and subtropical Natal (eastern) Bioregions, suggesting differentiation driven by resource specializations. Differentiation along the Natal coast was comparatively weak, but was evident in some analyses and varied depending on whether the samples were collected during or outside the seasonal sardine ( Sardinops sagax ) run. This local abundance of prey could influence the ranging patterns and apparent genetic structure of T. aduncus . These findings have significant and transferable management implications, most importantly in terms of differentiating populations inhabiting distinct bioregions and seasonal structural patterns within a region associated with the movement of prey resources.

Benthic Invertebrate Indices Show No Response to High Nitrate-Nitrogen in Lowland Agricultural Streams - Thomas P. Moore; Catherine M. Febria; Angus R. McIntosh; Helen J. Warburton; Jon S. Harding (Water, Air, & Soil Pollution, 2021)

Non-native fish as glochidial sinks: elucidating disruption pathways for Echyridella menziesii recruitment - Thomas P. Moore; Susan J. Clearwater (Hydrobiologia, 2021)

An exploratory study to investigate the association between age, physical activity, femoral trochlear cartilage thickness and biomarkers of tissue metabolism in adult males - Harry M. Roberts; Claire L. Griffith-McGeever; Julian A. Owen; Lewis Angell; Jonathan P. Moore; Jeanette M. Thom (European Journal of Applied Physiology, 2021)
Purpose To investigate the association between age, physical activity, femoral trochlear cartilage thickness and biomarkers of tissue metabolism in a cross-sectional sample of adult males. This study utilizes several emerging biomarkers that have been associated with early joint degenerative changes; serum COMP (cartilage oligomeric matrix protein), HA (hyaluronan) and lubricin. Methods Eighty-one males (age: mean (range): 43(18–70) years; body mass index: 25.2 (21.0–30.6) kg/m 2 ) volunteered. Resting serum COMP, HA and lubricin concentrations were determined via commercially available enzyme-linked immunosorbent assay (ELISA) and femoral trochlear cartilage thickness via supra-patellar ultrasound imaging. Physical activity levels were assessed using questionnaires. Statistical analyses were performed using correlation and regression analyses. Results Age was correlated with lateral trochlear cartilage thickness ( r = − 0.372; p < 0.01) and serum COMP ( r = 0.342; p < 0.01). 7-day physical activity was correlated with serum COMP ( r = 0.357, p < 0.01), and 12-month physical activity with both lateral trochlear cartilage thickness ( r = 0.340, p = 0.01) and serum HA ( r = 0.296, p < 0.05). Regression analyses revealed that age significantly accounted for the variability in lateral cartilage thickness and serum COMP, following the adjustment for potential cofounders. However, the association between age and lateral trochlear cartilage thickness was not moderated by physical activity levels (all p > 0.05). Conclusion This study indicates that older age may be associated with thinner lateral trochlear cartilage and higher cartilage turnover. Being physically active may also be positive for lateral trochlear cartilage thickness. However, overall, both age and physical activity level only account for a small amount of the variability in cartilage thickness and serum biomarkers.

Roundup negatively impacts the behavior and nerve function of the Madagascar hissing cockroach (Gromphadorhina portentosa) - Megha Kanabar; Samuel Bauer; Zimuzo M. Ezedum; Ian P. Dwyer; William S. Moore; Gabriella Rodriguez; Aditya Mall; Anne T. Littleton; Michael Yudell; Jenil Kanabar; Wade J. Tucker; Emily R. Daniels; et al. (Environmental Science and Pollution Research, 2021)

Precipitation alters the CO 2 effect on water‐use efficiency of temperate forests - Soumaya Belmecheri; R. Stockton Maxwell; Alan H. Taylor; Kenneth J. Davis; Rossella Guerrieri; David J. P. Moore; Shelly A. Rayback (Global Change Biology, 2021)
Increasing water‐use efficiency (WUE), the ratio of carbon gain to water loss, is a key mechanism that enhances carbon uptake by terrestrial vegetation under rising atmospheric CO 2 ( c a ). Existing theory and empirical evidence suggest a proportional WUE increase in response to rising c a as plants maintain a relatively constant ratio between the leaf intercellular ( c i ) and ambient ( c a ) partial CO 2 pressure ( c i / c a ). This has been hypothesized as the main driver of the strengthening of the terrestrial carbon sink over the recent decades. However, proportionality may not characterize CO 2 effects on WUE on longer time‐scales and the role of climate in modulating these effects is uncertain. Here, we evaluate long‐term WUE responses to c a and climate from 1901 to 2012 CE by reconstructing intrinsic WUE (iWUE, the ratio of photosynthesis to stomatal conductance) using carbon isotopes in tree rings across temperate forests in the northeastern USA. We show that iWUE increased steadily from 1901 to 1975 CE but remained constant thereafter despite continuously rising c a . This finding is consistent with a passive physiological response to c a and coincides with a shift to significantly wetter conditions across the region. Tree physiology was driven by summer moisture at multi‐decadal time‐scales and did not maintain a constant c i / c a in response to rising c a indicating that a point was reached where rising CO 2 had a diminishing effect on tree iWUE. Our results challenge the mechanism, magnitude, and persistence of CO 2 's effect on iWUE with significant implications for projections of terrestrial productivity under a changing climate.

Adherence to annual lung cancer screening with low-dose CT scan in a diverse population - Cherie P. Erkmen; Farouk Dako; Ryan Moore; Chandra Dass; Mark G. Weiner; Larry R. Kaiser; Grace X. Ma (Cancer Causes & Control, 2021)

Gene family amplification facilitates adaptation in freshwater unionid bivalve Megalonaias nervosa - Rebekah L. Rogers; Stephanie L. Grizzard; James E. Titus‐McQuillan; Katherine Bockrath; Sagar Patel; John P. Wares; Jeffrey T. Garner; Cathy C. Moore (Molecular Ecology, 2021)
Freshwater unionid bivalves currently face severe anthropogenic challenges. Over 70% of species in the United States are threatened, endangered or extinct due to pollution, damming of waterways and overfishing. These species are notable for their unusual life history strategy, parasite–host co‐evolution and biparental mitochondrial inheritance. Among this clade, the washboard mussel Megalonaias nervosa is one species that remains prevalent across the Southeastern United States, with robust population sizes. We have created a reference genome for M. nervosa to determine how genome content has evolved in the face of these widespread environmental challenges. We observe dynamic changes in genome content, with a burst of recent transposable element proliferation causing a 382 Mb expansion in genome content. Birth–death models suggest rapid expansions among gene families, with a mutation rate of 1.16 × 10 −8 duplications per gene per generation. Cytochrome P450 gene families have experienced exceptional recent amplification beyond expectations based on genome‐wide birth–death processes. These genes are associated with increased rates of amino acid changes, a signature of selection driving evolution of detox genes. Fitting evolutionary models of adaptation from standing genetic variation, we can compare adaptive potential across species and mutation types. The large population size in M. nervosa suggests a 4.7‐fold advantage in the ability to adapt from standing genetic variation compared with a low diversity endemic E. hopetonensis . Estimates suggest that gene family evolution may offer an exceptional substrate of genetic variation in M. nervosa , with P sgv = 0.185 compared with P sgv = 0.067 for single nucleotide changes. Hence, we suggest that gene family evolution is a source of 'hopeful monsters’ within the genome that may facilitate adaptation when selective pressures shift. These results suggest that gene family expansion is a key driver of adaptive evolution in this key species of freshwater Unionidae that is currently facing widespread environmental challenges. This work has clear implications for conservation genomics on freshwater bivalves as well as evolutionary theory. This genome represents a first step to facilitate reverse ecological genomics in Unionidae and identify the genetic underpinnings of phenotypic diversity.

Climate sensitivity of understory trees differs from overstory trees in temperate mesic forests - Christine R. Rollinson; M. Ross Alexander; Alex W. Dye; David J. P. Moore; Neil Pederson; Valerie Trouet (Ecology, 2021)
The response of understory trees to climate variability is key to understanding current and future forest dynamics. However, analyses of climatic effects on tree growth have primarily focused on the upper canopy, leaving understory dynamics unresolved. We analyzed differences in climate sensitivity based on canopy position of four common tree species ( Acer rubrum , Fagus grandifolia , Quercus rubra , and Tsuga canadensis ) using growth information from 1,084 trees across eight sites in the northeastern United States. Effects of canopy position on climate response varied, but were significant and often nonlinear, for all four species. Compared to overstory trees, understory trees showed stronger reductions in growth at high temperatures and varied shifts in precipitation response. This contradicts the prevailing assumption that climate responses, particularly to temperature, of understory trees are buffered by the overstory. Forest growth trajectories are uncertain in compositionally and structurally complex forests, and future demography and regeneration dynamics may be misinferred if not all canopy levels are represented in future forecasts.

Source of saline groundwater on tidally influenced blue holes on San Salvador Island, Bahamas - Megan E. Smith; Jonathan G. Wynn; Robert J. Scharping; Evan W. Moore; James R. Garey; Bogdan P. Onac (Hydrogeology Journal, 2021)

Climate change facilitates a parasite’s host exploitation via temperature‐mediated immunometabolic processes - Jörn P. Scharsack; Bartholomäus Wieczorek; Alexander Schmidt‐Drewello; Janine Büscher; Frederik Franke; Andrew Moore; Antoine Branca; Anika Witten; Monika Stoll; Erich Bornberg‐Bauer; Susann Wicke; Joachim Kurtz (Global Change Biology, 2021)
Global climate change can influence organismic interactions like those between hosts and parasites. Rising temperatures may exacerbate the exploitation of hosts by parasites, especially in ectothermic systems. The metabolic activity of ectotherms is strongly linked to temperature and generally increases when temperatures rise. We hypothesized that temperature change in combination with parasite infection interferes with the host's immunometabolism. We used a parasite, the avian cestode Schistocephalus solidus , which taps most of its resources from the metabolism of an ectothermic intermediate host, the three‐spined stickleback. We experimentally exposed sticklebacks to this parasite, and studied liver transcriptomes 50 days after infection at 13°C and 24°C, to assess their immunometabolic responses. Furthermore, we monitored fitness parameters of the parasite and examined immunity and body condition of the sticklebacks at 13°C, 18°C and 24°C after 36, 50 and 64 days of infection. At low temperatures (13°C), S. solidus growth was constrained, presumably also by the more active stickleback's immune system, thus delaying its infectivity for the final host to 64 days. Warmer temperature (18°C and 24°C) enhanced S. solidus growth, and it became infective to the final host already after 36 days. Overall, S. solidus produced many more viable offspring after development at elevated temperatures. In contrast, stickleback hosts had lower body conditions, and their immune system was less active at warm temperature. The stickleback's liver transcriptome revealed that mainly metabolic processes were differentially regulated between temperatures, whereas immune genes were not strongly affected. Temperature effects on gene expression were strongly enhanced in infected sticklebacks, and even in exposed‐but‐not‐infected hosts. These data suggest that the parasite exposure in concert with rising temperature, as to be expected with global climate change, shifted the host's immunometabolism, thus providing nutrients for the enormous growth of the parasite and, at the same time suppressing immune defence.

Predicting biodiversity richness in rapidly changing landscapes: climate, low human pressure or protection as salvation? - David W. Macdonald; Luca Chiaverini; Helen M. Bothwell; Żaneta Kaszta; Eric Ash; Gilmoore Bolongon; Özgün Emre Can; Ahimsa Campos-Arceiz; Phan Channa; Gopalasamy Reuben Clements; Andrew J. Hearn; Laurie Hedges; et al. (Biodiversity and Conservation, 2020)
Rates of biodiversity loss in Southeast Asia are among the highest in the world, and the Indo-Burma and South-Central China Biodiversity Hotspots rank among the world’s most threatened. Developing robust multi-species conservation models is critical for stemming biodiversity loss both here and globally. We used a large and geographically extensive remote-camera survey and multi-scale, multivariate optimization species distribution modelling to investigate the factors driving biodiversity across these two adjoining biodiversity hotspots. Four major findings emerged from the work. (i) We identified clear spatial patterns of species richness, with two main biodiverse centres in the Thai-Malay Peninsula and in the mountainous region of Southwest China. (ii) Carnivores in particular, and large ungulates to a lesser degree, were the strongest indicators of species richness. (iii) Climate had the largest effect on biodiversity, followed by protected status and human footprint. (iv) Gap analysis between the biodiversity model and the current system of protected areas revealed that the majority of areas supporting the highest predicted biodiversity are not protected. Our results highlighted several key locations that should be prioritized for expanding the protected area network to maximize conservation effectiveness. We demonstrated the importance of switching from single-species to multi-species approaches to highlight areas of high priority for biodiversity conservation. In addition, since these areas mostly occur over multiple countries, we also advocate for a paradigmatic focus on transboundary conservation planning.

Low Static Shear Modulus Along Foliation and Its Influence on the Elastic and Strength Anisotropy of Poorman Schist Rocks, Homestake Mine, South Dakota - Katherine J. Condon; Hiroki Sone; Herbert F. Wang; J. Ajo-Franklin; T. Baumgartner; K. Beckers; D. Blankenship; A. Bonneville; L. Boyd; S. Brown; J. A. Burghardt; C. Chai; et al. (Rock Mechanics and Rock Engineering, 2020)

Impacts on freshwater macrophytes produced by small invertebrate herbivores: Afrotropical and Neotropical wetlands compared - M. Celeste Franceschini; Kevin J. Murphy; Isabel Moore; Michael P. Kennedy; Fedra S. Martínez; Frank Willems; M. Laura De Wysiecki; Henry Sichingabula (Hydrobiologia, 2020)

Common transcriptome, plasma molecules, and imaging signatures in the aging brain and a Mendelian neurovascular disease, cerebral cavernous malformation - Janne Koskimäki; Sean P. Polster; Yan Li; Sharbel Romanos; Abhinav Srinath; Dongdong Zhang; Julián Carrión-Penagos; Rhonda Lightle; Thomas Moore; Seán B. Lyne; Agnieszka Stadnik; Kristina Piedad; et al. (GeroScience, 2020)

Respiration cycle duration and seawater flux through open blowholes of humpback ( Megaptera novaeangliae ) and North Atlantic right ( Eubalaena glacialis ) whales - Maria Clara Iruzun Martins; Carolyn Miller; Phillip Hamilton; Jooke Robbins; Daniel P. Zitterbart; Michael Moore (Marine Mammal Science, 2020)
Little is known about the dynamics of baleen whale respiratory cycles, especially the mechanics and activity of the blowholes and their interaction with seawater. In this study, the duration of complete respiration cycles (expiration/inhalation events) were quantified for the first time in two species: North Atlantic right whale (NARW) and humpback whale (HW) using high resolution, detailed imagery from an unoccupied aerial system (UAS). The mean duration of complete respiration cycles (expiration/inhalation event) in the NARW and HW were 3.07 s ( SD = 0.503, n = 15) and 2.85 s ( SD = 0.581, n = 21), respectively. Furthermore, we saw no significant differences in respiration cycle duration between age and sex classes in the NARW, but significant differences were observed between age classes in the HW. The observation of seawater covering an open blowhole was also quantified, with NARW having 20% of all breaths with seawater presence versus 90% in HW. Seawater incursion has not been described previously and challenges the general consensus that water does not enter the respiratory tract in baleen whales. Prevalent seawater has implications for the analysis and interpretation of exhaled respiratory vapor/mucosa samples, as well as for the potential inhalation of oil in spills.

Relative size underlies alternative morph development in a salamander - Michael P. Moore; Joseph H. K. Pechmann; Howard H. Whiteman (Oecologia, 2020)

Speleothem and glacier records of latest Pleistocene–early Holocene climate change in the western North American interior - Brendon J. Quirk; Glen N. Mackey; Diego P. Fernandez; Andy Armstrong; Jeffrey R. Moore (Journal of Quaternary Science, 2020)
Rapid and high‐magnitude North Atlantic climate oscillations following the Last Glacial Maximum have been correlated to climate change events in western North America. However, the strength of teleconnections between the North Atlantic and the interior of western North America remains poorly understood. We present a U‐series calibrated speleothem record from Timpanogos Cave National Monument, located at 2040 m asl in the Wasatch Mountains of Utah, spanning 13.5–10.6 ka. Additionally, we carried out a climate reconstruction for a coeval glacier advance in the Wind River Range of Wyoming. Our results indicate that between 13.5 and 12.8 ka, the Wasatch was probably first cool and dry and then warmed. After 12.8 ka, our record suggests cool and/or wetter conditions followed by reduced moisture until 11.8 ka, followed by an early Holocene wet period. The Timpanogos record exhibits few similarities with those from the North Atlantic. Climate reconstructions of the Titcomb Basin glacier suggest modest temperature depressions relative to modern ( 150%). The high‐altitude speleothem record presented here provides a valuable basis for understanding latest Pleistocene–early Holocene glacial episodes in western North America.

The Marine Knowledge Exchange Network: Insights from an Innovative Regional-to-National Scale Academic-Led Knowledge-to-Impact Network and Recommendations for Future Initiatives - M.T. Johnson; L.J. Johnson; G.A. Bayliss-Brown; V. Danino; S. Day; I. Dunnett; J. Forster; I. Lorenzoni; K. Kennedy; G. Malin; K. Moore; P. Moore Fuller; et al. (Coastal Management, 2020)

Comparative Toxicity of Nitrate to Common and Imperiled Freshwater Mussel Glochidia and Larval Fishes - Adrian P. Moore; Robert B. Bringolf (Archives of Environmental Contamination and Toxicology, 2020)

Design catalogue for eco-engineering of coastal artificial structures: a multifunctional approach for stakeholders and end-users - Kathryn A. O’Shaughnessy; Stephen J. Hawkins; Ally J. Evans; Mick E. Hanley; Paul Lunt; Richard C. Thompson; Robert A. Francis; Simon P. G. Hoggart; Pippa J. Moore; Gregorio Iglesias; David Simmonds; James Ducker; et al. (Urban Ecosystems, 2020)
Coastal urbanisation, energy extraction, food production, shipping and transportation have led to the global proliferation of artificial structures within the coastal and marine environments (sensu “ocean sprawl”), with subsequent loss of natural habitats and biodiversity. To mitigate and compensate impacts of ocean sprawl, the practice of eco-engineering of artificial structures has been developed over the past decade. Eco-engineering aims to create sustainable ecosystems that integrate human society with the natural environment for the benefit of both. The science of eco-engineering has grown markedly, yet synthesis of research into a user-friendly and practitioner-focused format is lacking. Feedback from stakeholders has repeatedly stated that a “photo user guide” or “manual” covering the range of eco-engineering options available for artificial structures would be beneficial. However, a detailed and structured “user guide” for eco-engineering in coastal and marine environments is not yet possible; therefore we present an accessible review and catalogue of trialled eco-engineering options and a summary of guidance for a range of different structures tailored for stakeholders and end-users as the first step towards a structured manual. This work can thus serve as a potential template for future eco-engineering guides. Here we provide suggestions for potential eco-engineering designs to enhance biodiversity and ecosystem functioning and services of coastal artificial structures with the following structures covered: (1) rock revetment, breakwaters and groynes composed of armour stones or concrete units; (2) vertical and sloping seawalls; (3) over-water structures (i.e., piers) and associated support structures; and (4) tidal river walls.

Climate and human water use diminish wetland networks supporting continental waterbird migration - J. Patrick Donnelly; Sammy L. King; Nicholas L. Silverman; Daniel P. Collins; Eduardo M. Carrera‐Gonzalez; Alberto Lafón‐Terrazas; Johnnie N. Moore (Global Change Biology, 2020)
Migrating waterbirds moving between upper and lower latitudinal breeding and wintering grounds rely on a limited network of endorheic lakes and wetlands when crossing arid continental interiors. Recent drying of global endorheic water stores raises concerns over deteriorating migratory pathways, yet few studies have considered these effects at the scale of continental flyways. Here, we investigate the resiliency of waterbird migration networks across western North America by reconstructing long‐term patterns (1984–2018) of terminal lake and wetland surface water area in 26 endorheic watersheds. Findings were partitioned regionally by snowmelt‐ and monsoon‐driven hydrologies and combined with climate and human water‐use data to determine their importance in predicting surface water trends. Nonlinear patterns of lake and wetland drying were apparent along latitudinal flyway gradients. Pervasive surface water declines were prevalent in northern snowmelt watersheds (lakes −27%, wetlands −47%) while largely stable in monsoonal watersheds to the south (lakes −13%, wetlands +8%). Monsoonal watersheds represented a smaller proportion of total lake and wetland area, but their distribution and frequency of change within highly arid regions of the continental flyway increased their value to migratory waterbirds. Irrigated agriculture and increasing evaporative demands were the most important drivers of surface water declines. Underlying agricultural and wetland relationships however were more complex. Approximately 7% of irrigated lands linked to flood irrigation and water storage practices supported 61% of all wetland inundation in snowmelt watersheds. In monsoonal watersheds, small earthen dams, meant to capture surface runoff for livestock watering, were a major component of wetland resources (67%) that supported networks of isolated wetlands surrounding endorheic lakes. Ecological trends and human impacts identified herein underscore the importance of assessing flyway‐scale change as our model depictions likely reflect new and emerging bottlenecks to continental migration.

RAD-Seq Analysis and in situ Monitoring of Nassau Grouper Reveal Fine-Scale Population Structure and Origins of Aggregating Fish - Krista D. Sherman; Josephine R. Paris; Robert Andrew King; Karen A. Moore; Craig P. Dahlgren; Lindy C. Knowles; Kristine Stump; Charles R. Tyler; Jamie R. Stevens (Frontiers in Marine Science, 2020)

Extracellular vesicles from mesenchymal stem cells reduce microglial-mediated neuroinflammation after cortical injury in aged Rhesus monkeys - Veronica Go; Bethany G. E. Bowley; Monica A. Pessina; Zheng Gang Zhang; Michael Chopp; Seth P. Finklestein; Douglas L. Rosene; Maria Medalla; Benjamin Buller; Tara L. Moore (GeroScience, 2020)

Tornado-days in the United States by phase of the Madden–Julian oscillation and global wind oscillation - Todd W. Moore; Michael P. McGuire (Climate Dynamics, 2020)

Resistance, Extinction, and Everything in Between – The Diverse Responses of Seaweeds to Marine Heatwaves - Sandra C. Straub; Thomas Wernberg; Mads S. Thomsen; Pippa J. Moore; Michael T. Burrows; Ben P. Harvey; Dan A. Smale (Frontiers in Marine Science, 2019)

Ovine Abortion by Neospora caninum: First Case Reported in Argentina - Yanina P. Hecker; Eleonora L. Morrell; María A. Fiorentino; Ignacio Gual; Emilia Rivera; Franco Fiorani; Matías A. Dorsch; María L. Gos; Lais L. Pardini; María V. Scioli; Sergio Magariños; Fernando A. Paolicchi; et al. (Acta Parasitologica, 2019)

A mother’s legacy: the strength of maternal effects in animal populations - Michael P. Moore; Howard H. Whiteman; Ryan A. Martin (Ecology Letters, 2019)
Although mothers influence the traits of their offspring in many ways beyond the transmission of genes, it remains unclear how important such ‘maternal effects’ are to phenotypic differences among individuals. Synthesizing estimates derived from detailed pedigrees, we evaluated the amount of phenotypic variation determined by maternal effects in animal populations. Maternal effects account for half as much phenotypic variation within populations as do additive genetic effects. Maternal effects most greatly affect morphology and phenology but, surprisingly, are not stronger in species with prolonged maternal care than in species without. While maternal effects influence juvenile traits more than adult traits on average, they do not decline across ontogeny for behaviour or physiology, and they do not weaken across the life cycle in species without maternal care. These findings underscore maternal effects as an important source of phenotypic variation and emphasise their potential to affect many ecological and evolutionary processes.

Synergies in Operational Oceanography: The Intrinsic Need for Sustained Ocean Observations - Fraser Davidson; Aida Alvera-Azcárate; Alexander Barth; Gary B. Brassington; Eric P. Chassignet; Emanuela Clementi; Pierre De Mey-Frémaux; Prasanth Divakaran; Christopher Harris; Fabrice Hernandez; Patrick Hogan; Lars R. Hole; et al. (Frontiers in Marine Science, 2019)

Ingestion and Absorption of Eucalypt Monoterpenes in the Specialist Feeder, the Koala (Phascolarctos cinereus) - Caroline Marschner; Mark B. Krockenberger; Damien P. Higgins; Christopher Mitchell; Ben D. Moore (Journal of Chemical Ecology, 2019)

A Mechanical Brain Damage Framework Used to Model Abnormal Brain Tau Protein Accumulations of National Football League Players - M. F. Horstemeyer; P. R. Berthelson; J. Moore; A. K. Persons; A. Dobbins; R. K. Prabhu (Annals of Biomedical Engineering, 2019)

Linking drought legacy effects across scales: From leaves to tree rings to ecosystems - Steven A. Kannenberg; Kimberly A. Novick; M. Ross Alexander; Justin T. Maxwell; David J. P. Moore; Richard P. Phillips; William R. L. Anderegg (Global Change Biology, 2019)
Severe drought can cause lagged effects on tree physiology that negatively impact forest functioning for years. These “drought legacy effects” have been widely documented in tree‐ring records and could have important implications for our understanding of broader scale forest carbon cycling. However, legacy effects in tree‐ring increments may be decoupled from ecosystem fluxes due to (a) postdrought alterations in carbon allocation patterns; (b) temporal asynchrony between radial growth and carbon uptake; and (c) dendrochronological sampling biases. In order to link legacy effects from tree rings to whole forests, we leveraged a rich dataset from a Midwestern US forest that was severely impacted by a drought in 2012. At this site, we compiled tree‐ring records, leaf‐level gas exchange, eddy flux measurements, dendrometer band data, and satellite remote sensing estimates of greenness and leaf area before, during, and after the 2012 drought. After accounting for the relative abundance of tree species in the stand, we estimate that legacy effects led to ~10% reductions in tree‐ring width increments in the year following the severe drought. Despite this stand‐scale reduction in radial growth, we found that leaf‐level photosynthesis, gross primary productivity (GPP), and vegetation greenness were not suppressed in the year following the 2012 drought. Neither temporal asynchrony between radial growth and carbon uptake nor sampling biases could explain our observations of legacy effects in tree rings but not in GPP. Instead, elevated leaf‐level photosynthesis co‐occurred with reduced leaf area in early 2013, indicating that resources may have been allocated away from radial growth in conjunction with postdrought upregulation of photosynthesis and repair of canopy damage. Collectively, our results indicate that tree‐ring legacy effects were not observed in other canopy processes, and that postdrought canopy allocation could be an important mechanism that decouples tree‐ring signals from GPP.

Temperature-responsive PNDJ hydrogels provide high and sustained antimicrobial concentrations in surgical sites - Derek J. Overstreet; Vajra S. Badha; John M. Heffernan; Erin P. Childers; Rex C. Moore; Brent L. Vernon; Alex C. McLaren (Drug Delivery and Translational Research, 2019)

Connectivity in coastal systems: Barrier island vegetation influences upland migration in a changing climate - Julie C. Zinnert; Stephen M. Via; Benjamin P. Nettleton; Philip A. Tuley; Laura J. Moore; Jon Anthony Stallins (Global Change Biology, 2019)
Due to their position at the land–sea interface, barrier islands are vulnerable to both oceanic and atmospheric climate change‐related drivers. In response to relative sea‐level rise, barrier islands tend to migrate landward via overwash processes which deposit sediment onto the backbarrier marsh, thus maintaining elevation above sea level. In this paper, we assess the importance of interior upland vegetation and sediment transport (from upland to marsh) on the movement of the marsh–upland boundary in a transgressive barrier system along the mid‐Atlantic Coast. We hypothesize that recent woody expansion is altering the rate of marsh to upland conversion. Using Landsat imagery over a 32 year time period (1984–2016), we quantify transitions between land cover (bare, grassland, woody vegetation, and marsh) and the marsh–upland boundary. We find that the Virginia Barrier Islands have both gains and losses in backbarrier marsh and upland, with 19% net loss from the system during the timeframe of the study and increased variance in marsh to upland conversion. This is consistent with recent work indicating a shift toward increasing rates of landward barrier island migration. Despite a net loss of upland area, macroclimatic winter warming resulted in 41% increase in woody vegetation in protected, low‐elevation areas, introducing new ecological scenarios that increase resistance to sediment movement from upland to marsh. Our analysis demonstrates how the interplay between elevation and interior island vegetative cover influences landward migration of the boundary between upland and marsh (a previously underappreciated indicator that an island is migrating), and thus, the importance of including ecological processes in the island interior into coastal modeling of barrier island migration and sediment movement across the barrier landscape.

Antibiotic misuse in respiratory tract infections in children and adults—a prospective, multicentre study (TAILORED Treatment) - Chantal B. van Houten; Asi Cohen; Dan Engelhard; John P. Hays; Roger Karlsson; Edward Moore; David Fernández; Racheli Kreisberg; Laurence V. Collins; Wouter de Waal; Karin M. de Winter-de Groot; Tom F. W. Wolfs; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Nursery crowding does not influence offspring, but might influence parental, fitness in a phytotelm-breeding frog - Emily S. Khazan; Tom Verstraten; Michael P. Moore; Matthew B. Dugas (Behavioral Ecology and Sociobiology, 2019)

Overexpressing ovotransferrin and avian β-defensin-3 improves antimicrobial capacity of chickens and poultry products - Caitlin A. Cooper; Mark L. Tizard; Tamsyn Stanborough; Sean C. Moore; P. Scott Chandry; Kristie A. Jenkins; Terry G. Wise; Terri E. O’Neil; Daniel S. Layton; Kirsten R. Morris; Robert J. Moore; Narelle Fegan; et al. (Transgenic Research, 2019)

Response to Comment on: “Estimating the Bioconcentration Factors of Hydrophobic Organic Chemicals from Biotransformation Rates Using Rainbow Trout Hepatocytes” - Frank A. P. C. Gobas; Yung-Shan Lee; Leslie J. Saunders; Margo M. Moore; Jennifer J. Trowell; Christopher J. Kennedy (Archives of Environmental Contamination and Toxicology, 2019)

Leaf functional trait responses to changes in water status differ among three oak (Quercus) species - Caitlyn E. Cooper; Jason G. Vogel; James P. Muir; Georgianne W. Moore (Plant Ecology, 2018)

Troubled waters: Threats and extinction risk of the sharks, rays and chimaeras of the Arabian Sea and adjacent waters - Rima W. Jabado; Peter M. Kyne; Riley A. Pollom; David A. Ebert; Colin A. Simpfendorfer; Gina M. Ralph; Shaikha S. Al Dhaheri; K. V. Akhilesh; Khadeeja Ali; Mohamud Hassan Ali; Tariq M. S. Al Mamari; K. K. Bineesh; et al. (Fish and Fisheries, 2018)
The extinction risk of sharks, rays and chimaeras is higher than that for most other vertebrates due to low intrinsic population growth rates of many species and the fishing intensity they face. The Arabian Sea and adjacent waters border some of the most important chondrichthyan fishing and trading nations globally, yet there has been no previous attempt to assess the conservation status of species occurring here. Using IUCN Red List of Threatened Species Categories and Criteria and their guidelines for application at the regional level, we present the first assessment of extinction risk for 153 species of sharks, rays and chimaeras. Results indicate that this region, home to 15% of described chondrichthyans including 30 endemic species, has some of the most threatened chondrichthyan populations in the world. Seventy‐eight species (50.9%) were assessed as threatened (Critically Endangered, Endangered or Vulnerable), and 27 species (17.6%) as Near Threatened. Twenty‐nine species (19%) were Data Deficient with insufficient information to assess their status. Chondrichthyan populations have significantly declined due to largely uncontrolled and unregulated fisheries combined with habitat degradation. Further, there is limited political will and national and regional capacities to assess, manage, conserve or rebuild stocks. Outside the few deepsea locations that are lightly exploited, the prognosis for the recovery of most species is poor in the near‐absence of management. Concerted national and regional management measures are urgently needed to ensure extinctions are avoided, the sustainability of more productive species is secured, and to avoid the continued thinning of the regional food security portfolio.

Trade-offs between larval survival and adult ornament development depend on predator regime in a territorial dragonfly - Michael P. Moore; Ryan A. Martin (Oecologia, 2018)

Interaction between known risk factors for head and neck cancer and socioeconomic status: the Carolina Head and Neck Cancer Study - Gaelen Stanford-Moore; Patrick T. Bradshaw; Mark C. Weissler; Jose P. Zevallos; Paul Brennan; Devasena Anantharaman; Behnoush Abedi-Ardekani; Andrew F. Olshan (Cancer Causes & Control, 2018)

Isolation by marine barriers and climate explain areas of endemism in an island rodent - Thomas C. Giarla; Sean P. Maher; Anang S. Achmadi; Meagan K. Moore; Mark T. Swanson; Kevin C. Rowe; Jacob A. Esselstyn (Journal of Biogeography, 2018)
Aim The Indonesian island of Sulawesi is home to thousands of endemic terrestrial animal species. Phylogeographical studies of some of these taxa revealed concordant distribution patterns (areas of endemism; AoEs), suggestive of a shared evolutionary or ecological mechanism driving divergence among various terrestrial taxa. Generally, AoEs have been attributed to Pleistocene marine incursions, geological fault zones and Sulawesi's history as an archipelago. We test, for the first time, the hypothesis that population divergences are associated with unsuitable climate spaces at the boundaries between these areas. Location Sulawesi, Indonesia. Taxon Maxomys musschenbroekii , a common murid rodent endemic to Sulawesi. Methods We sequenced a mitochondrial gene, four nuclear protein‐coding genes and hundreds of ultraconserved elements from individuals sampled across the island, which we used to build intraspecific phylogenies and identify population structure. To test climate‐related hypotheses, we used multiple regression to assess the extent to which genetic distances, over‐land geographical distances, environmental distances (derived from ecological niche model resistance surfaces) and areas of endemism are correlated. Results In all three genetic datasets, we inferred phylogeographical structure that is geographically concordant with previously defined AoEs. Ecological niche models showed a similar geography of suitability across the island since the Last Glacial Maximum, with varying levels of unsuitable climate space between AoEs. Genetic distances were more strongly correlated with environmental distances than geographical distances and interspecific divergences arose just in the past 1.5 Myr. Main Conclusions Population divergences within M. musschenbroekii are consistent with AoE definitions from other taxa. Stable areas of unsuitable habitat near AoE boundaries probably supplemented marine incursions in generating population structure within M. musschenbroekii and other co‐distributed species.

Geographical CO 2 sensitivity of phytoplankton correlates with ocean buffer capacity - Sophie Richier; Eric P. Achterberg; Matthew P. Humphreys; Alex J. Poulton; David J. Suggett; Toby Tyrrell; Christopher Mark Moore (Global Change Biology, 2018)
Accumulation of anthropogenic CO 2 is significantly altering ocean chemistry. A range of biological impacts resulting from this oceanic CO 2 accumulation are emerging, however, the mechanisms responsible for observed differential susceptibility between organisms and across environmental settings remain obscure. A primary consequence of increased oceanic CO 2 uptake is a decrease in the carbonate system buffer capacity, which characterizes the system's chemical resilience to changes in CO 2 , generating the potential for enhanced variability in p CO 2 and the concentration of carbonate [ ], bicarbonate [ ], and protons [H + ] in the future ocean. We conducted a meta‐analysis of 17 shipboard manipulation experiments performed across three distinct geographical regions that encompassed a wide range of environmental conditions from European temperate seas to Arctic and Southern oceans. These data demonstrated a correlation between the magnitude of natural phytoplankton community biological responses to short‐term CO 2 changes and variability in the local buffer capacity across ocean basin scales. Specifically, short‐term suppression of small phytoplankton ( p CO 2 within experiments performed in regions with higher ambient buffer capacity. The results further highlight the relevance of phytoplankton cell size for the impacts of enhanced p CO 2 in both the modern and future ocean. Specifically, cell size‐related acclimation and adaptation to regional environmental variability, as characterized by buffer capacity, likely influences interactions between primary producers and carbonate chemistry over a range of spatio‐temporal scales.

Climate research priorities for policy-makers, practitioners, and scientists in Georgia, USA - Murray A. Rudd; Althea F. P. Moore; Daniel Rochberg; Lisa Bianchi-Fossati; Marilyn A. Brown; David D’Onofrio; Carrie A. Furman; Jairo Garcia; Ben Jordan; Jennifer Kline; L. Mark Risse; Patricia L. Yager; et al. (Environmental Management, 2018)

Estimating the Bioconcentration Factors of Hydrophobic Organic Compounds from Biotransformation Rates Using Rainbow Trout Hepatocytes - Jennifer J. Trowell; Frank A. P. C. Gobas; Margo M. Moore; Christopher J. Kennedy (Archives of Environmental Contamination and Toxicology, 2018)

Genomes of ubiquitous marine and hypersaline Hydrogenovibrio , Thiomicrorhabdus and Thiomicrospira spp. encode a diversity of mechanisms to sustain chemolithoautotrophy in heterogeneous environments - Kathleen M. Scott; John Williams; Cody M. B. Porter; Sydney Russel; Tara L. Harmer; John H. Paul; Kirsten M. Antonen; Megan K. Bridges; Gary J. Camper; Christie K. Campla; Leila G. Casella; Eva Chase; et al. (Environmental Microbiology, 2018)
Summary Chemolithoautotrophic bacteria from the genera Hydrogenovibrio, Thiomicrorhabdus and Thiomicrospira are common, sometimes dominant, isolates from sulfidic habitats including hydrothermal vents, soda and salt lakes and marine sediments. Their genome sequences confirm their membership in a deeply branching clade of the Gammaproteobacteria . Several adaptations to heterogeneous habitats are apparent. Their genomes include large numbers of genes for sensing and responding to their environment (EAL‐ and GGDEF‐domain proteins and methyl‐accepting chemotaxis proteins) despite their small sizes (2.1–3.1 Mbp). An array of sulfur‐oxidizing complexes are encoded, likely to facilitate these organisms' use of multiple forms of reduced sulfur as electron donors. Hydrogenase genes are present in some taxa, including group 1d and 2b hydrogenases in Hydrogenovibrio marinus and H. thermophilus MA2‐6, acquired via horizontal gene transfer. In addition to high‐affinity cbb 3 cytochrome c oxidase, some also encode cytochrome bd‐ type quinol oxidase or ba 3 ‐ type cytochrome c oxidase, which could facilitate growth under different oxygen tensions, or maintain redox balance. Carboxysome operons are present in most, with genes downstream encoding transporters from four evolutionarily distinct families, which may act with the carboxysomes to form CO 2 concentrating mechanisms. These adaptations to habitat variability likely contribute to the cosmopolitan distribution of these organisms.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Evaluation of frequency of antibodies against Toxoplasma gondii,Neospora caninum and Sarcocystis spp. and transmission routes in sheep from Humid Pampa, Argentina - Yanina P. Hecker; Fernando Mogaburu Masson; Joaquín I. Armendano; Juan Cora; Carlos Flores Olivares; Ignacio Gual; Lais Pardini; Dadín P. Moore; Gastón Moré; Germán J. Cantón (Acta Parasitologica, 2018)
The aim of this study was to describe the frequency of ovine specific antibodies to Toxoplasma gondii , Neospora caninum and Sarcocystis spp. and to estimate different transmission routes of these infections. One hundred and thirty Texel sheep and their 117 Texel lambs were included in the study. Serum samples were tested for antibodies to T . gondii , N . caninum and Sarcocystis spp. using IFAT. Toxoplasma gondii seroprevalence was 10.00% in sheep (IC 95% : 4.80–15.20%), being higher in adult sheep (≥12 year) than in younger sheep (OR 1.30; 95% CI, 1.10–1.50). N . caninum and Sarcocystis spp. seroprevalences were 1.54% (IC 95% : 0.00–5.70) and 72.09% (IC 95% : 67.70–82.70), respectively, with no association between age and seropositivity in sheep ( P >0.05). T . gondii seroprevalence in lambs was 4.27% (IC 95% : 0.61–7.94). No association between T . gondii serological status in sheep and their lambs was detected ( P = 0.07). Two T . gondii and Sarcocystis spp. seropositive lambs were euthanized and T . gondii and Sarcocystis spp. DNA was detected by PCR in their tissues. In conclusion, the increase of T . gondii seropositivity in relationship with sheep age and the lack of association between sheep-lamb serological status, suggest that horizontal infection is the main transmission route in this flock as reported before. Due to the low number of N . caninum -seropositive ewes no assumptions can be done about the impact of this parasite in this flock. According with previous reports, the main transmission route for Sarcocystis spp. in this species in the present study was horizontal.

The effect of aerobic walking and lower body resistance exercise on serum COMP and hyaluronan, in both males and females - Harry M. Roberts; Jonathan P. Moore; Jeanette M. Thom (European Journal of Applied Physiology, 2018)

Neural correlates of verbal memory in youth with heavy prenatal alcohol exposure - Lauren A. Gross; Eileen M. Moore; Jeffrey R. Wozniak; Claire D. Coles; Julie A. Kable; Elizabeth R. Sowell; Kenneth L. Jones; Edward P. Riley; Sarah N. Mattson (Brain Imaging and Behavior, 2018)

The influence of aquaculture unit proximity on the pattern of Lepeophtheirus salmonis infection of anadromous Salmo trutta populations on the isle of Skye, Scotland - I. Moore; J. A. Dodd; M. Newton; C. W. Bean; I. Lindsay; P. Jarosz; C. E. Adams (Journal of Fish Biology, 2018)
A total of 230 anadromous Salmo trutta (brown trout) were sampled in five sheltered coastal fjords (or sea lochs) on the Isle of Skye, Scotland, U.K., in 2016 at varying distances from active Atlantic salmon Salmo salar farms. Statistical models were developed to investigate potential correlations between salmon lice Lepeophtheirus salmonis burdens on S. trutta hosts and their proximity to S. salar farm cages. Significant correlations were found between lice burdens and fish fork length and proximity to the nearest S. salar farm. The probability of the presence of L. salmonis on fish hosts increased with fish host size and with distance from the nearest S. salar farm, but total lice burdens were highest in fish sampled near S. salar farms and decreased with distance. The proportion of different life‐cycle stages of L. salmonis were also dependent on S. salar farm proximity, with higher juvenile lice numbers recorded at sites near S. salar farm cages. These results highlight the complexity of the relationship between S. trutta and L. salmonis infections on wild fish and emphasize the requirement of further research to quantify these effects to better inform conservation and management strategies, particularly in areas of active S. salar farm facilities.

Occurrence of quiescence in free-ranging migratory songbirds - Lynn N. Schofield; Jill L. Deppe; Robert H. Diehl; Michael P. Ward; Rachel T. Bolus; Theodore J. Zenzal; Jaclyn Smolinsky; Frank R. Moore (Behavioral Ecology and Sociobiology, 2018)

Relative influences of multiple sources of uncertainty on cumulative and incremental tree-ring-derived aboveground biomass estimates - M. Ross Alexander; Christine R. Rollinson; Flurin Babst; Valerie Trouet; David J. P. Moore (Trees, 2018)

An Ibero-American inter-laboratory trial to evaluate serological tests for the detection of anti-Neospora caninum antibodies in cattle - Lucía M. Campero; Javier Moreno-Gonzalo; María C. Venturini; Gastón Moré; Andrea Dellarupe; Magdalena Rambeaud; Ignacio E. Echaide; Beatriz Valentini; Carlos M. Campero; Dadín P. Moore; Dora B. Cano; Marcelo Fort; et al. (Tropical Animal Health and Production, 2018)

Larval body condition regulates predator‐induced life‐history variation in a dragonfly - Michael P. Moore; Cassandra Lis; Ryan A. Martin (Ecology, 2018)
Organisms with complex life cycles commonly exhibit adaptive plasticity in the timing of transitions between life stages. While the threat of predation is predicted to induce earlier transitions, empirical support has been equivocal. When predation risk affects both the propensity to transition to the next life stage and the ability to reach the energetic thresholds necessary to complete the transition, only those individuals in the best physiological condition may be able to accelerate development and emerge earlier. To test this hypothesis, we followed uniquely marked dragonfly larvae ( Pachydiplax longipennis ) through emergence in pools where we factorially manipulated the presence of a large heterospecific predator ( Anax junius ) and cannibalism risk via conspecific size variation. Consistent with our hypothesis, high‐condition larvae were more likely to emerge in the presence of the heterospecific predator than in its absence, and low‐condition larvae were more likely to emerge in its absence than in its presence. Moreover, high‐condition larvae emerged earlier when cannibalism risk was high than when it was low. Predation risk therefore has condition‐dependent effects on emergence. As predation risk frequently affects resource accumulation, similar mechanisms across taxa could commonly underlie the incongruence between empirical results and theoretical expectations for predator‐induced life‐history variation.

MODIS land cover uncertainty in regional climate simulations - Xue Li; Joseph P. Messina; Nathan J. Moore; Peilei Fan; Ashton M. Shortridge (Climate Dynamics, 2017)

Genomic insights into specialized metabolism in the marine actinomycete Salinispora - Anne‐Catrin Letzel; Jing Li; Gregory C.A. Amos; Natalie Millán‐Aguiñaga; Joape Ginigini; Usama R. Abdelmohsen; Susana P. Gaudêncio; Nadine Ziemert; Bradley S. Moore; Paul R. Jensen (Environmental Microbiology, 2017)
Summary Comparative genomics is providing new opportunities to address the diversity and distributions of genes encoding the biosynthesis of specialized metabolites. An analysis of 119 genome sequences representing three closely related species of the marine actinomycete genus Salinispora reveals extraordinary biosynthetic diversity in the form of 176 distinct biosynthetic gene clusters (BGCs) of which only 24 have been linked to their products. Remarkably, more than half of the BGCs were observed in only one or two strains, suggesting they were acquired relatively recently in the evolutionary history of the genus. These acquired gene clusters are concentrated in specific genomic islands, which represent hot spots for BGC acquisition. While most BGCs are stable in terms of their chromosomal position, others migrated to different locations or were exchanged with unrelated gene clusters suggesting a plug and play type model of evolution that provides a mechanism to test the relative fitness effects of specialized metabolites. Transcriptome analyses were used to address the relationships between BGC abundance, chromosomal position and product discovery. The results indicate that recently acquired BGCs can be functional and that complex evolutionary processes shape the micro‐diversity of specialized metabolism observed in closely related environmental bacteria.

Emergent climate and CO 2 sensitivities of net primary productivity in ecosystem models do not agree with empirical data in temperate forests of eastern North America - Christine R. Rollinson; Yao Liu; Ann Raiho; David J. P. Moore; Jason McLachlan; Daniel A. Bishop; Alex Dye; Jaclyn H. Matthes; Amy Hessl; Thomas Hickler; Neil Pederson; Benjamin Poulter; et al. (Global Change Biology, 2017)
Ecosystem models show divergent responses of the terrestrial carbon cycle to global change over the next century. Individual model evaluation and multimodel comparisons with data have largely focused on individual processes at subannual to decadal scales. Thus far, data‐based evaluations of emergent ecosystem responses to climate and CO 2 at multidecadal and centennial timescales have been rare. We compared the sensitivity of net primary productivity ( NPP ) to temperature, precipitation, and CO 2 in ten ecosystem models with the sensitivities found in tree‐ring reconstructions of NPP and raw ring‐width series at six temperate forest sites. These model‐data comparisons were evaluated at three temporal extents to determine whether the rapid, directional changes in temperature and CO 2 in the recent past skew our observed responses to multiple drivers of change. All models tested here were more sensitive to low growing season precipitation than tree‐ring NPP and ring widths in the past 30 years, although some model precipitation responses were more consistent with tree rings when evaluated over a full century. Similarly, all models had negative or no response to warm‐growing season temperatures, while tree‐ring data showed consistently positive effects of temperature. Although precipitation responses were least consistent among models, differences among models to CO 2 drive divergence and ensemble uncertainty in relative change in NPP over the past century. Changes in forest composition within models had no effect on climate or CO 2 sensitivity. Fire in model simulations reduced model sensitivity to climate and CO 2 , but only over the course of multiple centuries. Formal evaluation of emergent model behavior at multidecadal and multicentennial timescales is essential to reconciling model projections with observed ecosystem responses to past climate change. Future evaluation should focus on improved representation of disturbance and biomass change as well as the feedbacks with moisture balance and CO 2 in individual models.

Decay of the glycolytic pathway and adaptation to intranuclear parasitism within Enterocytozoonidae microsporidia - Dominic Wiredu Boakye; Pattana Jaroenlak; Anuphap Prachumwat; Tom A. Williams; Kelly S. Bateman; Ornchuma Itsathitphaisarn; Kallaya Sritunyalucksana; Konrad H. Paszkiewicz; Karen A. Moore; Grant D. Stentiford; Bryony A. P. Williams (Environmental Microbiology, 2017)
Summary Glycolysis and oxidative phosphorylation are the fundamental pathways of ATP generation in eukaryotes. Yet in microsporidia, endoparasitic fungi living at the limits of cellular streamlining, oxidative phosphorylation has been lost: energy is obtained directly from the host or, during the dispersive spore stage, via glycolysis. It was therefore surprising when the first sequenced genome from the Enterocytozoonidae – a major family of human and animal‐infecting microsporidians – appeared to have lost genes for glycolysis. Here, we sequence and analyse genomes from additional members of this family, shedding new light on their unusual biology. Our survey includes the genome of Enterocytozoon hepatopenaei , a major aquacultural parasite currently causing substantial economic losses in shrimp farming, and Enterospora canceri , a pathogen that lives exclusively inside epithelial cell nuclei of its crab host. Our analysis of gene content across the clade suggests that Ent. canceri 's adaptation to intranuclear life is underpinned by the expansion of transporter families. We demonstrate that this entire lineage of pathogens has lost glycolysis and, uniquely amongst eukaryotes, lacks any obvious intrinsic means of generating energy. Our study provides an important resource for the investigation of host‐pathogen interactions and reductive evolution in one of the most medically and economically important microsporidian lineages.

Microglia activation and phagocytosis: relationship with aging and cognitive impairment in the rhesus monkey - Eli Shobin; Michael P. Bowley; Larissa I. Estrada; Nadine C. Heyworth; Mary E. Orczykowski; Sherri A. Eldridge; Samantha M. Calderazzo; Farzad Mortazavi; Tara L. Moore; Douglas L. Rosene (GeroScience, 2017)

Soil greenhouse gas emissions from agroforestry and other land uses under different moisture regimes in lower Missouri River Floodplain soils: a laboratory approach - B. D. Moore; G. Kaur; P. P. Motavalli; B. A. Zurweller; B. M. Svoma (Agroforestry Systems, 2017)

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

Identifying gene–gene interactions that are highly associated with four quantitative lipid traits across multiple cohorts - Rishika De; Shefali S. Verma; Emily Holzinger; Molly Hall; Amber Burt; David S. Carrell; David R. Crosslin; Gail P. Jarvik; Helena Kuivaniemi; Iftikhar J. Kullo; Leslie A. Lange; Matthew B. Lanktree; et al. (Human Genetics, 2017)

Hemodynamic Performance and Thrombogenic Properties of a Superhydrophobic Bileaflet Mechanical Heart Valve - David L. Bark; Hamed Vahabi; Hieu Bui; Sanli Movafaghi; Brandon Moore; Arun K. Kota; Ketul Popat; Lakshmi P. Dasi (Annals of Biomedical Engineering, 2017)

Entomopathogenic fungi as control agents of Thaumatotibia leucotreta in citrus orchards: field efficacy and persistence - C. A. Coombes; M. P. Hill; S. D. Moore; J. F. Dames (BioControl, 2016)

The comparative analysis of complete genome sequences from two South African betabaculoviruses: Phthorimaea operculella granulovirus and Plutella xylostella granulovirus - M. D. Jukes; B. M. Motsoeneng; C. M. Knox; M. P. Hill; S. D. Moore (Archives of Virology, 2016)

Comparative genomic, proteomic and exoproteomic analyses of three Pseudomonas strains reveals novel insights into the phosphorus scavenging capabilities of soil bacteria - Ian D. E. A. Lidbury; Andrew R. J. Murphy; David J. Scanlan; Gary D. Bending; Alexandra M. E. Jones; Jonathan D. Moore; Andrew Goodall; John P. Hammond; Elizabeth M. H. Wellington (Environmental Microbiology, 2016)
Summary Bacteria that inhabit the rhizosphere of agricultural crops can have a beneficial effect on crop growth. One such mechanism is the microbial‐driven solubilization and remineralization of complex forms of phosphorus (P). It is known that bacteria secrete various phosphatases in response to low P conditions. However, our understanding of their global proteomic response to P stress is limited. Here, exoproteomic analysis of Pseudomonas putida BIRD‐1 (BIRD‐1), Pseudomonas fluorescens SBW25 and Pseudomonas stutzeri DSM4166 was performed in unison with whole‐cell proteomic analysis of BIRD‐1 grown under phosphate (Pi) replete and Pi deplete conditions. Comparative exoproteomics revealed marked heterogeneity in the exoproteomes of each Pseudomonas strain in response to Pi depletion. In addition to well‐characterized members of the PHO regulon such as alkaline phosphatases, several proteins, previously not associated with the response to Pi depletion, were also identified. These included putative nucleases, phosphotriesterases, putative phosphonate transporters and outer membrane proteins. Moreover, in BIRD‐1, mutagenesis of the master regulator, phoBR , led us to confirm the addition of several novel PHO‐dependent proteins. Our data expands knowledge of the Pseudomonas PHO regulon, including species that are frequently used as bioinoculants, opening up the potential for more efficient and complete use of soil complexed P.

Recent Scientific Publications Cast Doubt on North Atlantic Right Whale Future - Scott D. Kraus; Robert D. Kenney; Charles A. Mayo; William A. McLellan; Michael J. Moore; Douglas P. Nowacek (Frontiers in Marine Science, 2016)

Controls over Ocean Mesopelagic Interior Carbon Storage (COMICS): Fieldwork, Synthesis, and Modeling Efforts - Richard J. Sanders; Stephanie A. Henson; Adrian P. Martin; Tom R. Anderson; Raffaele Bernardello; Peter Enderlein; Sophie Fielding; Sarah L. C. Giering; Manuela Hartmann; Morten Iversen; Samar Khatiwala; Phyllis Lam; et al. (Frontiers in Marine Science, 2016)

The effect of vigorous running and cycling on serum COMP, lubricin, and femoral cartilage thickness: a pilot study - Harry M. Roberts; Jonathan P. Moore; Claire L. Griffith-McGeever; Matthew B. Fortes; Jeanette M. Thom (European Journal of Applied Physiology, 2016)

The impact of ethnicity/race on the association between the Veterans Aging Cohort Study (VACS) Index and neurocognitive function among HIV-infected persons - M. J. Marquine; M. Sakamoto; C. Dufour; A. Rooney; P. Fazeli; A. Umlauf; B. Gouaux; D. Franklin; R. Ellis; S. Letendre; M. Cherner; R. K. Heaton; et al. (Journal of NeuroVirology, 2016)

Heterogeneity in virulence relationships between Cryptophlebia leucotreta granulovirus isolates and geographically distinct host populations: lessons from codling moth resistance to CpGV-M - John K. Opoku-Debrah; Martin P. Hill; Caroline Knox; Sean D. Moore (BioControl, 2016)

Natal philopatry varies with larval condition in salamanders - Michael P. Moore; Howard H. Whiteman (Behavioral Ecology and Sociobiology, 2016)

Highly heritable resistance to root-lesion nematode (Pratylenchus thornei) in Australian chickpea germplasm observed using an optimised glasshouse method and multi-environment trial analysis - M. S. Rodda; K. B. Hobson; C. R. Forknall; R. P. Daniel; J. P. Fanning; D. D. Pounsett; S. Simpfendorfer; K. J. Moore; K. J. Owen; J. G. Sheedy; J. P. Thompson; G. J. Hollaway; et al. (Australasian Plant Pathology, 2016)

The effects of resistance exercise training on arterial stiffness in metabolic syndrome - E. DeVallance; S. Fournier; K. Lemaster; C. Moore; S. Asano; D. Bonner; D. Donley; I. M. Olfert; P. D. Chantler (European Journal of Applied Physiology, 2016)

Antibiotics as CECs: An Overview of the Hazards Posed by Antibiotics and Antibiotic Resistance - Geoffrey I. Scott; Dwayne E. Porter; R. Sean Norman; C. Hart Scott; Miguel I. Uyaguari-Diaz; Keith A. Maruya; Steve B. Weisberg; Michael H. Fulton; Ed F. Wirth; Janet Moore; Paul L. Pennington; Daniel Schlenk; et al. (Frontiers in Marine Science, 2016)

A preliminary study on the movements of smelt, O smerus eperlanus , in two E ast A nglian rivers - A. Moore; M. Ives; P. Davison; L. Privitera (Fisheries Management and Ecology, 2016)

Rock geochemistry induces stress and starvation responses in the bacterial proteome - Casey C. Bryce; Thierry Le Bihan; Sarah F. Martin; Jesse P. Harrison; Timothy Bush; Bryan Spears; Alanna Moore; Natalie Leys; Bo Byloos; Charles S. Cockell (Environmental Microbiology, 2016)
Summary Interactions between microorganisms and rocks play an important role in Earth system processes. However, little is known about the molecular capabilities microorganisms require to live in rocky environments. Using a quantitative label‐free proteomics approach, we show that a model bacterium ( C upriavidus metallidurans CH 34) can use volcanic rock to satisfy some elemental requirements, resulting in increased rates of cell division in both magnesium‐ and iron‐limited media. However, the rocks also introduced multiple new stresses via chemical changes associated with pH , elemental leaching and surface adsorption of nutrients that were reflected in the proteome. For example, the loss of bioavailable phosphorus was observed and resulted in the upregulation of diverse phosphate limitation proteins, which facilitate increase phosphate uptake and scavenging within the cell. Our results revealed that despite the provision of essential elements, rock chemistry drives complex metabolic reorganization within rock‐dwelling organisms, requiring tight regulation of cellular processes at the protein level. This study advances our ability to identify key microbial responses that enable life to persist in rock environments.

The predictability and magnitude of life‐history divergence to ecological agents of selection: a meta‐analysis in livebearing fishes - Michael P. Moore; Rüdiger Riesch; Ryan A. Martin (Ecology Letters, 2016)
Environments causing variation in age‐specific mortality – ecological agents of selection – mediate the evolution of reproductive life‐history traits. However, the relative magnitude of life‐history divergence across selective agents, whether divergence in response to specific selective agents is consistent across taxa and whether it occurs as predicted by theory, remains largely unexplored. We evaluated divergence in offspring size, offspring number, and the trade‐off between these traits using a meta‐analysis in livebearing fishes (Poeciliidae). Life‐history divergence was consistent and predictable to some (predation, hydrogen sulphide) but not all (density, food limitation, salinity) selective agents. In contrast, magnitudes of divergence among selective agents were similar. Finally, there was a negative, asymmetric relationship between offspring‐number and offspring‐size divergence, suggesting greater costs of increasing offspring size than number. Ultimately, these results provide strong evidence for predictable and consistent patterns of reproductive life‐history divergence and highlight the importance of comparing phenotypic divergence across species and ecological selective agents.

Characterization of the peptide binding specificity of the HLA class I alleles B*38:01 and B*39:06 - John Sidney; Jennifer Schloss; Carrie Moore; Mikaela Lindvall; Amanda Wriston; Donald F. Hunt; Jeffrey Shabanowitz; Teresa P. DiLorenzo; Alessandro Sette (Immunogenetics, 2016)

Coastal Vertebrate Exposure to Predicted Habitat Changes Due to Sea Level Rise - Elizabeth A. Hunter; Nathan P. Nibbelink; Clark R. Alexander; Kyle Barrett; Lara F. Mengak; Rachel K. Guy; Clinton T. Moore; Robert J. Cooper (Environmental Management, 2015)

Dimercaptopropane Sulfonate Chelation Affects In Vivo Hg and MeHg Distribution in Tissues and Urine of Prairie Voles (Microtus ochrogaster) - G. P. Cobb; A. W. Moore; K. T. Rummel; S. T. McMurry (Bulletin of Environmental Contamination and Toxicology, 2015)

Prioritization of knowledge needs for sustainable aquaculture: a national and global perspective - Aisla C Jones; Angela Mead; Michel J Kaiser; Melanie C V Austen; Alex W Adrian; Neil A Auchterlonie; Kenneth D Black; Lucy R Blow; Charlotte Bury; Janet H Brown; Gavin M Burnell; Elaine Connolly; et al. (Fish and Fisheries, 2015)
Aquaculture is currently the fastest expanding global animal food production sector and is a key future contributor to food security. An increase in food security will be dependent upon the development and improvement of sustainable practices. A prioritization exercise was undertaken, focusing on the future knowledge needs to underpin UK sustainable aquaculture (both domestic and imported products) using a ‘task force’ group of 36 ‘practitioners’ and 12 ‘research scientists’ who have an active interest in sustainable aquaculture. A long list of 264 knowledge needs related to sustainable aquaculture was developed in conjunction with the task force. The long list was further refined through a three stage process of voting and scoring, including discussions of each knowledge need. The top 25 knowledge needs are presented, as scored separately by ‘practitioners’ or ‘research scientists’. There was similar agreement in priorities identified by these two groups. The priority knowledge needs will provide guidance to structure ongoing work to make science accessible to practitioners and help to prioritize future science policy needs and funding. The process of knowledge exchange, and the mechanisms by which this can be achieved, effectively emerged as the top priority for sustainable aquaculture. Viable alternatives to wild fish‐based aquaculture feeds, resource constraints that will potentially limit expansion of aquaculture, sustainable offshore aquaculture and the treatment of sea lice also emerged as strong priorities. Although the exercise was focused on UK needs for sustainable aquaculture, many of the emergent issues are considered to have global application.

An experimental test for age-related improvements in reproductive performance in a frog that cares for its young - Matthew B. Dugas; Michael P. Moore; Caitlin N. Wamelink; Corinne L. Richards-Zawacki; Ryan A. Martin (The Science of Nature, 2015)

Agathis bishopi (Hymenoptera: Braconidae) as a Potential Tool for Detecting Oranges Infested with Thaumatotibia leucotreta (Lepidoptera: Tortricidae) - Kennedy Zimba; Martin P. Hill; Sean D. Moore; Unathi Heshula (Journal of Insect Behavior, 2015)

Restoration using Acropora cervicornis at the T/V MARGARA grounding site - S. P. Griffin; M. I. Nemeth; T. D. Moore; B. Gintert (Coral Reefs, 2015)

Maternal investment mediates offspring life history variation with context‐dependent fitness consequences - Michael P. Moore; Tobias Landberg; Howard H. Whiteman (Ecology, 2015)
Maternal effects, such as per capita maternal investment, often interact with environmental conditions to strongly affect traits expressed early in ontogeny. However, their impact on adult life history traits and fitness components is relatively unknown. Theory predicts that lower per capita maternal investment will have strong fitness costs when the offspring develop in unfavorable conditions, yet few studies have experimentally manipulated per capita maternal investment and followed offspring through adulthood. We used a surgical embryonic yolk removal technique to investigate how per capita maternal investment interacted with an important ecological factor, larval density, to mediate offspring life history traits through reproductive maturity in an amphibian, Ambystoma talpoideum . We predicted that increased larval density would reinforce the life history variation induced by differences in per capita investment (i.e., Controls vs. Reduced Yolk), with Reduced larvae ultimately expressing traits associated with lower fitness than Controls when raised at high densities. We found that Reduced individuals were initially smaller and more developed, caught up in size to Controls within the first month of the larval stage, but were smaller at the end of the larval stage in low densities. Reduced individuals also were more likely to undergo metamorphosis at high densities and mature females invested in more eggs for their body sizes than Controls. Together, our results do not support our hypothesis, but instead indicate that Reduced individuals express traits associated with higher fitness when they develop in high‐density environments, but lower fitness in low‐density environments. The observed life history and fitness patterns are consistent with the “maternal match” hypothesis, which predicts that when the maternal environment (e.g., high density) results in phenotypic variation that is transmitted to the offspring (e.g., reduced per capita yolk investment), and offspring face that same environment (e.g., high larval density), the fitness of both mother and offspring is maximized.

Comparison of low-carbon pathways for California - Geoffrey M. Morrison; Sonia Yeh; Anthony R. Eggert; Christopher Yang; James H. Nelson; Jeffery B. Greenblatt; Raphael Isaac; Mark Z. Jacobson; Josiah Johnston; Daniel M. Kammen; Ana Mileva; Jack Moore; et al. (Climatic Change, 2015)

Genetic and biological characterisation of a novel Plutella xylostella granulovirus, PlxyGV-SA - Fatima Abdulkadir; Caroline Knox; Tamryn Marsberg; Martin P. Hill; Sean D. Moore (BioControl, 2015)

Future habitat loss and extinctions driven by land‐use change in biodiversity hotspots under four scenarios of climate‐change mitigation - Samuel M. Jantz; Brian Barker; Thomas M. Brooks; Louise P. Chini; Qiongyu Huang; Rachel M. Moore; Jacob Noel; George C. Hurtt (Conservation Biology, 2015)
Numerous species have been pushed into extinction as an increasing portion of Earth's land surface has been appropriated for human enterprise. In the future, global biodiversity will be affected by both climate change and land‐use change, the latter of which is currently the primary driver of species extinctions. How societies address climate change will critically affect biodiversity because climate‐change mitigation policies will reduce direct climate‐change impacts; however, these policies will influence land‐use decisions, which could have negative impacts on habitat for a substantial number of species. We assessed the potential impact future climate policy could have on the loss of habitable area in biodiversity hotspots due to associated land‐use changes. We estimated past extinctions from historical land‐use changes (1500–2005) based on the global gridded land‐use data used for the Intergovernmental Panel on Climate Change Fifth Assessment Report and habitat extent and species data for each hotspot. We then estimated potential extinctions due to future land‐use changes under alternative climate‐change scenarios (2005–2100). Future land‐use changes are projected to reduce natural vegetative cover by 26‐58% in the hotspots. As a consequence, the number of additional species extinctions, relative to those already incurred between 1500 and 2005, due to land‐use change by 2100 across all hotspots ranged from about 220 to 21000 (0.2% to 16%), depending on the climate‐change mitigation scenario and biological factors such as the slope of the species–area relationship and the contribution of wood harvest to extinctions. These estimates of potential future extinctions were driven by land‐use change only and likely would have been higher if the direct effects of climate change had been considered. Future extinctions could potentially be reduced by incorporating habitat preservation into scenario development to reduce projected future land‐use changes in hotspots or by lessening the impact of future land‐use activities on biodiversity within hotspots.

Changes in soil biogeochemistry following disturbance by girdling and mountain pine beetles in subalpine forests - Nicole A. Trahan; Emily L. Dynes; Evan Pugh; David J. P. Moore; Russell K. Monson (Oecologia, 2015)

Genome-wide methylation analysis in Silver–Russell syndrome patients - A. R. Prickett; M. Ishida; S. Böhm; J. M. Frost; W. Puszyk; S. Abu-Amero; P. Stanier; R. Schulz; G. E. Moore; R. J. Oakey (Human Genetics, 2015)

Identifying best methods for routine ELISA detection of microcystin in seafood - Ellen P. Preece; Barry C. Moore; Mark E. Swanson; F. Joan Hardy (Environmental Monitoring and Assessment, 2015)

Emergent stability in a large, free‐flowing watershed - Jonathan W. Moore; Michael P. Beakes; Holly K. Nesbitt; Justin D. Yeakel; David A. Patterson; Lisa A. Thompson; Corey C. Phillis; Douglas C. Braun; Corinna Favaro; David Scott; Charmaine Carr-Harris; William I. Atlas (Ecology, 2015)
While it is widely recognized that financial stock portfolios can be stabilized through diverse investments, it is also possible that certain habitats can function as natural portfolios that stabilize ecosystem processes. Here we propose and examine the hypothesis that free‐flowing river networks act as such portfolios and confer stability through their integration of upstream geological, hydrological, and biological diversity. We compiled a spatially (142 sites) and temporally (1980–present) extensive data set on fisheries, water flows, and temperatures, from sites within one of the largest watersheds in the world that remains without dams on its mainstem, the Fraser River, British Columbia, Canada. We found that larger catchments had more stable fisheries catches, water flows, and water temperatures than smaller catchments. These data provide evidence that free‐flowing river networks function as hierarchically nested portfolios with stability as an emergent property. Thus, free‐flowing river networks can represent a natural system for buffering variation and extreme events.

Fragmented Tasmania: the transition from Rodinia to Gondwana - D. H. Moore; P. G. Betts; M. Hall (Australian Journal of Earth Sciences, 2015)

Comparative migratory behavior and survival of wild and hatchery steelhead (Oncorhynchus mykiss) smolts in riverine, estuarine, and marine habitats of Puget Sound, Washington - Fred A. Goetz; Eric Jeanes; Megan E. Moore; Thomas P. Quinn (Environmental Biology of Fishes, 2015)

Fire in Australian savannas: from leaf to landscape - Jason Beringer; Lindsay B. Hutley; David Abramson; Stefan K. Arndt; Peter Briggs; Mila Bristow; Josep G. Canadell; Lucas A. Cernusak; Derek Eamus; Andrew C. Edwards; Bradley J. Evans; Benedikt Fest; et al. (Global Change Biology, 2015)
Savanna ecosystems comprise 22% of the global terrestrial surface and 25% of Australia (almost 1.9 million km 2 ) and provide significant ecosystem services through carbon and water cycles and the maintenance of biodiversity. The current structure, composition and distribution of Australian savannas have coevolved with fire, yet remain driven by the dynamic constraints of their bioclimatic niche. Fire in Australian savannas influences both the biophysical and biogeochemical processes at multiple scales from leaf to landscape. Here, we present the latest emission estimates from Australian savanna biomass burning and their contribution to global greenhouse gas budgets. We then review our understanding of the impacts of fire on ecosystem function and local surface water and heat balances, which in turn influence regional climate. We show how savanna fires are coupled to the global climate through the carbon cycle and fire regimes. We present new research that climate change is likely to alter the structure and function of savannas through shifts in moisture availability and increases in atmospheric carbon dioxide, in turn altering fire regimes with further feedbacks to climate. We explore opportunities to reduce net greenhouse gas emissions from savanna ecosystems through changes in savanna fire management.

SNP characteristics predict replication success in association studies - Ivan P. Gorlov; Jason H. Moore; Bo Peng; Jennifer L. Jin; Olga Y. Gorlova; Christopher I. Amos (Human Genetics, 2014)

Littoral and benthic macroinvertebrate community responses to contrasting stressors in a large New Zealand river - Kevin J Collier; Mark P Hamer; Stephen C Moore (New Zealand Journal of Marine and Freshwater Research, 2014)
Large rivers present major challenges for biomonitoring and the development of biocriteria because of difficulties obtaining samples representative of the range of habitats present and a paucity of information on taxa responses to environmental conditions. We sampled littoral and deepwater benthic habitats to investigate macroinvertebrate community composition associated with organic, sediment and heated water discharges at 22 transects along a 73 km section of the lower Waikato River, North Island, New Zealand. Significant community differences in near‐field exposure versus no exposure sites were found only in littoral habitats, partly reflecting changes in relative abundances of Crustacea and Oligochaeta. Littoral and benthic habitats supported different macroinvertebrate communities, particularly downstream of the sediment input and following the onset of a river‐floodplain morphology which may have enhanced deposition of suspended sediment. Distance down river was a significant covariate for most metrics derived from benthic samples, but did not influence the relative abundance of most macroinvertebrate groups in littoral samples. Collectively, these results suggest that littoral habitats are likely to be more suitable than benthic habitats for biomonitoring since macroinvertebrate faunas were responsive to near‐field stressor exposure and were less likely to be influenced by longitudinal changes in river conditions.

Snapshot of Vibrio parahaemolyticus densities in open and closed shellfish beds in Coastal South Carolina and Mississippi - J. Gooch Moore; A. Ruple; K. Ballenger-Bass; S. Bell; P. L. Pennington; G. I. Scott (Environmental Monitoring and Assessment, 2014)

The unique trace metal and mixed layer conditions of the Costa Rica upwelling dome support a distinct and dense community of Synechococcus - Nathan A. Ahlgren; Abigail Noble; Allison P. Patton; Kathryn Roache‐Johnson; Laurel Jackson; Daniela Robinson; Cedar McKay; Lisa R. Moore; Mak A. Saito; Gabrielle Rocap (Limnology and Oceanography, 2014)
The Costa Rica Dome (CRD) is a wind‐driven upwelling feature in the eastern tropical Pacific that supports unusually high concentrations (> 10 6 cells mL −1 ) of the picocyanobacteria Prochlorococcus and Synechococcus . To understand what causes this unusual phytoplankton bloom, we conducted a comprehensive survey of the hydrography, picophytoplankton population structure, and trace metal chemistry of the CRD and surrounding oligotrophic and equatorial upwelling waters. Based on size‐fractionated chlorophyll, picoplankton dominated phytoplankton biomass in the region, and the three water regimes sampled supported different assemblages of Prochlorococcus , Synechococcus , and eukaryotic picophytoplankton. Cobalt (Co), a required nutrient for cyanobacteria, was strongly complexed in surface waters and was at least twice as high in the photic zone of the CRD than in surrounding waters. In contrast, iron (Fe) and manganese (Mn) levels were comparable in and outside the CRD. Synechococcus clades II and CRD1 and Prochlorococcus ecotype eMIT9312 (high light II) were the dominant genotypes throughout the region, as assessed by quantitative polymerase chain reaction assays. The composition of less abundant Synechococcus clade subpopulations differed in and outside the CRD and within the CRD. Co, mixed layer depth, and temperature were the important drivers of both total Synechococcus abundance and cyanobacterial community composition. This supports a model whereby the combination of upwelled macronutrients, high concentrations of complexed Co, and Fe and Mn scarcity in the warm, shallow mixed layer of the CRD limit larger phytoplankton and induce dense concentrations of picocyanobacteria. Globally, we suggest that trace metals influence phytoplankton distributions at both the broad (cyanobacterial vs. eukaryotic) and the fine (ecotype‐level) taxonomic levels.

A tree-ring perspective on the terrestrial carbon cycle - Flurin Babst; M. Ross Alexander; Paul Szejner; Olivier Bouriaud; Stefan Klesse; John Roden; Philippe Ciais; Benjamin Poulter; David Frank; David J. P. Moore; Valerie Trouet (Oecologia, 2014)

Establishment and Short-term Productivity of Annual and Perennial Bioenergy Crops Across a Landscape Gradient - Danielle M. Wilson; Emily A. Heaton; Lisa A. Schulte; Theodore P. Gunther; Monika E. Shea; Richard B. Hall; William Landon Headlee; Kenneth J. Moore; Nicholas N. Boersma (BioEnergy Research, 2014)

Curcumin analogue UBS109 prevents bone loss in breast cancer bone metastasis mouse model: involvement in osteoblastogenesis and osteoclastogenesis - Masayoshi Yamaguchi; Shijun Zhu; Shumin Zhang; Daqing Wu; Terry M. Moore; James P. Snyder; Mamoru Shoji (Cell and Tissue Research, 2014)

A synthesis of methane emissions from 71 northern, temperate, and subtropical wetlands - Merritt R. Turetsky; Agnieszka Kotowska; Jill Bubier; Nancy B. Dise; Patrick Crill; Ed R. C. Hornibrook; Kari Minkkinen; Tim R. Moore; Isla H. Myers‐Smith; Hannu Nykänen; David Olefeldt; Janne Rinne; et al. (Global Change Biology, 2014)
Wetlands are the largest natural source of atmospheric methane. Here, we assess controls on methane flux using a database of approximately 19 000 instantaneous measurements from 71 wetland sites located across subtropical, temperate, and northern high latitude regions. Our analyses confirm general controls on wetland methane emissions from soil temperature, water table, and vegetation, but also show that these relationships are modified depending on wetland type (bog, fen, or swamp), region (subarctic to temperate), and disturbance. Fen methane flux was more sensitive to vegetation and less sensitive to temperature than bog or swamp fluxes. The optimal water table for methane flux was consistently below the peat surface in bogs, close to the peat surface in poor fens, and above the peat surface in rich fens. However, the largest flux in bogs occurred when dry 30‐day averaged antecedent conditions were followed by wet conditions, while in fens and swamps, the largest flux occurred when both 30‐day averaged antecedent and current conditions were wet. Drained wetlands exhibited distinct characteristics, e.g. the absence of large flux following wet and warm conditions, suggesting that the same functional relationships between methane flux and environmental conditions cannot be used across pristine and disturbed wetlands. Together, our results suggest that water table and temperature are dominant controls on methane flux in pristine bogs and swamps, while other processes, such as vascular transport in pristine fens, have the potential to partially override the effect of these controls in other wetland types. Because wetland types vary in methane emissions and have distinct controls, these ecosystems need to be considered separately to yield reliable estimates of global wetland methane release.

Use of the recommended drug combination for secondary prevention after a first occurrence of acute coronary syndrome in France - J. Bezin; A. Pariente; R. Lassalle; C. Dureau-Pournin; A. Abouelfath; P. Robinson; N. Moore; C. Droz-Perroteau; A. Fourrier-Reglat (European Journal of Clinical Pharmacology, 2014)

Synchronisation and stability in river metapopulation networks - J. D. Yeakel; J. W. Moore; P. R. Guimarães; M. A. M. de Aguiar (Ecology Letters, 2014)
Spatial structure in landscapes impacts population stability. Two linked components of stability have large consequences for persistence: first, statistical stability as the lack of temporal fluctuations; second, synchronisation as an aspect of dynamic stability, which erodes metapopulation rescue effects. Here, we determine the influence of river network structure on the stability of riverine metapopulations. We introduce an approach that converts river networks to metapopulation networks, and analytically show how fluctuation magnitude is influenced by interaction structure. We show that river metapopulation complexity (in terms of branching prevalence) has nonlinear dampening effects on population fluctuations, and can also buffer against synchronisation. We conclude by showing that river transects generally increase synchronisation, while the spatial scale of interaction has nonlinear effects on synchronised dynamics. Our results indicate that this dual stability – conferred by fluctuation and synchronisation dampening – emerges from interaction structure in rivers, and this may strongly influence the persistence of river metapopulations.

Phenological responses of juvenile pecan and white oak on an upland site - D. M. Burner; D. K. Brauer; J. L. Snider; C. A. Harrington; P. A. Moore (Agroforestry Systems, 2014)

Using scale characteristics and water temperature to reconstruct growth rates of juvenile steelhead Oncorhynchus mykiss - M. P. Beakes; S. Sharron; R. Charish; J. W. Moore; W. H. Satterthwaite; E. Sturm; B. K. Wells; S. M. Sogard; M. Mangel (Journal of Fish Biology, 2014)
Juvenile steelhead Oncorhynchus mykiss from a northern California Central Valley population were reared in a controlled laboratory experiment. Significantly different rates of growth were observed among fish reared under two ration treatments and three temperature treatments (8, 14 and 20° C). Wider circulus spacing and faster deposition was associated with faster growth. For the same growth rate, however, circulus spacing was two‐fold wider and deposited 36% less frequently in the cold compared to the hot temperature treatment. In a multiple linear regression, median circulus spacing and water temperature accounted for 68% of the variation in observed O. mykiss growth. These results corroborate previous research on scale characteristics and growth, while providing novel evidence that highlights the importance of water temperature in these relationships. Thus, this study establishes the utility of using scale analysis as a relatively non‐invasive method for inferring growth in salmonids.

A new method for producing transgenic birds via direct in vivo transfection of primordial germ cells - Scott G. Tyack; Kristie A. Jenkins; Terri E. O’Neil; Terry G. Wise; Kirsten R. Morris; Matthew P. Bruce; Scott McLeod; Alexander J. Wade; James McKay; Robert J. Moore; Karel A. Schat; John W. Lowenthal; et al. (Transgenic Research, 2013)

Predicting invasion in grassland ecosystems: is exotic dominance the real embarrassment of richness? - Eric W. Seabloom; Elizabeth T. Borer; Yvonne Buckley; Elsa E. Cleland; Kendi Davies; Jennifer Firn; W. Stanley Harpole; Yann Hautier; Eric Lind; Andrew MacDougall; John L. Orrock; Suzanne M. Prober; et al. (Global Change Biology, 2013)
Invasions have increased the size of regional species pools, but are typically assumed to reduce native diversity. However, global‐scale tests of this assumption have been elusive because of the focus on exotic species richness, rather than relative abundance. This is problematic because low invader richness can indicate invasion resistance by the native community or, alternatively, dominance by a single exotic species. Here, we used a globally replicated study to quantify relationships between exotic richness and abundance in grass‐dominated ecosystems in 13 countries on six continents, ranging from salt marshes to alpine tundra. We tested effects of human land use, native community diversity, herbivore pressure, and nutrient limitation on exotic plant dominance. Despite its widespread use, exotic richness was a poor proxy for exotic dominance at low exotic richness, because sites that contained few exotic species ranged from relatively pristine (low exotic richness and cover) to almost completely exotic‐dominated ones (low exotic richness but high exotic cover). Both exotic cover and richness were predicted by native plant diversity (native grass richness) and land use (distance to cultivation). Although climate was important for predicting both exotic cover and richness, climatic factors predicting cover (precipitation variability) differed from those predicting richness (maximum temperature and mean temperature in the wettest quarter). Herbivory and nutrient limitation did not predict exotic richness or cover. Exotic dominance was greatest in areas with low native grass richness at the site‐ or regional‐scale. Although this could reflect native grass displacement, a lack of biotic resistance is a more likely explanation, given that grasses comprise the most aggressive invaders. These findings underscore the need to move beyond richness as a surrogate for the extent of invasion, because this metric confounds monodominance with invasion resistance. Monitoring species' relative abundance will more rapidly advance our understanding of invasions.

Detection of antibodies against Brucella abortus, Leptospira spp., and Apicomplexa protozoa in water buffaloes in the Northeast of Argentina - José L. Konrad; Lucía M. Campero; Gastón S. Caspe; Bibiana Brihuega; Graciela Draghi; Dadin P. Moore; Gustavo A. Crudeli; María C. Venturini; Carlos M. Campero (Tropical Animal Health and Production, 2013)

First report of seroprevalence of Toxoplasma gondii and Neospora caninum in dairy sheep from Humid Pampa, Argentina - Yanina P. Hecker; Dadín P. Moore; Jorge A. Manazza; Juan M. Unzaga; Ernesto J. A. Späth; Lais L. Pardini; María C. Venturini; José L. Roberi; Carlos M. Campero (Tropical Animal Health and Production, 2013)

Three nights of sleep deprivation does not alter thermal strain during exercise in the heat - Jonathan P. Moore; Adam D. Harper Smith; Umberto Di Felice; Neil P. Walsh (European Journal of Applied Physiology, 2013)

Evaluation of MODIS surrogates for meteorological humidity data in east Africa - Shengpan Lin; Nathan J. Moore; Joseph P. Messina; Jiaping Wu (International Journal of Remote Sensing, 2013)

Persistent reduced ecosystem respiration after insect disturbance in high elevation forests - David J. P. Moore; Nicole A. Trahan; Phil Wilkes; Tristan Quaife; Britton B. Stephens; Kelly Elder; Ankur R. Desai; Jose Negron; Russell K. Monson (Ecology Letters, 2013)
Amid a worldwide increase in tree mortality, mountain pine beetles ( Dendroctonus ponderosae Hopkins) have led to the death of billions of trees from Mexico to Alaska since 2000. This is predicted to have important carbon, water and energy balance feedbacks on the Earth system. Counter to current projections, we show that on a decadal scale, tree mortality causes no increase in ecosystem respiration from scales of several square metres up to an 84 km 2 valley. Rather, we found comparable declines in both gross primary productivity and respiration suggesting little change in net flux, with a transitory recovery of respiration 6–7 years after mortality associated with increased incorporation of leaf litter C into soil organic matter, followed by further decline in years 8–10. The mechanism of the impact of tree mortality caused by these biotic disturbances is consistent with reduced input rather than increased output of carbon.

Global mapping of storm surges and the assessment of coastal vulnerability - G. R. Brakenridge; J. P. M. Syvitski; I. Overeem; S. A. Higgins; A. J. Kettner; J. A. Stewart-Moore; R. Westerhoff (Natural Hazards, 2013)

Assessing the Risk of Ships Striking Large Whales in Marine Spatial Planning - J. V. REDFERN; M. F. MCKENNA; T. J. MOORE; J. CALAMBOKIDIS; M. L. DEANGELIS; E. A. BECKER; J. BARLOW; K. A. FORNEY; P. C. FIEDLER; S. J. CHIVERS (Conservation Biology, 2013)
Marine spatial planning provides a comprehensive framework for managing multiple uses of the marine environment and has the potential to minimize environmental impacts and reduce conflicts among users. Spatially explicit assessments of the risks to key marine species from human activities are a requirement of marine spatial planning. We assessed the risk of ships striking humpback (Megaptera novaeangliae), blue (Balaenoptera musculus), and fin (Balaenoptera physalus) whales in alternative shipping routes derived from patterns of shipping traffic off Southern California (U.S.A.). Specifically, we developed whale‐habitat models and assumed ship‐strike risk for the alternative shipping routes was proportional to the number of whales predicted by the models to occur within each route. This definition of risk assumes all ships travel within a single route. We also calculated risk assuming ships travel via multiple routes. We estimated the potential for conflict between shipping and other uses (military training and fishing) due to overlap with the routes. We also estimated the overlap between shipping routes and protected areas. The route with the lowest risk for humpback whales had the highest risk for fin whales and vice versa. Risk to both species may be ameliorated by creating a new route south of the northern Channel Islands and spreading traffic between this new route and the existing route in the Santa Barbara Channel. Creating a longer route may reduce the overlap between shipping and other uses by concentrating shipping traffic. Blue whales are distributed more evenly across our study area than humpback and fin whales; thus, risk could not be ameliorated by concentrating shipping traffic in any of the routes we considered. Reducing ship‐strike risk for blue whales may be necessary because our estimate of the potential number of strikes suggests that they are likely to exceed allowable levels of anthropogenic impacts established under U.S. laws. Evaluación del Riesgo de Colisiones de Barcos y Ballenas en la Planificación Marina Espacial

Arabinose-rich polymers as an evolutionary strategy to plasticize resurrection plant cell walls against desiccation - John P. Moore; Eric E. Nguema-Ona; Mäite Vicré-Gibouin; Iben Sørensen; William G.T. Willats; Azeddine Driouich; Jill M. Farrant (Planta, 2013)

Bleaching, coral mortality and subsequent survivorship on a West Australian fringing reef - M. Depczynski; J. P. Gilmour; T. Ridgway; H. Barnes; A. J. Heyward; T. H. Holmes; J. A. Y. Moore; B. T. Radford; D. P. Thomson; P. Tinkler; S. K. Wilson (Coral Reefs, 2013)

Spatial and temporal development of phytoplankton iron stress in relation to bloom dynamics in the high‐latitude North Atlantic Ocean - Thomas J. Ryan-Keogh; Anna I. Macey; Maria C. Nielsdóttir; Michael I. Lucas; Sebastian S. Steigenberger; Mark C. Stinchcombe; Eric P. Achterberg; Thomas S. Bibby; C. Mark Moore (Limnology and Oceanography, 2013)
The high‐latitude North Atlantic (HLNA) is characterized by a marked seasonal phytoplankton bloom, which removes the majority of surface macronutrients. However, incomplete nitrate depletion is frequently observed during summer in the region, potentially reflecting the seasonal development of an iron (Fe) limited phytoplankton community. In order to investigate the seasonal development and spatial extent of iron stress in the HLNA, nutrient addition experiments were performed during the spring (May) and late summer (July and August) of 2010. Grow‐out experiments (48–120 h) confirmed the potential for iron limitation in the region. Short‐term (24 h) incubations further enabled high spatial coverage and mapping of phytoplankton physiological responses to iron addition. The difference in the apparent maximal photochemical yield of photosystem II (PSII) (F v : F m ) between nutrient (iron) amended and control treatments (Δ(F v : F m )) was used as a measure of the relative degree of iron stress. The combined observations indicated variability in the seasonal cycle of iron stress between different regions of the Irminger and Iceland Basins of the HLNA, related to the timing of the annual bloom cycle in contrasting biogeochemical provinces. Phytoplankton iron stress developed during the transition from the prebloom to peak bloom conditions in the HLNA and was more severe for larger cells. Subsequently, iron stress was reduced in regions where macronutrients were depleted following the bloom. Iron availability plays a significant role in the biogeochemistry of the HLNA, potentially lowering the efficiency of one of the strongest biological carbon pumps in the ocean.

Modelling the migratory behaviour of salmonids in relation to environmental and physiological parameters using telemetry data - B. BENDALL; A. MOORE; D. MAXWELL; P. DAVISON; N. EDMONDS; D. ARCHER; D. SOLOMON; V. GREEST; R. WYATT; K. BROAD (Fisheries Management and Ecology, 2012)
Advances in the field of telemetry techniques during the last few decades have greatly expanded our knowledge on migratory behaviour and provided the opportunity to obtain practically useful data for the conservation and management of salmonid populations. However, applying this information to the development of much needed population‐based migration models has been limited. Furthermore, this research has generally been restricted to assessing the role of river flow on fish movement. Models derived from a 6‐year telemetry study on the movements of Atlantic salmon, Salmo salar L., and sea trout, Salmo trutta L., in the River Tyne are presented together with an assessment of counter data from the same river to highlight the importance of additional environmental and physiological parameters in regulating fish movement. The data are discussed in relation to the advantages of telemetry data, the need to develop predictive models, the statistical methods used and the potential direction of future work in this area.

The mammalian gene function resource: the international knockout mouse consortium - Allan Bradley; Konstantinos Anastassiadis; Abdelkader Ayadi; James F. Battey; Cindy Bell; Marie-Christine Birling; Joanna Bottomley; Steve D. Brown; Antje Bürger; Carol J. Bult; Wendy Bushell; Francis S. Collins; et al. (Mammalian Genome, 2012)

Plant pest and disease diagnosis using electronic nose and support vector machine approach - Reza Ghaffari; Jullada Laothawornkitkul; Daciana Iliescu; Evor Hines; Mark Leeson; Richard Napier; Jason P Moore; Nigel D Paul; C Nicholas Hewitt; Jane E Taylor (Journal of Plant Diseases and Protection, 2012)

The Gauss–Listing geopotential value W 0 and its rate from altimetric mean sea level and GRACE - N. Dayoub; S. J. Edwards; P. Moore (Journal of Geodesy, 2012)

Identification of germline genomic copy number variation in familial pancreatic cancer - Wigdan Al-Sukhni; Sarah Joe; Anath C. Lionel; Nora Zwingerman; George Zogopoulos; Christian R. Marshall; Ayelet Borgida; Spring Holter; Aaron Gropper; Sara Moore; Melissa Bondy; Alison P. Klein; et al. (Human Genetics, 2012)

Increased cortical expression of FK506 binding protein-51 in HIV-associated neurocognitive disorders - Virawudh Soontornniyomkij; Ian P. Everall; David J. Moore; Ben Gouaux; Erick T. Tatro; Vadim Gospodarev; Eliezer Masliah; Nicole S. Yin; Harry V. Vinters; Cristian L. Achim (Journal of NeuroVirology, 2012)

Using aerial photography to investigate evidence of feeding by bowhead whales - Julie A. Mocklin; David J. Rugh; Sue E. Moore; Robyn P. Angliss (Marine Mammal Science, 2012)
Aerial photographs were analyzed to investigate the feeding habits of the Bering‐Chukchi‐Beaufort (BCB) population of bowhead whales ( Balaena mysticetus ), particularly epibenthic feeding near Barrow, Alaska. Evidence of epibenthic feeding was based on mud visible on the dorsal surface of whales, resulting from feeding near the seafloor. Other cues used to assess feeding were an open mouth or the presence of feces in photographs. Over 3,600 photographs were analyzed including photos from surveys in spring and late summer and in both the western and eastern Beaufort Sea. Of all the photographs analyzed, 64% were scored as definitively muddy. In spring, ratios ranged from a low of 27% in 2003 to a high of 76% in 2004. When all May sample sets off Barrow were combined (1985, 1986, 2003, 2004), there was a significant difference ( t ‐test, P

A shared MHC supertype motif emerges by convergent evolution in macaques and mice, but is totally absent in human MHC molecules - Alessandro Sette; John Sidney; Scott Southwood; Carrie Moore; Jessica Berry; Courtney Dow; Kate Bradley; Ilka Hoof; Mark G. Lewis; William H. Hildebrand; Curtis P. McMurtrey; Nancy A. Wilson; et al. (Immunogenetics, 2012)

Identification of the peptide-binding motif recognized by the pigtail macaque class I MHC molecule Mane-A1*082:01 (Mane A*0301) - Carrie Moore; John Sidney; A. Michelle English; Amanda Wriston; Donald F. Hunt; Jeffrey Shabanowitz; Scott Southwood; Kate Bradley; Bernard A. P. Lafont; Bianca R. Mothé; Alessandro Sette (Immunogenetics, 2012)

Development of natural growth regimes for hatchery-reared steelhead to reduce residualism, fitness loss, and negative ecological interactions - Barry A. Berejikian; Donald A. Larsen; Penny Swanson; Megan E. Moore; Christopher P. Tatara; William L. Gale; Chris R. Pasley; Brian R. Beckman (Environmental Biology of Fishes, 2012)

Rapid Biomass Quality Determination of Corn Stover Using Near-Infrared Reflectance Spectroscopy - Patrick T. Murphy; Kenneth J. Moore; D. Raj Raman; Robert P. Anex; Steven L. Fales (BioEnergy Research, 2012)

Behavioural and electrophysiological effects of visual paired associate context manipulations during encoding and recognition in younger adults, older adults and older cognitively declined adults - Michael J. Hogan; Joanne P. M. Kenney; Richard A. P. Roche; Michael A. Keane; Jennifer L. Moore; Jochen Kaiser; Robert Lai; Neil Upton (Experimental Brain Research, 2012)

A primer for data assimilation with ecological models using Markov Chain Monte Carlo (MCMC) - J. M. Zobitz; A. R. Desai; D. J. P. Moore; M. A. Chadwick (Oecologia, 2011)

When should we save the most endangered species? - Howard B. Wilson; Liana N Joseph; Alana L. Moore; Hugh P. Possingham (Ecology Letters, 2011)
Ecology Letters (2011) 14 : 886–890 Abstract At the heart of our efforts to protect threatened species, there is a controversial debate about whether to give priority to cost‐effective actions or whether focusing solely on the most endangered species will ultimately lead to preservation of the greatest number of species. By framing this debate within a decision‐analytic framework, we show that allocating resources solely to the most endangered species will typically not minimise the number of extinctions in the long‐term, as this does not account for the risk of less endangered species going extinct in the future. It is only favoured when our planning timeframe is short or we have a long‐term view and we are optimistic about future conditions. Conservation funding tends to be short‐term in nature, which biases allocations to more endangered species. Our work highlights the need to consider resource allocation for biodiversity over the long‐term; ‘preventive conservation’, rather than just short‐term fire‐fighting.

A geological interpretation of the Echuca magnetotelluric survey, Victoria - Z. R. Dennis; D. H. Moore; J. P. Cull (Australian Journal of Earth Sciences, 2011)

Synthesis and characterization of an unsymmetrical cobalt(III) active site analogue of nitrile hydratase - Jennifer K. Angelosante; Lauren M. Schopp; Breia J. Lewis; Amber D. Vitalo; Dustin T. Titus; Rebecca A. Swanson; April N. Stanley; Brendan P. Abolins; Michelle J. Frome; Lisa E. Cooper; David L. Tierney; Curtis Moore; et al. (JBIC Journal of Biological Inorganic Chemistry, 2011)

Nutrient provision increases signalling and protein synthesis in human skeletal muscle after repeated sprints - Vernon G. Coffey; Daniel R. Moore; Nicholas A. Burd; Tracy Rerecich; Trent Stellingwerff; Andrew P. Garnham; Stuart M. Phillips; John A. Hawley (European Journal of Applied Physiology, 2011)

Crustal architecture of central Victoria: results from the 2006 deep crustal reflection seismic survey - R. A. Cayley; R. J. Korsch; D. H. Moore; R. D. Costelloe; A. Nakamura; C. E. Willman; T. J. Rawling; V. J. Morand; P. B. Skladzien; P. J. O'Shea (Australian Journal of Earth Sciences, 2011)

Magnetotelluric survey for undercover structural mapping, Central Victoria - Z. R. Dennis; D. H. Moore; J. P. Cull (Australian Journal of Earth Sciences, 2011)

Dietary exposure of three passerine species to PCDD/DFs from the Chippewa, Tittabawassee, and Saginaw River floodplains, Midland, Michigan, USA - Timothy B. Fredricks; John P. Giesy; Sarah J. Coefield; Rita M. Seston; Melissa M. Haswell; Dustin L. Tazelaar; Patrick W. Bradley; Jeremy N. Moore; Shaun A. Roark; Matthew J. Zwiernik (Environmental Monitoring and Assessment, 2011)

Timings and interactions of skilled musicians - George P. Moore; Jessie Chen (Biological Cybernetics, 2010)

Estimating parameters of a forest ecosystem C model with measurements of stocks and fluxes as joint constraints - Andrew D. Richardson; Mathew Williams; David Y. Hollinger; David J. P. Moore; D. Bryan Dail; Eric A. Davidson; Neal A. Scott; Robert S. Evans; Holly Hughes; John T. Lee; Charles Rodrigues; Kathleen Savage (Oecologia, 2010)

Influence of habitat degradation on fish replenishment - M. I. McCormick; J. A. Y. Moore; P. L. Munday (Coral Reefs, 2010)

The utilization of a Pacific salmon Oncorhynchus nerka subsidy by three populations of charr Salvelinus spp. - K. P. Denton; H. B. Rich; J. W. Moore; T. P. Quinn (Journal of Fish Biology, 2010)
The L F ‐at‐age trajectories differentiated two populations of Dolly Varden charr Salvelinus malma and a population of Arctic charr Salvelinus alpinus from the eastern end of Iliamna Lake, Alaska. Salvelinus malma from the Pedro Bay ponds were the smallest for a given age, followed by Salvelinus alpinus from the lake, and S. malma from the Iliamna River were much larger. The utilization of a large sockeye salmon Oncorhynchus nerka subsidy by the three Salvelinus spp. populations was then investigated by comparing diet data and mixing model (MixSIR) outputs based on carbon and nitrogen stable isotopes. Stomach contents indicated that both S. malma populations fed on O. nerka products, especially eggs and larval Diptera that had scavenged O. nerka carcasses, whereas S. alpinus fed on a variety of prey items such as three‐spined sticklebacks Gasterosteus aculeatus and snails. Stable‐isotope analysis corroborated the diet data; the two S. malma populations incorporated more O. nerka ‐derived nutrients into their tissues than did S. alpinus from the lake, although all populations showed substantial utilization of O. nerka ‐derived resources. Salvelinus alpinus also seemed to be much more omnivorous, as shown by stable‐isotope mixing models, than the S. malma populations. The dramatic differences in growth rate between the two S. malma populations, despite similar trophic patterns, indicate that other important genetic or environmental factors affect their life history, including proximate temperature controls and ultimate predation pressures.

The effects of farming system, habitat type and bait type on the isolation of entomopathogenic fungi from citrus soils in the Eastern Cape Province, South Africa - T. A. Goble; J. F. Dames; M. P Hill; S. D. Moore (BioControl, 2010)

Evidence for indirect effects of plant diversity and composition on net nitrification - Daniel C. Laughlin; Stephen C. Hart; Jason P. Kaye; Margaret M. Moore (Plant and Soil, 2010)

Single receiver phase ambiguity resolution with GPS data - Willy Bertiger; Shailen D. Desai; Bruce Haines; Nate Harvey; Angelyn W. Moore; Susan Owen; Jan P. Weiss (Journal of Geodesy, 2010)

Biofluid Mechanics of Special Organs and the Issue of System Control - Mair Zamir; James E. Moore; Hideki Fujioka; Donald P. Gaver (Annals of Biomedical Engineering, 2010)

Powering an Implantable Minipump with a Multi-layered Printed Circuit Coil for Drug Infusion Applications in Rodents - Tina K. Givrad; Jean-Michel I. Maarek; William H. Moore; Daniel P. Holschneider (Annals of Biomedical Engineering, 2010)

Synthesis of Upper Mississippi River System submersed and emergent aquatic vegetation: past, present, and future - Megan Moore; Susan P. Romano; Thad Cook (Hydrobiologia, 2010)

Longer growing seasons lead to less carbon sequestration by a subalpine forest - JIA HU; DAVID J. P. MOORE; SEAN P. BURNS; RUSSELL K. MONSON (Global Change Biology, 2010)
As global temperatures increase, the potential for longer growing seasons to enhance the terrestrial carbon sink has been proposed as a mechanism to reduce the rate of further warming. At the Niwot Ridge AmeriFlux site, a subalpine forest in the Colorado Rocky Mountains, we used a 9‐year record (1999–2007) of continuous eddy flux observations to show that longer growing season length (GSL) actually resulted in less annual CO 2 uptake. Years with a longer GSL were correlated with a shallower snow pack, as measured using snow water equivalent (SWE). Furthermore, years with a lower SWE correlated with an earlier start of spring. For three years, 2005, 2006, and 2007, we used observations of stable hydrogen isotopes ( δ D) of snow vs. rain, and extracted xylem water from the three dominant tree species, lodgepole pine, Engelmann spruce, and subalpine fir, to show that the trees relied heavily on snow melt water even late into the growing season. By mid‐August, 57% to 68% of xylem water reflected the isotopic signature of snow melt. By coupling the isotopic water measurements with an ecosystem model, SIPNET, we found that annual forest carbon uptake was highly dependent on snow water, which decreases in abundance during years with longer growing seasons. Once again, for the 3 years 2005, 2006, and 2007, annual gross primary productivity, which was derived as an optimized parameter from the SIPNET model was estimated to be 67% 77%, and 71% dependent on snow melt water, respectively. Past studies have shown that the mean winter snow pack in mountain ecosystems of the Western US has been declining for decades and is correlated with positive winter temperature anomalies. Since climate change models predict continuation of winter warming and reduced snow in mountains of the Western US, the strength of the forest carbon sink is likely to decline further.

Optical tools for ocean monitoring and research - C. Moore; A. Barnard; P. Fietzek; M. R. Lewis; H. M. Sosik; S. White; O. Zielinski (Ocean Science, 2009)
Requirements for understanding the relationships between ocean color and suspended and dissolved materials within the water column, and a rapidly emerging photonics and materials technology base for performing optical based analytical techniques have generated a diverse offering of commercial sensors and research prototypes that perform optical measurements in water. Through inversion, these tools are now being used to determine a diverse set of related biogeochemical and physical parameters. Techniques engaged include measurement of the solar radiance distribution, absorption, scattering, stimulated fluorescence, flow cytometry, and various spectroscopy methods. Selective membranes and other techniques for material isolation further enhance specificity, leading to sensors for measurement of dissolved oxygen, methane, carbon dioxide, common nutrients and a variety of other parameters. Scientists are using these measurements to infer information related to an increasing set of parameters and wide range of applications over relevant scales in space and time.

Relative importance and chemical effects of diffuse and focused recharge in an eogenetic karst aquifer: an example from the unconfined upper Floridan aquifer, USA - M. Ritorto; E. J. Screaton; J. B. Martin; P. J. Moore (Hydrogeology Journal, 2009)

Hepatic P450 Enzyme Activity, Tissue Morphology and Histology of Mink (Mustela vison) Exposed to Polychlorinated Dibenzofurans - Jeremy N. Moore; John L. Newsted; Markus Hecker; Matthew J. Zwiernik; Scott D. Fitzgerald; Denise P. Kay; Xiaowei Zhang; Eric B. Higley; Lesa L. Aylward; Kerrie J. Beckett; Robert A. Budinsky; Steven J. Bursian; et al. (Archives of Environmental Contamination and Toxicology, 2009)

Afternoons with Segundo - George P. Moore (Biological Cybernetics, 2009)

Predicting impacts of climate‐induced range expansion: an experimental framework and a test involving key grazers on temperate rocky shores - LOUISE B. FIRTH; TASMAN P. CROWE; PIPPA MOORE; RICHARD C. THOMPSON; STEPHEN J. HAWKINS (Global Change Biology, 2009)
Climate change has strong potential to modify the structure and functioning of ecosystems, but experimental field studies into its effects are rare. On rocky shores, grazing limpets strongly affect ecosystem structure and their distribution in NW Europe is changing in response to climate change. Three limpet species co‐occur in SW Britain ( Patella vulgata, Patella ulyssiponensis and Patella depressa ) on open rock and in pools. Shores in Ireland are similar, but currently lack P. depressa . It is anticipated that P. depressa will expand its range into Ireland as the climate warms, but we currently lack an empirical basis to predict the consequences of this change. Recent studies show that increasing abundance of P. depressa on British shores has been accompanied by a decline of P. vulgata suggesting interspecific competition. In this study, a new experimental framework was used to examine the potential for P. depressa to affect P. vulgata on Irish shores. P. vulgata was experimentally transplanted into enclosures on open rock and in pools in both Ireland and Britain. In pools, treatments also included transplanted P. ulyssiponensis to mimic natural assemblages. Growth and mortality of P. vulgata were measured over 6 months with no differences between Ireland and Britain. In Britain, P. vulgata caged in pools with transplanted P. depressa and P. ulyssiponensis showed reduced growth, compared with when caged in pools with P. ulyssiponensis alone. There was no effect of P. depressa on the growth rate of P. vulgata on open rock. Results indicate that if the range of P. depressa extends into Ireland, it would reduce the growth of P. vulgata where it co‐occurs with P. ulyssiponensis in pools. The framework used here provides a field‐based approach that could be used to examine the impacts of climate‐induced range expansions on the structure and functioning of other ecosystems.

Production of transgenic pineapple (Ananas cosmos (L.) Merr.) plants via adventitious bud regeneration - M.-L. Wang; G. Uruu; L. Xiong; X. He; C. Nagai; K. T. Cheah; J. S. Hu; G.-L. Nan; B. S. Sipes; H. J. Atkinson; P. H. Moore; K. G. Rohrbach; et al. (In Vitro Cellular & Developmental Biology - Plant, 2009)

A six-year study of fire-related flowering cues and coexistence of two perennial grasses in a wet longleaf pine (Pinus palustris) savanna - J. Stephen Brewer; Amy L. Cunningham; Timothy P. Moore; Randell M. Brooks; Joanne L. Waldrup (Plant Ecology, 2009)

Increased frequency of α-synuclein in the substantia nigra in human immunodeficiency virus infection - Negar Khanlou; Negar Khanlou; David J Moore; Negar Khanlou; David J Moore; Gursharan Chana; Mariana Cherner; Deborah Lazzaretto; Sharron Dawes; Igor Grant; Eliezer Masliah; Ian P Everall; et al. (Journal of NeuroVirology, 2009)

Population structure of spotted salamanders ( Ambystoma maculatum ) in a fragmented landscape - J. L. PURRENHAGE; P. H. NIEWIAROWSKI; F.B.‐G. MOORE (Molecular Ecology, 2009)
Understanding the impacts of landscape‐level processes on the population biology of amphibians is critical, especially for species inhabiting anthropogenically modified landscapes. Many pond‐breeding amphibians are presumed to exist as metapopulations, but few studies demonstrate the extent and consequences of this metapopulation structure. Gene flow measures may facilitate the construction of more realistic models of population structure than direct measures of migration. This is especially true for species that are cryptic, such as many amphibians. We used eight polymorphic microsatellite loci to determine the genetic population structure of spotted salamanders ( Ambystoma maculatum ) breeding at 17 ponds in northeastern Ohio, a landscape fragmented by roads, agriculture, urban areas and the Cuyahoga River. Using a variety of analyses (Bayesian clustering, F ‐statistics, AMOVA) we generated a model of salamander population genetic structure. Our data revealed patterns of genetic connectivity that were not predicted by geographical distances between ponds (no isolation by distance). We also tested for a relationship between population structure and several indices of landscape resistance, but found no effect of potential barriers to dispersal on genetic connectivity. Strong overall connectivity among ponds, despite the hostile habitat matrix, may be facilitated by a network of riparian corridors associated with the Cuyahoga River; however, high gene flow in this system may indicate a general ability to disperse and colonize beyond particular corridors.

The effect of carbon dioxide enrichment on apparent stem respiration from Pinus taeda L. is confounded by high levels of soil carbon dioxide - David J. P. Moore; Miquel A. Gonzalez-Meler; Lina Taneva; Jeffrey S. Pippen; Hyun-Seok Kim; Evan H. DeLucia (Oecologia, 2008)

Hydrogen sulphide is pro-inflammatory in haemorrhagic shock - Y.-Y. P. Mok; P. K. Moore (Inflammation Research, 2008)

COMPARATIVE ECOLOGY OF NORTH ATLANTIC SHORES: DO DIFFERENCES IN PLAYERS MATTER FOR PROCESS? - Stuart R. Jenkins; Pippa Moore; Michael T. Burrows; David J. Garbary; Stephen J. Hawkins; Agnar Ingólfsson; Kenneth P. Sebens; Paul V. R. Snelgrove; David S. Wethey; Sarah A. Woodin (Ecology, 2008)
The contrasting histories of the western and eastern shores of the North Atlantic Ocean provide an excellent opportunity to consider the implications of past events for present ecological processes and the functioning of marine ecosystems. Similarities and differences in assemblage composition have been driven by large‐scale events, such as the trans‐Arctic interchange, which has shaped the species pool, and cycles of glaciation, which have determined phases of local or regional extinction and colonization. More recently, anthropogenically induced invasions and local extinctions have significantly altered biogeographic distributions. Here we consider for both hard and soft substrata how the presence or absence of key taxa influences the outcomes of trophic and other biological interactions, and evaluate the consequences for community structure and ecosystem functioning. On intertidal hard substratum shores, biodiversity of epilithic microphagous grazers differs across latitudinal and longitudinal scales. Diversity is high in southern Europe but declines to the north and across the Atlantic. Lower diversity and the absence of patellid limpets in Iceland and the northwest Atlantic compared to Europe result in differences in consumer pressure, and an apparent contrast in the importance of herbivory vs. competitive interactions and predation pressure as community structuring processes. Interestingly, despite differences in “process,” community patterns are remarkably similar between the east and west. On soft sediment shores, there are conspicuous geographic differences in importance of bioturbators and large digging predators. Hemichordates can be abundant and important infaunal bioturbators in the western Atlantic, but they generally play a much reduced role in the eastern Atlantic. In addition, the number and diversity of digging predators on western Atlantic shores is high; the horseshoe crab, swimming portunid crabs, large whelks, excavating waterfowl, and an abundance of skates and rays exert intense predation pressure and associated biogenic disturbance to sediments. In Europe, except for excavating waterfowl these taxa are rare or absent. Thus, the importance of large, biological agents of disturbance is lower on European shores as a consequence of both recent anthropogenic pressure and natural processes over larger time scales. Consideration of key structuring taxa over the Atlantic shows that human‐mediated transport has had considerable influence. Faunas on both sides of the Atlantic are becoming more similar to the point that some of the key differences in assemblage composition and hence community organization have blurred. Recent introductions as well as planned experimental manipulations provide the opportunity to understand the role of species identity in determining community structure and ecosystem functioning over large spatial scales; the North Atlantic may be an ideal test system to explore these areas.

Nondestructive Scat Sampling in Assessment of Mink (Mustela vison) Exposed to Polychlorinated Dibenzofurans (PCDFs) - Matthew J. Zwiernik; Jeremy N. Moore; Jong Seong Khim; Lisa L. Williams; Denise P. Kay; Steve Bursian; Lesa L. Aylward; John P. Giesy (Archives of Environmental Contamination and Toxicology, 2008)

Rainbow Smelt (Osmerus mordax) Genomic Library and EST Resources - K. R. von Schalburg; J. Leong; G. A. Cooper; A. Robb; M. R. Beetz-Sargent; R. Lieph; R. A. Holt; R. Moore; K. V. Ewart; W. R. Driedzic; B. F. H. ten Hallers; B. Zhu; et al. (Marine Biotechnology, 2008)
Genomic resources in rainbow smelt ( Osmerus mordax ) enable us to examine the genome duplication process in salmonids and test hypotheses relating to the fate of duplicated genes. They further enable us to pursue physiological and ecological studies in smelt. A bacterial artificial chromosome library containing 52,410 clones with an average insert size of 146 kb was constructed. This library represents an 11-fold average coverage of the rainbow smelt ( O. mordax ) genome. In addition, several complementary deoxyribonucleic acid libraries were constructed, and 36,758 sequences were obtained and combined into 12,159 transcripts. Over half of these transcripts have been identified, several of which have been associated with cold adaptation. These basic resources show high levels of similarity (86%) to salmonid genes and provide initial support for genome duplication in the salmonid ancestor. They also facilitate identification of genes important to fish and direct us toward new technologies for other studies in fish biology.

Local and large‐scale climate forcing of Puget Sound oceanographic properties on seasonal to interdecadal timescales - Stephanie K. Moore; Nathan J. Mantua; Jonathan P. Kellogg; Jan A. Newton (Limnology and Oceanography, 2008)
The influence of climate on Puget Sound oceanographic properties is investigated on seasonal to interannual timescales using continuous profile data at 16 stations from 1993 to 2002 and records of sea surface temperature (SST) and sea surface salinity (SSS) from 1951 to 2002. Principal components analyses of profile data identify indices representing 42%, 58%, and 56% of the total variability at depth‐station combinations for temperature, salinity, and density, respectively, and 22% for water column stratification. Variability in the leading pattern of Puget Sound water temperature and salinity profiles is well correlated with local surface air temperatures and freshwater inflows to Puget Sound from major river basins, respectively. SST and SSS anomalies are informative proxies for the leading patterns of variations in Puget Sound temperature and salinity profiles. Using this longer time history of observations, we find that SST and SSS anomalies also have significant correlations with Aleutian Low, El Niñntilde;o‐Southern Oscillation, and Pacific Decadal Oscillation variations in winter that can persist for up to three seasons or reemerge the following year. However, correlations with large‐scale climate variations are weaker compared to those with local environmental forcing parameters.

Experimental evidence for extreme dispersal limitation in tropical forest birds - R. P. Moore; W. D. Robinson; I. J. Lovette; T. R. Robinson (Ecology Letters, 2008)
Movements of organisms between habitat remnants can affect metapopulation structure, community assembly dynamics, gene flow and conservation strategy. In the tropical landscapes that support the majority of global biodiversity and where forest fragmentation is accelerating, there is particular urgency to understand how dispersal across habitats mediates the demography, distribution and differentiation of organisms. By employing unique dispersal challenge experiments coupled with exhaustive inventories of birds in a Panamanian lacustrine archipelago, we show that the ability to fly even short distances (

Objective video quality measure for application to tele-echocardiography - Peter Thomas Moore; Neil O’Hare; Kevin P. Walsh; Neil Ward; Niamh Conlon (Medical & Biological Engineering & Computing, 2008)

Pitch and space maps of skilled cellists: accuracy, variability, and error correction - Jessie Chen; Marjorie H. Woollacott; Steven Pologe; George P. Moore (Experimental Brain Research, 2008)

Two canine CD1a proteins are differentially expressed in skin - Frank A. Looringh van Beeck; Dirk M. Zajonc; Peter F. Moore; Yvette M. Schlotter; Femke Broere; Victor P. M. G. Rutten; Ton Willemse; Ildiko Van Rhijn (Immunogenetics, 2008)

A Rapid Simultaneous Saccharification and Fermentation (SSF) Technique to Determine Ethanol Yields - Asli Isci; Patrick T. Murphy; Robert P. Anex; Kenneth J. Moore (BioEnergy Research, 2008)

Social spacing of crayfish in natural habitats: what role does dominance play? - K. Fero; P. A. Moore (Behavioral Ecology and Sociobiology, 2008)

Modeling whale entanglement injuries: An experimental study of tissue compliance, line tension, and draw‐length - Jeremy P. Winn; Becky L. Woodward; Michael J. Moore; Michael L. Peterson; John G. Riley (Marine Mammal Science, 2008)
Two test systems were developed to evaluate the influence of draw‐length and tissue compliance on entanglement‐induced epidermal abrasion in humpback ( Megaptera novaeangliae ) and right whale ( Eubalaena glacialis ) tissue samples. Under straight pull abrasion tests, an adult right whale fluke required 3.7 times the load and 15 times the draw‐length of a right whale calf flipper to induce epidermal failure whereas a humpback fluke was intermediate between these extremes. A load applied tangentially to the leading edge of the fluke or flipper resulted in a substantial, but reversible, deflection of the leading edge in the direction of the applied load. The maximum possible deformation of the leading edge under shear load, prior to the line slipping relative to the skin, was defined as the tissue compliance limit. Oscillatory abrasion tests revealed that line draw‐lengths exceeding the tissue compliance limit resulted in substantially increased tissue abrasion. In actual entanglements, line draw‐length relative to the tissue compliance may determine if the line will cut into the body or simply press against the skin. Increasing the entangling line's ability to stretch in response to a load could potentially minimize sliding of the line relative to the skin and help mitigate entanglement injuries.

Integration of Process-based Soil Respiration Models with Whole-Ecosystem CO2 Measurements - J. M. Zobitz; D. J. P. Moore; W. J. Sacks; R. K. Monson; D. R. Bowling; D. S. Schimel (Ecosystems, 2008)

Phosphatase activities in soil after repeated untreated and alum-treated poultry litter applications - P. J. Tomlinson; M. C. Savin; P. A. Moore (Biology and Fertility of Soils, 2008)

Relative influence of nitrogen and phosphorous availability on phytoplankton physiology and productivity in the oligotrophic sub‐tropical North Atlantic Ocean - C. Mark Moore; Matthew M. Mills; Rebecca Langlois; Angela Milne; Eric P. Achterberg; Julie La Roche; Richard J. Geider (Limnology and Oceanography, 2008)
Nutrient addition bioassay experiments were performed in the low‐nutrient, low‐chlorophyll oligotrophic subtropical North Atlantic Ocean to investigate the influence of nitrogen (N), phosphorus (P), and/or iron (Fe) on phytoplankton physiology and the limitation of primary productivity or picophytoplankton biomass. Additions of N alone resulted in 1.5‐2 fold increases in primary productivity and chlorophyll after 48 h, with larger (~threefold) increases observed for the addition of P in combination with N (NP). Measurements of cellular chlorophyll contents permitted evaluation of the physiological response of the photosynthetic apparatus to N and P additions in three picophytoplankton groups. In both Prochlorococcus and the picoeukaryotes, cellular chlorophyll increased by similar amounts in N and NP treatments relative to all other treatments, suggesting that pigment synthesis was N limited. In contrast, the increase of cellular chlorophyll was greater in NP than in N treatments in Synechococcus , suggestive of NP co‐limitation. Relative increases in cellular nucleic acid were also only observed in Synechococcus for NP treatments, indicating co‐limitation of net nucleic acid synthesis. A lack of response to relief of nutrient stress for the efficiency of photosystem II photochemistry, F v :F m , suggests that the low nutrient supply to this region resulted in a condition of balanced nutrient limited growth, rather than starvation. N thus appears to be the proximal (i.e. direct physiological) limiting nutrient in the oligotrophic sub‐tropical North Atlantic. In addition, some major picophytoplankton groups, as well as overall autotrophic community biomass, appears to be co‐limited by N and P.

Studying Daphnia feeding behavior as a black box: a novel electrochemical approach - D. C. Peñalva-Arana; P. A. Moore; B. A. Feinberg; J. DeWall; J. R. Strickler (Hydrobiologia, 2007)

Gauge repeatability and reproducibility for accessing variability during dissolution testing: A technical note - Zongming Gao; Terry Moore; Anjanette P. Smith; William Doub; Benjamin Westenberger; Lucinda Buhse (AAPS PharmSciTech, 2007)

Spring‐neap modulation of internal tide mixing and vertical nitrate fluxes at a shelf edge in summer - Jonathan Sharples; Jacqueline F. Tweddle; J. A. Mattias Green; Matthew R. Palmer; Young-Nam Kim; Anna E. Hickman; Patrick M. Holligan; C. Mark Moore; Tom P. Rippeth; John H. Simpson; Vladimir Krivtsov (Limnology and Oceanography, 2007)
Measurements of the intra‐tidal and spring‐neap variation in the vertical flux of nitrate into the base of the sub‐surface chlorophyll maximum (SCM) were made at the shelf edge of the Celtic Sea, a region with strong internal mixing driven by an internal tide. The neap tide daily mean nitrate flux was 1.3 (0.9‐1.8, 95% confidence interval) mmol m ‐2 d ‐1 . The spring tide flux was initially estimated as 3.5 (2.3‐5.2, 95% confidence interval) mmol m ‐2 d ‐1 . The higher spring tide nitrate flux was the result of turbulent dissipation occurring within the base of the SCM as compared to deeper dissipation during neap tides and was dominated by short events associated with the passage of internal solitons. Taking into account the likely under‐sampling of these short mixing events raised the spring tide nitrate flux estimate to about 9 mmol m ‐2 d ‐1 . The neap tide nitrate flux was sufficient to support substantial new production and a considerable fraction of the observed rates of carbon fixation. Spring tide fluxes were potentially in excess of the capacity of the phytoplankton community to uptake nitrate. This potential excess nitrate flux during spring tides may be utilized to support new production during the lower mixing associated with the transition toward neap tide. The shelf edge is shown to be a region with a significantly different phytoplankton community as compared to the adjacent Celtic Sea and northeast Atlantic Ocean, highlighting the role of gradients in physical processes leading to gradients in ecosystem structure.

Occurrence of Cryptosporidium parvum and Bacterial Pathogens in Faecal Material in the Red Fox (Vulpes vulpes) Population - Y. Nagano; M. B. Finn; C. J. Lowery; T. Murphy; J. Moriarty; E. Power; D. Toolan; A. O’Loughlin; M. Watabe; K. A. McCorry; E. Crothers; J. S. G. Dooley; et al. (Veterinary Research Communications, 2007)

A QTL on chromosome 6A in bread wheat (Triticum aestivum) is associated with longer coleoptiles, greater seedling vigour and final plant height - W. Spielmeyer; J. Hyles; P. Joaquim; F. Azanza; D. Bonnett; M. E. Ellis; C. Moore; R. A. Richards (Theoretical and Applied Genetics, 2007)

Effect of adenoviral mediated overexpression of fibromodulin on human dermal fibroblasts and scar formation in full-thickness incisional wounds - Alexander Stoff; Angel A. Rivera; J. Michael Mathis; Steven T. Moore; N. S. Banerjee; Maaike Everts; Antonio Espinosa-de-los-Monteros; Zdenek Novak; Luis O. Vasconez; Thomas R. Broker; Dirk F. Richter; Dale Feldman; et al. (Journal of Molecular Medicine, 2007)

Mercury and Methylmercury Accumulation and Excretion in Prairie Voles (Microtus ochrogaster) Receiving Chronic Doses of Methylmercury - G. P. Cobb; A. W. Moore; K. T. Rummel; B. M. Adair; S. T. McMurry; M. J. Hooper (Archives of Environmental Contamination and Toxicology, 2007)

Elevated placental expression of the imprinted PHLDA2 gene is associated with low birth weight - S. Apostolidou; S. Abu-Amero; K. O’Donoghue; J. Frost; O. Olafsdottir; K. M. Chavele; J. C. Whittaker; P. Loughna; P. Stanier; G. E. Moore (Journal of Molecular Medicine, 2007)

Unobtrusive integration of data management with fMRI analysis - Andrew V. Poliakov; Xenia Hertzenberg; Eider B. Moore; David P. Corina; George A. Ojemann; James F. Brinkley (Neuroinformatics, 2007)

Fires in tropical forests – what is really the problem? lessons from Indonesia - L. Tacconi; P. F. Moore; D. Kaimowitz (Mitigation and Adaptation Strategies for Global Change, 2006)

Flurbiprofen and its nitric oxide-releasing derivative protect against septic shock in rats - F. Anuar; M. Whiteman; M. Bhatia; P. K. Moore (Inflammation Research, 2006)

Explicit formula for the geoid-quasigeoid separation - R. Tenzer; P. Novák; P. Moore; M. Kuhn; P. Vaníček (Studia Geophysica et Geodaetica, 2006)

Atmospheric effects in the derivation of geoid-generated gravity anomalies - R. Tenzer; P. Novák; P. Moore; P. Vajda (Studia Geophysica et Geodaetica, 2006)

New insights from MALDI-ToF MS, NMR, and GC-MS: mass spectrometry techniques applied to palynology - S. E. M. Moore; A. R. Hemsley; A. N. French; E. Dudley; R. P. Newton (Protoplasma, 2006)

Annual basal area increment and growth duration of Pinus taeda in response to eight years of free‐air carbon dioxide enrichment - DAVID J. P. MOORE; SUSANNE AREF; RINGO M. HO; JEFFREY S. PIPPEN; JASON G. HAMILTON; EVAN H. DE LUCIA (Global Change Biology, 2006)
Rising CO 2 is predicted to increase forest productivity, although the duration of the response and how it might be altered by variation in rainfall, temperature and other environmental variables are not well understood. We measured the basal area of rapidly growing Pinus taeda trees exposed to free‐air CO 2 enrichment for 8 years and used these measurements to estimate monthly and annual growth. We used these measurements in a statistical model to estimate the start and end of growth in each year. Elevated CO 2 increased the basal area increment ( BAI ) of trees by 13–27%. In most years, exposure to elevated CO 2 increased the growth rate but not the duration of the active growth period. With the exception of 1 year following an extreme drought and a severe ice storm, BAI was positively correlated with the amount of rainfall during the active growth period. The interannual variation in the relative enhancement of BAI caused by elevated CO 2 was strongly related to temperature and rainfall, and was greatest in years with high vapor pressure deficit. There was no evidence of a systematic reduction in the stimulation of growth during the first 8 years of this experiment, suggesting that the hypothesized limitation of the CO 2 response caused by nitrogen availability has yet to occur.

Identification ofArcobacter species using phospholipid and total fatty acid profiles - D. Jelínek; P. Miketová; L. Khailová; K. H. Schram; I. M. (Ki) Moore; J. Vytřasová (Folia Microbiologica, 2006)

An examination of the diversity of a novel Campylobacter reservoir - William J. Snelling; James P. McKenna; Catherine J. Hack; John E. Moore; James S. G. Dooley (Archives of Microbiology, 2006)

Spatial variability of stable isotopes and fossil pigments in surface sediments of Alaskan coastal lakes: Constraints on quantitative estimates of past salmon abundance - Curtis S. Brock; Peter R. Leavitt; Daniel E. Schindler; Susan P. Johnson; Jonathan W. Moore (Limnology and Oceanography, 2006)
We quantified spatial patterns of stable isotopes of N and C (δ 15 N, δ 13 C) and fossil pigment concentrations in the uppermost 10 mm of sediment (,10 yr) from 74 profundal locations and three spawning‐stream discharge areas in Lake Nerka, southwest Alaska. Sediment δ 15 N (4.3% ± 0.7%) and δ 13 C (−26.3% ± 1.2%) varied directly (δ 15 N) or inversely (δ 13 C) with water column depth, whereas concentrations of most fossil pigments from algae were negatively correlated with depth. Sediment δ 15 N and δ 13 C were poorly correlated with either fossil pigment abundance or the local densities of spawning salmon. Instead, coastal nursery lakes appeared to integrate marine‐derived nutrients rapidly into lakewide nutrient pools, suggesting that while individual cores may be used to reconstruct whole‐lake salmon densities, habitat‐specific variations of past fish populations cannot be quantified reliably from sedimentary analyses.

Prosthetic valve endocarditis due to coagulase-negative staphylococci: findings from the International Collaboration on Endocarditis Merged Database - T. Lalani; Z. A. Kanafani; V. H. Chu; L. Moore; G. R. Corey; P. Pappas; C. W. Woods; C. H. Cabell; B. Hoen; C. Selton-Suty; T. Doco-Lecompte; C. Chirouze; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2006)

A method for estimating inherent optical properties of New Zealand continental shelf waters from satellite ocean colour measurements - Matthew H. Pinkerton; Gerald F. Moore; Samantha J. Lavender; Mark P. Gall; Kadija Oubelkheir; Kenneth M. Richardson; Philip W. Boyd; James Aiken (New Zealand Journal of Marine and Freshwater Research, 2006)
We describe a method to estimate spectral absorption and backscattering coefficients between 412 and 555 nm from measurements of remote sensing reflectance across the visible spectrum. The algorithm described is applicable to ocean colour satellite measurements (e.g., SeaWiFS). In situ measurements of inherent and apparent optical properties were made at 19 coastal stations off the north coast of New Zealand's South Island in December 2001. These measurements were used to parameterise a bio‐optical model that estimates remote sensing reflectance from concentrations of water constituents. The model generated a large number (5000) of modelled ocean colour reflectance spectra that represented a greater range of biogeochemical conditions than were measured in the study area. These modelled values spanned a wide range of chlorophyll concentrations (0.1–10 mg m ‐3 ), total suspended particulate material concentrations (0.1–50 g m ‐3 ), and dissolved yellow substance absorptions (0.01–3 m ‐1 ). The modelled spectra were then used to test the performance of the algorithm. The median ratio of algorithm values to target values was 0.84 (absorption), and 0.80 (backscatter), and the median absolute errors were 33% (absorption) and 36% (backscatter) across two orders of magnitude. The r 2 values between target and algorithm values of inherent optical properties in log‐log space were 0.89 for backscatter, and varied with wavelength for absorption from 0.79 (412 nm), 0.72 (443 nm), 0.63 (490 nm), 0.55 (510 nm), and 0.21 (555 nm).

Medium-term impacts of hydraulic clam dredgers on a macrobenthic community of the Adriatic Sea (Italy) - Elisabetta B. Morello; Carlo Froglia; R. James A. Atkinson; P. Geoffrey Moore (Marine Biology, 2006)

EXPERIMENTAL MODELING OF LARGE WHALE ENTANGLEMENT INJURIES - Becky L. Woodward; Jeremy P. Winn; Michael J. Moore; Michael L. Peterson (Marine Mammal Science, 2006)
The abrasive impact of commercial fishing gear on right whale fluke tissue was modeled using a reciprocating load generator. A line passing over the leading edge of a fluke specimen was fixed at one end while the other end was loaded in an oscillatory manner. A 24‐h abrasion test using an accelerated loading rate of 60 cycles/min and a 9.0‐kg load on the fixed end of the most abrasive line tested (old sink line) was used to simulate a whale swimming 2 m/s towing four standard lobster buoys for five days. A tension load of 267 N was generated on the oscillatory side of the fluke. The test line failed to break the skin on the fluke but, instead, produced a compression furrow (maximum depth 0.31 cm) that closely resembled marks found on stranded right ( Eubalaena glacialis ) and humpback ( Megaptera novaeangliae ) whales. Different line types (float vs . sink) and ages of rope (new vs. old) produced furrows of varying depths and appearances. Further tests characterizing whale skin/fishing line interactions will provide a better understanding of the mechanisms that govern entanglement injuries and provide a framework for better forensic analysis and interpretation of gear‐related injuries observed in large whales.

Iron limits primary productivity during spring bloom development in the central North Atlantic - C. MARK MOORE; MATTHEW M. MILLS; ANGELA MILNE; REBECCA LANGLOIS; ERIC P. ACHTERBERG; KARIN LOCHTE; RICHARD J. GEIDER; JULIE LA ROCHE (Global Change Biology, 2006)
We present in situ biophysical measurements and bioassay experiments that demonstrate iron limitation of primary productivity during the spring bloom in the central North Atlantic. Mass balance calculations indicate that nitrate drawdown is iron (Fe)‐limited and that aeolian Fe supply to this region cannot support maximal phytoplankton growth during the bloom. Using a simple simulation model, we show that relief of Fe limitation during the spring bloom can increase nitrate drawdown and, hence, new primary production, by 70%. We conclude that the episodic nature of iron supplied by dust deposition is an important factor controlling the dynamics of the spring bloom. From this, we hypothesize that variability in the timing and magnitude of the spring bloom in response to aeolian Fe supply will affect carbon drawdown and food web dynamics in the central North Atlantic.

Sterol carrier protein-2 expression alters sphingolipid metabolism in transfected mouse L-cell fibroblasts - Daniel G. Milis; Messiah K. Moore; Barbara P. Atshaves; Friedhelm Schroeder; John R. Jefferson (Molecular and Cellular Biochemistry, 2006)

Physiological state of phytoplankton communities in the Southwest Atlantic sector of the Southern Ocean, as measured by fast repetition rate fluorometry - Claire L. Holeton; Florence Nédélec; Richard Sanders; Louise Brown; C. Mark Moore; David P. Stevens; Karen J. Heywood; Peter J. Statham; Cathy H. Lucas (Polar Biology, 2005)

The South African and Namibian Populations of the Resurrection Plant Myrothamnus flabellifolius are Genetically Distinct and Display Variation in Their Galloylquinic Acid Composition - John P. Moore; Jill M. Farrant; George G. Lindsey; Wolf F. Brandt (Journal of Chemical Ecology, 2005)

Case Study Part 2: Probabilistic Modelling of Long-term Effects of Pesticides on Individual Breeding Success in Birds and Mammals - W. ROELOFS; D.R. CROCKER; R.F. SHORE; D.R.J. MOORE; G.C. SMITH; H.R. AKCAKAYA; R.S. BENNETT; P.F. CHAPMAN; M. CLOOK; M. CRANE; I.C. DEWHURST; P.J. EDWARDS; et al. (Ecotoxicology, 2005)

Case Study Part 1: How to Calculate Appropriate Deterministic Long-Term Toxicity to Exposure Ratios (TERs) for Birds and Mammals - R.F. SHORE; D.R. CROCKER; H.R. AKCAKAYA; R.S. BENNETT; P.F. CHAPMAN; M. CLOOK; M. CRANE; I.C. DEWHURST; P.J. EDWARDS; A. FAIRBROTHER; S. FERSON; D. FISCHER; et al. (Ecotoxicology, 2005)

A non‐invasive method to assess the impact of electronic tag insertion on stress levels in fishes - N. Lower; A. Moore; A. P. Scott; T. Ellis; J. D. James; I. C. Russell (Journal of Fish Biology, 2005)
The present study investigated, for the first time, a non‐invasive technique for monitoring cortisol levels in fishes that had been implanted with electronic transmitters. This technique involved the measurement of cortisol released into the water by individual fish. Carp Cyprinus carpio and roach Rutilus rutilus that had been tagged with miniature dummy acoustic transmitters responded to the surgical implantation of the tags with an immediate (1 to 4 h) increase in cortisol concentrations in the water. These amounts of cortisol were higher than in ‘handled only’ and ‘handled and anaesthetized’ groups. Estimated cortisol release rates for both species correlated well with the direct measurements in the water. In both species, water cortisol concentration and cortisol release rates returned to pre‐stress levels within 12 h of tag‐insertion, and remained low for the remainder of the experiment. The calculation of cortisol release rates highlighted a difference of a factor of about four between peak release rates in carp and roach. There was no evident long‐term cortisol stress response to the presence of a tag in the body cavity in either species.

Relationship between communities and processes; new insights from a field study of a contaminated ecosystem - Philip W. Ramsey; Matthias C. Rillig; Kevin P. Feris; Nathan S. Gordon; Johnnie N. Moore; William E. Holben; James E. Gannon (Ecology Letters, 2005)
We used a 93‐year‐old mine waste contamination gradient in alluvial soil to explore the relationship between ecosystem level functioning and community structure in a chronically stressed ecosystem. The sensitivity of broad functional parameters ( in situ soil respiration, microbial biomass, above and below ground plant biomass) and microbial diversity [phospholipid fatty acid (PLFA) abundance and richness] were compared. Functional responses were linear with respect to contaminants while thresholds were detected in the community structural response to contamination along the gradient. For example, in situ soil respiration was negatively and linearly correlated to contamination concentration ( R = −0.783, P

Life Cycle Assessment of Water Recycling Technology - N. Tangsubkul; P. Beavis; S. J. Moore; S. Lundie; T. D. Waite (Water Resources Management, 2005)

Construction of a Festuca pratensis BAC library for map-based cloning in Festulolium substitution lines - Iain S. Donnison; Donal M. O’Sullivan; Ann Thomas; Peter Canter; Beverley Moore; Ian Armstead; Howard Thomas; Keith J. Edwards; Ian P. King (Theoretical and Applied Genetics, 2005)

The influence of climate on the timing and rate of spring bird migration - Peter P. Marra; Charles M. Francis; Robert S. Mulvihill; Frank R. Moore (Oecologia, 2005)

Insights into the genomic basis of niche specificity of Pseudomonas putida KT2440 - V. A. P. Martins Dos Santos; S. Heim; E. R. B. Moore; M. Strätz; K. N. Timmis (Environmental Microbiology, 2004)
Summary A major challenge in microbiology is the elucidation of the genetic and ecophysiological basis of habitat specificity of microbes. Pseudomonas putida is a paradigm of a ubiquitous metabolically versatile soil bacterium. Strain KT2440, a safety strain that has become a laboratory workhorse worldwide, has been recently sequenced and its genome annotated. By drawing on both published information and on original in silico analysis of its genome, we address here the question of what genomic features of KT2440 could explain or are consistent with its ubiquity, metabolic versatility and adaptability. The genome of KT2440 exhibits combinations of features characteristic of terrestrial, rhizosphere and aquatic bacteria, which thrive in either copiotrophic or oligotrophic habitats, and suggests that P. putida has evolved and acquired functions that equip it to thrive in diverse, often inhospitable environments, either free‐living, or in close association with plants. The high diversity of protein families encoded by its genome, the large number and variety of small aralogous families, insertion elements, repetitive extragenic palindromic sequences, as well as the mosaic structure of the genome (with many regions of ‘atypical’ composition) and the multiplicity of mobile elements, reflect a high functional diversity in P. putida and are indicative of its evolutionary trajectory and adaptation to the diverse habitats in which it thrives. The unusual wealth of determinants for high affinity nutrient acquisition systems, mono‐ and di‐oxygenases, oxido‐reductases, ferredoxins and cytochromes, dehydrogenases, sulfur metabolism proteins, for efflux pumps and glutathione‐S‐transfereases, and for the extensive array of extracytoplasmatic function sigma factors, regulators, and stress response systems, constitute the genomic basis for the exceptional nutritional versatility and opportunism of P. putida , its ubiquity in diverse soil, rhizosphere and aquatic systems, and its renowned tolerance of natural and anthropogenic stresses. This metabolic diversity is also the basis of the impressive evolutionary potential of KT2440, and its utility for the experimental design of novel pathways for the catabolism of organic, particularly aromatic, pollutants, and its potential for bioremediation of soils contaminated with such compounds as well as for its application in the production of high‐added value compounds.

Discrepancy Between Antennal and Behavioral Responses for Enantiomers of α-Pinene: Electrophysiology and Behavior of Helicoverpa armigera (Lepidoptera) - C. D. Hull; J. P. Cunningham; C. J. Moore; M. P. Zalucki; B. W. Cribb (Journal of Chemical Ecology, 2004)

Statistical Issues in a Modeling Approach to Assessing Bioequivalence or PK Similarity with Presence of Sparsely Sampled Subjects - Chuanpu Hu; Katy H. P. Moore; Yong H. Kim; Mark E. Sale (Journal of Pharmacokinetics and Pharmacodynamics, 2004)

Green fluorescent protein as a visual selection marker for papaya ( Carica papaya L.) transformation - P. H. Moore; Y. J. Zhu; R. Agbayani (Plant Cell Reports, 2004)

Climatic Suitability, Life‐History Traits, Introduction Effort, and the Establishment and Spread of Introduced Mammals in Australia - DAVID M. FORSYTH; RICHARD P. DUNCAN; MARY BOMFORD; GEOFF MOORE (Conservation Biology, 2004)
Major progress in understanding biological invasions has recently been made by quantitatively comparing successful and unsuccessful invasions. We used such an approach to test hypotheses about the role of climatic suitability, life history, and historical factors in the establishment and subsequent spread of 40 species of mammal that have been introduced to mainland Australia. Relative to failed species, the 23 species that became established had a greater area of climatically suitable habitat available in Australia, had previously become established elsewhere, had a larger overseas range, and were introduced more times. These relationships held after phylogeny was controlled for, but successful species were also significantly more likely to be nonmigratory. A forward‐selection model included only two of the nine variables for which we had data for all species: climatic suitability and introduction effort. When the model was adjusted for phylogeny, those same two variables were included, along with previous establishment success. Of the established species, those with a larger geographic range size in Australia had a greater area of climatically suitable habitat, had traits associated with a faster population growth rate (small body size, shorter life span, lower weaning age, more offspring per year), were nonherbivorous, and had a larger overseas range size. When the model was adjusted for phylogeny, the importance of climatic suitability and the life‐history traits remained significant, but overseas range size was no longer important and species with greater introduction effort had a larger geographic range size. Two variables explained variation in geographic range size in a forward‐selection model: species with smaller body mass and greater longevity tended to have larger range sizes in Australia. These results mirror those from a recent analysis of exotic‐bird introductions into Australia, suggesting that, at least among vertebrate taxa, similar factors predict establishment and spread. Our approach and results are being used to assess the risks of exotic vertebrates becoming established and spreading in Australia.

An EST survey of the sugarcane transcriptome - H.-M. Ma; S. Schulze; S. Lee; M. Yang; E. Mirkov; J. Irvine; P. Moore; A. Paterson (Theoretical and Applied Genetics, 2004)

Construction of a genetic map for arabica coffee - H. M. Pearl; C. Nagai; P. H. Moore; D. L. Steiger; R. V. Osgood; R. Ming (Theoretical and Applied Genetics, 2004)

Haplotype mapping of the bronchiolitis susceptibility locus near IL8 - Jeremy Hull; Kate Rowlands; Elizabeth Lockhart; Mike Sharland; Catrin Moore; Neil Hanchard; Dominic P. Kwiatkowski (Human Genetics, 2004)

Association of cone thermogenesis and volatiles with pollinator specificity in Macrozamia cycads - I. Terry; C. J. Moore; G. H. Walter; P. I. Forster; R. B. Roemer; J. D. Donaldson; P. J. Machin (Plant Systematics and Evolution, 2004)

Release of sex steroids into the water by roach - N. Lower; A. P. Scott; A. Moore (Journal of Fish Biology, 2004)
Electro‐olfactogram (EOG) recordings of the olfactory epithelium of both male and female roach Rutilus rutilus demonstrated that both sexes were able to detect free and glucuronidated 17,20β‐dihydroxy‐4‐pregnen‐3‐one (17,20β‐P) with high sensitivity. Male, but not female, roach were also sensitive to androstenedione. Sexually mature female roach were shown to release free 17,20β‐P, glucuronidated 17,20β‐P and androstenedione into the water; for all three steroids, the rate of release was significantly enhanced by injection of carp pituitary extract (CPE). A series of trials was also carried out which showed that mature males, and to a lesser extent immature males and females, were able also to release free and glucuronidated 17,20β‐P, both before and after CPE treatment. Water extracts from containers that had held CPE‐treated mature male and female roach were examined for the presence of other steroids. This revealed that free and glucuronidated 17,20β‐P plus free and glucuronidated 17,20β,21‐trihydroxy‐4‐pregnen‐3‐one (17,20β, 21‐P) predominated in water extracts from both sexes. The free moieties of 17,20α‐dihydroxy‐4‐pregnen‐3‐one, 17‐hydroxyprogesterone and 11‐deoxycortisol were found at concentrations which were between four and 20 times lower than those of free 17,20β‐P. Androstenedione was found at concentrations which were 25‐fold lower than those of 17,20β‐P. Despite its apparent high rate of release by sexually mature male and female roach, free 17,20β,21‐P was found not to exhibit any EOG activity at the highest dose tested (10 −7 M).

Wollastonite at the Sterling Hill Fe?Zn?Mn ore body, Ogdensburg, New Jersey - A. Dzs-Moore; P. B. Leavens; R. E. Jenkins II; N. M. Altounian (Mineralogy and Petrology, 2003)

Error analyses of CHAMP data for recovery of the Earth?s gravity field - P. Moore; J.F. Turner; Z. Qiang (Journal of Geodesy, 2003)

Construction and characterisation of a hexaploid wheat (Triticum aestivum L.) BAC library from the reference germplasm ‘Chinese Spring’ - S. Allouis; G. Moore; A. Bellec; R. Sharp; P. Faivre Rampant; K. Mortimer; S. Pateyron; T. N. Foote; S. Griffiths; M. Caboche; B. Chalhoub (Cereal Research Communications, 2003)

Sedimentary Nonylphenol Contamination in an Urbanized, Industrialized Segment of the Delaware River Estuary, USA - J. T. F. Ashley; A. Moore; H. M. Stapleton; D. J. Velinsky; M. P. Wilhelm (Bulletin of Environmental Contamination and Toxicology, 2003)

An outbreak of Fusarium head blight of durum wheat on the Liverpool Plains in northern New South Wales in 1999 - R. J. Southwell; K. J. Moore; W. Manning; P. T. Hayman (Australasian Plant Pathology, 2003)

DDC and COBL, flanking the imprinted GRB10 gene on 7p12, are biallelically expressed - Megan P. Hitchins; Louise Bentley; David Monk; Colin Beechey; Jo Peters; Gavin Kelsey; Fumitoshi Ishino; Michael A. Preece; Philip Stanier; Gudrun E. Moore (Mammalian Genome, 2002)

AFLP analysis of genetic diversity within and among Coffea arabica cultivars - D. Steiger; C. Nagai; P. Moore; C. Morden; R. Osgood; R. Ming (Theoretical and Applied Genetics, 2002)

Molecular dissection of complex traits in autopolyploids: mapping QTLs affecting sugar yield and related traits in sugarcane - R. Ming; Y. Wang; X. Draye; P. Moore; J. Irvine; A. Paterson (Theoretical and Applied Genetics, 2002)

Ravens ( Corvus corax corax L.) in the British landscape: a thousand years of ecological biogeography in place‐names - P. G. Moore (Journal of Biogeography, 2002)
Aim To investigate the information content of place‐names regarding the habits, habitat and biogeography of ravens in Britain over the past millennium. Location England, Scotland and Wales. Methods Linguistic and ecological analysis of over 400 British place‐names that have a putative ‘raven’ derivation. Results Most of the ‘raven’ place‐names are Old English in origin. Some of these (a minority), however, derive from personal names. The derivations of most names reflect landscape rather than man‐made features; the majority relating to high, craggy ground or coastal features, a minority to wooded situations or human habitations. In lowland Scotland and the Scottish borders the colloquial name corbie dominates ‘raven’ place‐names, perhaps reflecting French influence. In the Highlands and the Western Isles the Gaelic fitheach and its derivatives are predominant. Relatively fewer place‐names that have ‘raven’ roots have been educed in other parts of the Celtic West, i.e. Wales and Cornwall (only one traced in the latter). Main conclusions Comparison of the geographical distribution of ‘raven’‐derived place‐names with the present‐day distribution of the species in Britain reveals the extent of the contraction in the raven's range to the West over historical time, most notably during theprevious two centuries, associated with changed land‐management practices in particular.

A meta‐analysis of elevated [CO 2 ] effects on soybean ( Glycine max ) physiology, growth and yield - Elizabeth A. Ainsworth; Phillip A. Davey; Carl J. Bernacchi; Orla C. Dermody; Emily A. Heaton; David J. Moore; Patrick B. Morgan; Shawna L. Naidu; Hyung‐shim Yoo Ra; Xin‐guang Zhu; Peter S. Curtis; Stephen P. Long (Global Change Biology, 2002)
The effects of elevated [CO 2 ] on 25 variables describing soybean physiology, growth and yield are reviewed using meta‐analytic techniques. This is the first meta‐analysis to our knowledge performed on a single crop species and summarizes the effects of 111 studies. These primary studies include numerous soybean growth forms, various stress and experimental treatments, and a range of elevated [CO 2 ] levels (from 450 to 1250 p.p.m.), with a mean of 689 p.p.m. across all studies. Stimulation of soybean leaf CO 2 assimilation rate with growth at elevated [CO 2 ] was 39%, despite a 40% decrease in stomatal conductance and a 11% decrease in Rubisco activity. Increased leaf CO 2 uptake combined with an 18% stimulation in leaf area to provide a 59% increase in canopy photosynthetic rate. The increase in total dry weight was lower at 37%, and seed yield still lower at 24%. This shows that even in an agronomic species selected for maximum investment in seed, several plant level feedbacks prevent additional investment in reproduction, such that yield fails to reflect fully the increase in whole plant carbon uptake. Large soil containers (> 9 L) have been considered adequate for assessing plant responses to elevated [CO 2 ]. However, in open‐top chamber experiments, soybeans grown in large pots showed a significant threefold smaller stimulation in yield than soybeans grown in the ground. This suggests that conclusions about plant yield based on pot studies, even when using very large containers, are a poor reflection of performance in the absence of any physical restriction on root growth. This review supports a number of current paradigms of plant responses to elevated [CO 2 ]. Namely, stimulation of photosynthesis is greater in plants that fix N and have additional carbohydrate sinks in nodules. This supports the notion that photosynthetic capacity decreases when plants are N‐limited, but not when plants have adequate N and sink strength. The root : shoot ratio did not change with growth at elevated [CO 2 ], sustaining the charge that biomass allocation is unaffected by growth at elevated [CO 2 ] when plant size and ontogeny are considered.

Ultrafast Flow Quantification With Segmented k-Space Magnetic Resonance Phase Velocity Mapping - Haosen Zhang; Sandra S. Halliburton; James R. Moore; Orlando P. Simonetti; Paulo R. Schvartzman; Richard D. White; George P. Chatzimavroudis (Annals of Biomedical Engineering, 2002)

An Interactive Management System for Operational Control of Kirazdere Reservoir (Turkey) - Z. Rao; I. N. Moore; P. E. O’Connell; D. G. Jamieson (Water Resources Management, 2001)

The ERS-2 altimetric bias and gravity field enhancement using dual crossovers between ERS and TOPEX/Poseidon - P. Moore (Journal of Geodesy, 2001)

A spectral optimally interpolated mean sea surface from satellite radar altimetry - R. A. Cullen; P. Moore (Journal of Geodesy, 2001)

Construction and characterization of a papaya BAC library as a foundation for molecular dissection of a tree-fruit genome - R. Ming; P. H. Moore; F. Zee; C. A. Abbey; H. Ma; A. H. Paterson (Theoretical and Applied Genetics, 2001)

Changes in the haemagglutinin and the neuraminidase genes prior to the emergence of highly pathogenic H7N1 avian influenza viruses in Italy - J. Banks; E. S. Speidel; E. Moore; L. Plowright; A. Piccirillo; I. Capua; P. Cordioli; A. Fioretti; D. J. Alexander (Archives of Virology, 2001)

Phytoplankton distribution and survival in the thermocline - Jonathan Sharples; Mark C. Moore; Tom P. Rippeth; Patrick M. Holligan; David J. Hydes; Neil R. Fisher; John H. Simpson (Limnology and Oceanography, 2001)
Observations of the vertical structure of density, concentrations of chlorophyll a and nitrate, and turbulent dissipation rates were made over a period of 25 h in a well‐stratified shelf region in the Western English Channel, between neap and spring tides. Maximum turbulent dissipation at the base of the thermocline occurred almost 5 h after maximum tidal currents. This turbulence aids phytoplankton growth by supplying bottom‐layer nutrients into the subsurface chlorophyll maximum but reduces phytoplankton concentrations in the thermocline by mixing cells from the base of the subsurface maximum into the bottom mixed layer. The turbulent dissipation observations were used to estimate an average nitrate flux into the thermocline of 2.0 (0.8‐3.2, 95% confidence interval) mmol m −2 d −1 , which is estimated to have been capable of supporting new phytoplankton growth at a rate of 160 (64–256) mg C m −2 d −1 . Turbulent entrainment of carbon from the base of the subsurface biomass maximum into the bottom mixed layer was observed to be 290 (120–480) mg C m −2 d −1 . This apparent excess export from the chlorophyll maximum is suggested to be a feature of the spring‐neap cycle, with export dominating as the tidal turbulence increases toward spring tides and erodes the base of the thermocline. The observed rate of carbon export into the bottom mixed layer could account for as much as 25% of the gross annual primary production in stratifying shelf seas. Such turbulent losses, combined with grazing losses and low light levels, suggest that phytoplankton need to be highly adapted to environmental conditions within the thermocline in order to survive.

Characterization of active nitrogen pools in soils under different cropping systems - S. P. Deng; J. M. Moore; M. A. Tabatabai (Biology and Fertility of Soils, 2000)

Misidentification of soil bacteria by fatty acid methyl ester (FAME) and BIOLOG analyses - N. Oka; P. G. Hartel; O. Finlay-Moore; J. Gagliardi; D. A. Zuberer; J. J. Fuhrmann; J. S. Angle; H. D. Skipper (Biology and Fertility of Soils, 2000)

World‐wide genetic differentiation of Eubalaena : questioning the number of right whale species - H. C. Rosenbaum; R. L. Brownell; M. W. Brown; C. Schaeff; V. Portway; B. N. White; S. Malik; L. A. Pastene; N. J. Patenaude; C. S. Baker; M. Goto; P. B. Best; et al. (Molecular Ecology, 2000)
Few studies have examined systematic relationships of right whales ( Eubalaena spp.) since the original species descriptions, even though they are one of the most endangered large whales. Little morphological evidence exists to support the current species designations for Eubalaena glacialis in the northern hemisphere and E. australis in the southern hemisphere. Differences in migratory behaviour or antitropical distribution between right whales in each hemisphere are considered a barrier to gene flow and maintain the current species distinctions and geographical populations. However, these distinctions between populations have remained controversial and no study has included an analysis of all right whales from the three major ocean basins. To address issues of genetic differentiation and relationships among right whales, we have compiled a database of mitochondrial DNA control region sequences from right whales representing populations in all three ocean basins that consist of: western North Atlantic E. glacialis , multiple geographically distributed populations of E. australis and the first molecular analysis of historical and recent samples of E. glacialis from the western and eastern North Pacific Ocean. Diagnostic characters, as well as phylogenetic and phylogeographic analyses, support the possibility that three distinct maternal lineages exist in right whales, with North Pacific E. glacialis being more closely related to E. australis than to North Atlantic E. glacialis . Our genetic results provide unequivocal character support for the two usually recognized species and a third distinct genetic lineage in the North Pacific under the Phylogenetic Species Concept, as well as levels of genetic diversity among right whales world‐wide.

A novel restriction fragment length polymorphism for petrels or tube‐nosed seabirds - C. D. Millar; G. A. Taylor; P. J. Moore; J. L. Halverson; D. M. Lambert (Molecular Ecology, 2000)

Cloning and characterization of NBS-LRR class resistance-gene candidate sequences in citrus - Z. Deng; S. Huang; P. Ling; C. Chen; C. Yu; C. A. Weber; G. A. Moore; F.G. Gmitter (Theoretical and Applied Genetics, 2000)

Anthropogenic, Climatic, and Hydrologic Trends in the Kosi Basin, Himalaya - Keshav P. Sharma; Berrien Moore; Charles J. Vorosmarty (Climatic Change, 2000)

Sensitivity of the Himalayan Hydrology to Land-Use and Climatic Changes - Keshav P. Sharma; Charles J. Vorosmarty; Berrien Moore (Climatic Change, 2000)

An investigation into the efficacy of intravenous diclofenac in post-operative dental pain - R. A. Seymour; U. Moore; J. Hawkesford; P. Coulthard; D. Jackson-Leech; D. Thomas; M. Hill; M. L. Combs; T. Renton; M. McGurk (European Journal of Clinical Pharmacology, 2000)

Characterisation of oxidised 7Fe dicluster ferredoxins with NMR spectroscopy - Jonathan P. Hannan; Johanneke L. H. Busch; Jacques Breton; Richard James; Andrew J. Thomson; Geoffrey R. Moore; S. L. Davy (JBIC Journal of Biological Inorganic Chemistry, 2000)

Transgenic Trifolium repens with foliage accumulating the high sulphur protein, sunflower seed albumin - P. Christiansen; J.M. Gibson; A. Moore; C. Pedersen; L. Tabe; P.J. Larkin (Transgenic Research, 2000)

Characterization of microsatellite loci in the redclaw crayfish, Cherax quadricarinatus - N. Baker; K. Byrne; S. Moore; P. Mather (Molecular Ecology, 2000)

A combined RFLP and AFLP linkage map of upland rice (Oryza sativa L.) used to identify QTLs for root-penetration ability - A. H. Price; K. A. Steele; B. J. Moore; P. P. Barraclough; L. J. Clark (Theoretical and Applied Genetics, 2000)

Specific inhibitors of inducible nitric oxide synthase: Efficacy in a rodent model of sepsis - D. J. Fretland; D. L. Widomski; C. P. Anglin; W. Moore , G. Jerome , C. Kornmeier; E. A. Hallinan; T. Hagen; A. Bergmanis; B. Pitzele (Inflammation Research, 1999)

Cultivation of epithelia from the secretory coil of the ovine apocrine gland: Evidence of secretory cell function and ductal morphogenesis In vitro - Z. Maras; G. Yardley; E. Deane; G. P. M. Moore (In Vitro Cellular & Developmental Biology - Animal, 1999)

RELATIVE ABUNDANCE OF LARGE WHALES AROUND SOUTH GEORGIA (1979–1998) 1 - M. J. Moore; S. D. Berrow; B. A. Jensen; P. Carr; R. Sears; V. J. Rowntree; R. Payne; P. K. Hamilton (Marine Mammal Science, 1999)
A bstract To assess large‐whale stocks following the cessation of land‐based South Georgia whaling in 1965, we report three independent sighting databases: a cruise in 1997, observations from Bird Island (NW of South Georgia) between 1979 and 1998, and mariner sightings between 1992 and 1997. All species were rare, with sightings of southern right whales being the most common event. Two right whales photographed off South Georgia matched animals known from Peninsula Valdés, Argentina, a population known to be growing at 7% per annum . In contrast, blue and fin whales appeared to be less abundant. A single blue whale mother‐calf pair was observed off the Shag Rocks in February 1997. Extirpation of animals from this particular feeding ground is the most likely reason for ongoing low numbers of all species. Other factors may include competition for krill by traditional predators such as penguins and seals and more recently by humans, an unusually high rate of natural mortality, habitat change such as alteration in sea ice coverage, and/or the impact of ongoing whaling. The history of this critical area of large‐whale habitat and this report demonstrate the need for improved, consistent longterm monitoring of population trends for these depleted stocks.

Reproductive priming in mature male Atlantic salmon parr exposed to the sound of redd cutting - A. Moore; C. P. Waring (Journal of Fish Biology, 1999)
The sounds of a wild female Atlantic salmon cutting a redd were associated with significant increases in the levels of plasma 17,20β‐dihydroxy‐4‐pregnen‐3‐one (17,20βP) and of expressible milt in mature male parr, comparable with levels of the steroid and milt produced in parr exposed to the priming pheromone, prostaglandin F 2a . Hence auditory cues may have a significant role in synchronising reproductive physiology in Atlantic salmon.

Optical Thin-Film Sensors for the Determination of Aqueous Halide Ions - Chris D. Geddes; Peter Douglas; Christopher P. Moore; Trevor J. Wear; Peter L. Egerton (Journal of Fluorescence, 1999)

Evaluation of NASH and RT-PCR for the detection of PVY in dormant tubers and its comparison with visual symptoms and ELISA in plants - M. Singh; R. P. Singh; L. Moore (American Journal of Potato Research, 1999)

The effects of black tea and other beverages on aspects of cognition and psychomotor performance - I. Hindmarch; P. T. Quinlan; K. L. Moore; C. Parkin (Psychopharmacology, 1998)

Accuracy assessment and refinement of the JGM-2 and JGM-3 gravity fields for radial positioning of ERS-1 - P. Moore; S. Ehlers; S. Carnochan (Journal of Geodesy, 1998)

Effect of nickel(II) substitution on the resonance Raman and NMR spectra of Alcaligenes xylosoxidans azurin II: implications for axial-ligand bonding interactions in cupredoxin active sites - Jonathan P. Hannan; Sharon L. Davy; Geoffrey R. Moore; Robert R. Eady; C. R. Andrew (JBIC Journal of Biological Inorganic Chemistry, 1998)

CXC chemokines mechanism of action in regulating tumor angiogenesis - Bethany B. Moore; Douglas A. Arenberg; Christina L. Addison; Michael P. Keane; Peter J. Polverini; Robert M. Strieter (Angiogenesis, 1998)

Boundary-layer effect on chemical signal movement near the antennae of the sphinx moth, Manduca sexta : temporal filters for olfaction - R. W. S. Schneider; J. Lanzen; P. A. Moore (Journal of Comparative Physiology A, 1998)

Demonstration of peripheral fucose units in N-linked glycans of human immunodeficiency virus type 1 gp 120: effects on glycoprotein conformation - A. Bolmstedt; M. Biller; J. -E. S. Hansen; J. P. Moore; S. Olofsson (Archives of Virology, 1997)

l -2-Chloropropionic acid-induced cerebellar granule cell necrosis is potentiated by L-type calcium channel antagonists - P. S. Widdowson; A. Gyte; R. Upton; J. C. E. Smith; M. Pitts; R. Moores; I. Wyatt (Archives of Toxicology, 1997)

Potato leafroll virus detection by RT-PCR in field-collected aphids - Rudra P. Singh; J. Kurz; G. Boiteau; Lynn M. Moore (American Journal of Potato Research, 1997)

Tenidap inhibits 5-lipoxygenase product formation in vitro, but this activity is not observed in three animal models - T. J. Carty; F. J. Sweeney; R. J. Griffiths; J. D. Eskra; M. J. Ernest; J. S. Pillar; J. D. Cheng; L. D. Loose; P. A. Joseph; P. P. Pazoles; P. F. Moore; A. Nagahisa; et al. (Inflammation Research, 1997)

Regional Biodiversity Planning and Lemur Conservation with GIS in Western Madagascar - A. P. Smith; N. Horning; D. Moore (Conservation Biology, 1997)
Primary forest cover in western Madagascar declined from 12.5% in 1950 to 2.8% in 1990. Approximately 23% of remaining forest is located within reserves, but this is no guarantee of protection. Forest cover in the Andranomena Reserve in western Madagascar has been reduced by 44% since 1950. The identification of priority areas for establishment of development projects has been constrained by lack of information on the distribution, abundance, and habitat requirements of threatened species and the size, condition, and threats to survival of forest remnants. We evaluate a rapid fauna survey and habitat modeling procedure specifically designed to generate information for reserve selection and design using Geographical Information Systems (GIS). The study was conducted in the largest remnant (94,000 ha) of primary monsoon rainforest in western Madagascar, using lemurs as an indicator group. Lemur abundance and microhabitat variables were measured at 64 stratified survey sites dispersed throughout the region. These records were incorporated into a GIS with other environmental and landuse data derived from maps and satellite imagery. Statistical procedures were applied to analyze species habitats, predict and map species distributions, and estimate species population sizes throughout the study area. Patterns of slash and burn agriculture and anthropogenic disturbance were also analyzed to identify areas at low risk of cultural disturbance. A map of disturbance risk was overlaid with a map of relative lemur biodiversity to identify conservation priority areas with high biodiversity and low risk of short term disturbance. Lemur diversity was most strongly influenced by habitat clearing and human disturbance (harvesting, stock grazing, and hunting) within 8 km of villages. Lemur diversity was highest in a region of higher elevation and rainfall, distant from villages and roads. The only existing reserve in the study area was located in a region of high disturbance risk. Almost half the reserve has been degraded during the past 45 years. There is considerable scope for re‐allocation of land use within the study area to include a core protected area, a buffer zone with controlled hunting and timber harvesting, and an adjacent ecotourism facility. We found that information generated by a stratified biodiversity and landuse survey at a sampling intensity of less than 0.1% was sufficient to provide an objective foundation for regional biodiversity planning.

Influence of soil hydric parameters on the winter cold hardiness of a burrowing beetle, Leptinotarsa decemlineata (Say) - J. P. Costanzo; J. B. Moore; R. E. Lee Jr.; P. E. Kaufman; J. A. Wyman (Journal of Comparative Physiology B, 1997)

A geopotential error analysis for a non planar satellite to satellite tracking mission - R. Mackenzie; P. Moore (Journal of Geodesy, 1997)

An EBV-transformed owl monkey B-lymphocyte cell line - J. G. Scammell; P. D. Reynolds; M. Y. Elkhalifa; J. A. Tucker; C. M. Moore (In Vitro Cellular & Developmental Biology - Animal, 1997)

A medium-density genetic linkage map of the bovine genome - W. Barendse; D. Vaiman; S. J. Kemp; Y. Sugimoto; S. M. Armitage; J. L. Williams; H. S. Sun; A. Eggen; M. Agaba; S. A. Aleyasin; M. Band; M. D. Bishop; et al. (Mammalian Genome, 1997)

Experimental analysis of fluid mechanical energy losses in aortic valve stenosis: Importance of pressure recovery - Russell S. Heinrich; Arnold A. Fontaine; Randall Y. Grimes; Aniket Sidhaye; Serena Yang; Kristin E. Moore; Robert A. Levine; Ajit P. Yoganathan (Annals of Biomedical Engineering, 1996)

Mating strategies and mating success of fallow (Dama dama) bucks in a non-lekking population - N. P. Moore; P. F. Kelly; J. P. Cahill; T. J. Hayden (Behavioral Ecology and Sociobiology, 1995)

Mating strategies and mating success of fallow ( Dama dama ) bucks in a non-lekking population - N. P. Moore; P. F. Kelly; J. P. Cahill; T. J. Hayden (Behavioral Ecology and Sociobiology, 1995)

Effect of sunscreens, irradiance and resting periods on the germination ofMetarhizium flavoviride conidia - T. R. Hunt; D. Moore; P. M. Higgins; C. Prior (BioControl, 1994)

Urinary creatine profiles after administration of cell-specific testicular toxicants to the rat - Nigel P. Moore; Dianne M. Creasy; Tim J. B. Gray; John A. Timbrell (Archives of Toxicology, 1992)

The integration of pasture, livestock and widely-spaced pine in South West Western Australia - G. W. Anderson; R. W. Moore; P. J. Jenkins (Agroforestry Systems, 1988)

The integration of pasture, livestock and widely-spaced pine in South West Western Australia - G. W. Anderson; R. W. Moore; P. J. Jenkins (Agroforestry Systems, 1988)

Synchronizing human movement with an external clock source - D. Hary; G. P. Moore (Biological Cybernetics, 1987)

A glycine betaine transport system in Aphanothece halophytica and other glycine betaine-synthesising cyanobacteria - D. J. Moore; R. H. Reed; W. D. P. Stewart (Archives of Microbiology, 1987)

Proteins expressed by Mill Door/79 virus, a Kemerovo serogroup orbivirus transmitted by the ticksIxodes uriae - R. P. Spence; J. S. K. Pullin; N. F. Moore (Archives of Virology, 1986)

The proteins expressedin vivo andin vitro by an orbivirus of the Kemerovo serogroup isolated fromIxodes uriae ticks from St. Abb's Head, Scotland - S. M. Eley; P. A. Nuttall; N. F. Moore (Archives of Virology, 1985)

The biochemistry of orbiviruses - R. P. Spence; N. F. Moore; Patricia A. Nuttall (Archives of Virology, 1984)

How can we interpret the zero tolerance for bacterial ring rot in certified seed potatoes - C. E. Logsdon; H. W. Poulsen; John J. Adams; J. W. Scannell; C. W. Frutchey; Robert Hickman; T. C. Blackburn; J, L. Robinson; E. L. Newdick; Paul J. Eastman; L. O. Weaver; H. C. Moore; et al. (American Journal of Potato Research, 1957)

Crop and market news - B. A. Brown; H. C. Moore; P. N. Davis; J. F. Sharples; H. O. Werner; O. C. Hicks; J. Gilbert Borton; H. C. Odell; E. V. Hardenburg (American Journal of Potato Research, 1926)

Crop and market news - B. A. Brown; K. P. Bemis; E. A. Stokdyk; G. D. Clark; H. C. Moore; A. G. Tolaas; H. O. Werner; Wm. Martin; E. V. Hardenburg; W. K. McCulock; H. H. Zimmerly; J. G. Milward (American Journal of Potato Research, 1926)

Brighter outlook for potatoes - J. G. Lipman; H. O. Werner; E. P. Miller; Walter M. Peacock; Julian Dimock; R. F. Howard; R. G. Newton; Wm. H. Martin; George H. Valentine; Dee Crane; O. C. Hicks; H. C. Moore (American Journal of Potato Research, 1925)

Kiwanians sponsor potato club work - P. R. Young; E. V. Hardenburg; B. E. Brown; Paul M. Williams; Daniel Dean; A. G. Waller; H. R. Talmage; H. C. Moore; J. G. Milward; W. Stuart; H. B. Stevens; R. W. Goss; et al. (American Journal of Potato Research, 1925)

Potato notes - C. Tice; H. G. Zuckerman; W. C. Edmundson; W. L. Floyd; G. W. Waller; A. J. Johnston; E. P. Miller; E. A. Stokdyk; G. L. Tiebout; H. C. Moore; Walter M. Peacock; Andrew Schnetzler; et al. (American Journal of Potato Research, 1925)